Transcription factor SlbZIP12 affects tomato shelf life by mediating the ethylene biosynthesis at postharvest stage - Abdul Karim Amin; Wenyi Zhu; Pengwei Li; Shi Shi; Mengru Qin; Yan He; Huizhen Zhang; Hong Yao; Shuqi Chen; Hamza Latif; Mohammad Yousof Soltani; Mahmood Hemat; et al. (Postharvest Biology and Technology, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Paternal vitamin D deficiency is associated with offspring testicular developmental abnormalities, fibrosis, and altered sperm miRNA profiles - Yu-Ming Chen; Zhi-Hong Tian; Shi-Yuan Li; Juan Dai; Xing-Ru Wang; Guo-Ying Sun; Min Liu; Berthold Hocher; Mei Tian (Molecular Biology Reports, 2026)

A SASP-related four-gene signature associated with intervertebral disc degeneration: integrated bioinformatics analysis and validation of pinocembrin as a therapeutic candidate - Ge-Liang Yao; Shi-Jiang Wang; Ying Zhang; Jia-Ming Liu; Hong-Hai Song; Zhi-Li Liu (Molecular Biology Reports, 2026)

New variant in KITLG shapes the pathogenesis of familial progressive hyper- and hypo-pigmentation - Bodan Wu; Ming He; Tongyun Liu; Wenjing Zhao; Jianhong Ye; Tao Jiang; Congcong Teng; Yaxin Huang; Yangjia Zhang; Jiao Li; Hong Shi; Jie Zhang (Molecular Genetics and Genomics, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Urea-induced nitrogen-rich pyrolysis for co-upgrading of sludge-derived biochar and bio-oil - Ruizhi Wang; Junhong Chen; Jinze Li; Yi Yang; Li Gu; Dezhi Shi; Hong Cheng; Weiliang Pan; Yongdong Chen (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Experimental and analytical investigations of composite girders with CSW-CFST chord-UHPC slab under impact loading - Wei Xian; Shuang-Shuang Li; Wen-Da Wang; Yan-Li Shi; Wei-Hong Wu; Wensu Chen (Engineering Structures, 2026)

Superior removal of phthalate acid esters from water using a magnetic PIM-1 adsorbent - Ruobing Jia; Shunying Li; Keda Guo; Shiqi Yang; Yingying Zhang; Qiangqiang Xu; Hong Ye; Hehe Li; Shuangyang Li; Shengpeng Shi (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Groundwater-constrained screening of ecological restoration priority areas through integrating MSPA–MCR and MODFLOW: A case study of the West Liao River Plain, China - Pengxin Cao; Long Yan; Dili Li; Tianyin Xu; Tianyu Shi; Yanhang Hu; Zifeng Hong (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Functional characterization of a plant germacrene D-4-ol synthase enabling the production of bioactive α-cadinol and τ-muurolol under changed catalysis conditions - Shao-Jun Cheng; Shi-Jie Liu; Wan-Jun Liang; Qin-Qin Shen; Zhong-Zhu Yuan; Zong-Hua Xiao; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Enhanced solar-driven interfacial vapor generation of lignite-based aerogel via water and thermal dual management - Mei Xiong; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Zhao Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Journal of Environmental Chemical Engineering, 2026)

Microplastics and nanoplastics: Characterizing potential health perturbations and mechanistic evidence - Ting-Shuo Lu; Shi-Yun Wang; Yue-Xi Liu; Fang-Yuan Teng; Hong-Xia Li (Food Research International, 2026)

Integrating ecological networks and metagenomics to decipher core microbial drivers of organic acid metabolism during heaped fermentation of sauce-flavor Baijiu - Hong-Yan Zhang; Ting-Cai Huang; Li-Juan Chai; Wei Shi; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Research International, 2026)

Decoding the thermocyclic solar-driven fermentation: Multi-omics insights into microbial and metabolic dynamics of traditional Chishui river basin soy sauce - Wei-Qin Deng; Zhen-Ming Lu; Xiong-Bo Li; Zhi-Yi Fan; Ting Li; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Chemistry, 2026)

From black box to transparency: Explainable artificial intelligence driven origin identification of Xinjiang Nilka black bee honey - Xiao-Hui Sun; Lin-Hua Shi; Xiang-Shuai Li; Xiu-Ying Tang; Hong-Song Ren; Sheng-Hong Liu (Food Chemistry, 2026)

Concentration-dependent interfacial reconstruction governs the thermal stability of whey protein microgels-sucrose ester hybrid Pickering emulsions - Xiang Li; Yingxiang Li; Qianyi Ye; Yaoxi Zhang; Sihan Cheng; Yikai Chen; Hong Liu; Tongfei Shi; Jie Xiao (Food Hydrocolloids, 2026)

Delocalized π-electron polymeric nanoflowers with dual redox functionalities for high-capacity and ultrafast capacitive removal of Sr(II) - Jiawei Wu; Lintong Hu; Yuting Peng; Yize Li; Ying Hong; Jun Yang; Minjie Shi; Yuqing Lin (Environmental Research, 2026)

Picolinic acid enhances peroxymonosulfate activation by trace Fe(II) for excellent performance in ultrafiltration treatment of surface water: The dominant role of non-radical pathways - Bing Zhang; Xiangyou Yue; Heli Tang; Guoqiang Hong; Binghan Li; Bing Zhang; Bin Liu; Wenxin Shi (Desalination, 2026)

Solvation engineering of dual-polymer gel electrolyte via competitive coordination effect for durable lithium metal batteries - Xiaoya Qu; Na Li; Hao Zhai; Zhengyuan Bai; Yong Liu; Hao Wang; Shu Hong; Zhenyue Xing; Xiaodong Shi; Peng Wang (Chemical Engineering Journal, 2026)

Cantharidin triggers cardiotoxicity via reactive anhydride-mediated covalent protein modification - Yaya Fan; Chengjiang He; Yeli Li; Ni Li; Chao Fang; Fuguo Shi; Hong Pan (Chemico-Biological Interactions, 2026)

Quantifying taxonomy-function associations across hierarchical scales of bacterial nitrogen cycling - Mingli Jiang; Yanni Huang; Zhiming Wu; Qian Zhu; Qian Li; Kaihua Pan; Mingliang Zhang; Liang Shi; Jiguo Qiu; Pengfa Li; Xin Yan; Yiyong Zhu; et al. (Soil Ecology Letters, 2026)

Electroacupuncture-induced gut microbiota alterations correlate with FXR/FGF15 activation and metabolic improvement in hyperlipidemic rats - Huan Wu; Li Zhou; Wei Lin; Hong-xing Zhang; Zhao-qing Zhang; Xiao-fei Wang; Shi-ru Ju; Zhi-gang Liu; Fei Hu (Advances in Traditional Medicine, 2026)

Weed stem dual-stage localization by crop exclusion: A case study on carrot fields - Hong Xu; Yang Li; Xianwei Hou; Huarui Wu; Guanshan Zhang; Guoying Shi; Tianhua Li (Crop Protection, 2026)

A fully human antibody A140 neutralizes abrin toxin via lysosomal intracellular mechanisms, confers potent protection in vitro and in vivo, and reverses transcriptomic dysregulation with a Favorable safety profile - Feng Qin; Shi-You Chen; Peng Lin; Bin Wang; Xin Fu; Jian-Li Jiang; Hong-Yong Cui; Shi-Jie Wang (Toxicology and Applied Pharmacology, 2026)

Interfacial contact evolution enables low-temperature early warning of lithium-ion battery thermal runaway - Ruixin Ma; Jingyu Chen; Fei Xia; Jieqi Cao; Qiang Li; Hong Kang; Dandong Wang; Binbin Yu; Weixiong Wu; Junye Shi; Jiangping Chen (Process Safety and Environmental Protection, 2026)

The coupled dissolution and re-precipitation process controlling gold remobilization: A case study of the Taolegai gold deposit, North China Craton - Zheng-yang Zhang; Le Yang; Jian Li; Shi-yong Li; Kai-lei Xu; Hong-jiang Shi; Wen-yan Cai; Lei-lei Dong (Geochemistry, 2026)

From outcrossing to reproductive assurance: Seasonal plasticity in the breeding system of bi-seasonal flowering Tamarix ramosissima Ledeb. (Tamaricaceae) - Meng-Yuan Zhang; Jia-Hui Leng; Hong-Ju Cui; Jun-Xue Shi; Yuan-yuan Li; Xiang Shi (Flora, 2026)

Chronic paracetamol exposure disrupts behavior and induces intrinsic apoptosis in a freshwater bivalve - Yun-xia Hou; Shi-yin Tang; Wang Liu; Zhi-tong Li; Kai-jian Wei; Xiang-sheng Hong; Jian-hui Qin; Jin-miao Zha (Environmental Pollution, 2026)

Single-precursor-enabled surface/near-surface engineering for stabilizing oxygen redox in high-voltage Li-rich layered cathodes - Yujia Zhang; Shi Gu; Fuliang Guo; Pengcheng Yuan; Ao Li; Nan Zhang; Liang Yin; Hong Li (Chemical Engineering Journal, 2026)

Concentration-dependent variation in carbon allocation and microbial assembly in chain elongation microbiota: Comparative effects of acetate, ethanol, and lactate - Ya-Ning Song; Li-Juan Chai; Ling Ao; Jun-Lan Mei; Yu-Long Li; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Bioresource Technology, 2026)

Grass Carp Reovirus ( GCRV ): Biology, Immune Responses and Control Strategies - Waqar Younas; Mijuan Shi; Rong Huang; Yaping Wang; Libo He; Hong Yang; Lei Zhang; Yingyin Cheng; Wanting Zhang; Lanjie Liao; Yongming Li; Bin Gui; et al. (Reviews in Aquaculture, 2026)
As the world's population grows, aquaculture is becoming a rapidly growing source of protein. Grass carp ( Ctenopharyngodon idella ) is one of the most important aquacultured species in China and has emerged as a significant commercial fish worldwide. However, grass carp reovirus (GCRV) poses a significant threat to grass carp aquaculture. This review covers GCRV biology, phylogeny, pathogenesis, immune response pathways, therapeutic approaches, and future challenges and directions. A comprehensive phylogenetic analysis describes the structure of GCRV, its entry into cells, its molecular architecture, its replication procedures and its interactions with the host, with a particular focus on the pivotal role of Pattern Recognition Receptors (PRRs). The paper explores how PRRs, such as RLRs (RIG‐I and MDA5) and TLRs (TLR3 and TLR19), are essential for identifying GCRV and initiating robust antiviral responses, particularly the interferon pathway. The paper goes on to explain the complex immune evasion tactics employed by GCRV, emphasizing how viral proteins such as VP41, VP4 and VP56 selectively target and interfere with critical components of PRR signaling cascades, such as MAVS‐TBK1 and MITA/STING, thereby reducing host immunity. Various next‐generation vaccines are being developed, including DNA, subunit, VLP and oral/mucosal platforms. These are supported by Chinese herbal and chemical antivirals. According to CRISPR/Cas9, experimental RNAi, PI4KB and SOCS3a/3b are host genes that can be altered to increase grass carp resistance to GCRV. This research offers significant insights into viral cell invasion and strengthens innate and adaptive immunity, enabling safer, more practical and multilayered control in aquaculture.

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

Integrative whole-transcriptome analysis of circRNAs, lncRNAs, miRNAs, and mRNAs reveals regulatory networks in mouse brain during Toxoplasma gondii infection - Xiao-Dan Yuan; He Ma; Shi-Chen Xie; Hong-Chao Sun; Chao Chen; Xin-Yu Wei; Zhong-Yuan Li; Jing Jiang; Hany M. Elsheikha; Yu-Zhe Sun (The Veterinary Journal, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A future cornerstone for the cold archives in the artificial intelligence era: multidimensional optical data storage - Zi-Ting Liu; Shi-Jie Song; Xin Zhang; Guo-Hong Liu; Ke-Mi Xu; Qi-Dai Chen; Yu-Hao Lei; Zhen-Ze Li; Lei Wang (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Prospective life cycle assessment for high-value hydrogen from plastic waste by catalytic microwave processing: from laboratory to industrial scale - Zihao Shi; Zhenzhen Hong; Mengying Chen; Mulan Tu; Chuanping Li; Fen Wei; Xiong Peng; Xiaochuan Chen; Junxiong Wu; Yuming Chen; Qinghua Chen; Wei-Qiang Chen; et al. (Resources, Conservation and Recycling, 2026)

Emerging dactylellinatone attractant aids in the predation of nematodes by nematode-trapping fungus Dactylellina haptotyla - Hong-Mei Lei; Guang-Ke Zhang; Guo-Hong Li; Shi-Mei Shen; Min Deng; Pei-Ji Zhao (Pesticide Biochemistry and Physiology, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Fusarielins Q–Y: fusarielin polyketides from Fusarium asiaticum QA-6 inhabiting the roots of the cultivated Artemisia argyi and their antibacterial activity against aquatic pathogens - Xiao-Shan Shi; Sui-Qun Yang; Yu-Liang Dong; Xiao-Ming Li; Ling-Hong Meng; Yan-He Li; Dun-Jia Wang; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Probing oxidation of hydroxy-polycyclic aromatic hydrocarbons at air-water interface in water microdroplets - Xiaohui Shi; Jiahui Huang; Siyu Zhu; Yuexin Zhang; Pei Liu; Bo Li; Hong Zhang; Yun Ju; Jing Zhao; Jie Jiang; Jing He (Journal of Hazardous Materials, 2026)

Indium enrichment in VMS deposits: insights from sphalerite geochemistry and thermodynamic modeling of the Tiemurt Pb-Zn-Cu deposit, NW China - Min Luo; Peng-Peng Yu; Yi Zheng; Jie-Jun Lei; Xi Chen; Yi-Han Wu; Hong-Xiang Shan; Quan-Jie Li; Zhuo-Xiong Shi (Journal of Geochemical Exploration, 2026)

Ion-specific phase behaviors of gluconate aerosols regulated by alkali metal counter-cations: a supramolecular network stiffness perspective - Mengyun Shi; Wenjing Li; Shufeng Pang; Fei Zhao; Yun-Hong Zhang (Journal of Environmental Sciences, 2026)

Transition metal-coordinated metastable [MoS4]2- cluster for SO2-facilitated gaseous mercury adsorption from wet flue gas - Chaobin Shi; Qinyuan Hong; Zhen Qi; Jiaenbota Ayiding; Sichao Li; Wenjun Huang; Zan Qu; Zhenghong Luo; Naiqiang Yan; Haomiao Xu (Journal of Environmental Sciences, 2026)

Deciphering Qu-aroma in Nongxiangxing baijiu via a customized aroma base solution - Sheng-Bing Yang; Zhen-Ming Lu; Jia-Nan Hu; Ting-Yao Tu; Man-Si Niu; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; et al. (Food Research International, 2026)

Investigation of the interaction between phloretin and Staphylococcus aureus toxin proteins and its application in chicken meat - Hong Li; Ce Shi; Tariq Aziz; Nawal Al-Hoshani; Manal F. Elkhadragy; Abdelrahman R. Ahmed; Haiying Cui; Lin Lin (Food Chemistry, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

Functional characterization of the MdMYB73L gene in drought and salt stress tolerance in apple - Xiao-Wen Li; Han-Yu Dong; Ya-Qi Liu; Jing-Yi Su; Xue Wang; Chang Li; Qi-Fei Wu; Wen-Xian Zhang; Xin-Rong Shi; Hong-Jian Cao; Qiangbo Liu; Xiao-Fei Wang; et al. (Plant Molecular Biology, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

A single-cell transcriptomic atlas of the spotted scat testis reveals two Sertoli cell subclusters with differential dmrt1Y expression - Yu Li; Mou-Yan Jiang; Shan-Ni Cao; You-Xing Peng; Yuan-Qing Huang; Hong-Juan Shi; Hua-Pu Chen; Tian-Li Wu; Dong-Neng Jiang (Aquaculture, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Ginsenoside Rg3 ameliorates di-(2-ethylhexyl) phthalate-induced spermatogenic impairment via attenuating ferroptosis and restoring sertoli cell secretory dysfunction - Xu-Fei Gao; Nan Ma; Yu-Zhuo Zhang; Jing Zhang; Zhi Liu; Hong-Yan Zhu; Xiao-Jie Gong; Yin-Shi Sun; Di Qu; Jun-Nan Hu; Zi Wang; Wei Li (Journal of Environmental Sciences, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Microwave enhanced regeneration of CO2 adsorbents: Mechanistic study and theoretical modeling via fluorescence thermometry - Yuanwen Shi; Zhenyu Zhao; Hong Li; Xin Gao (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Computational-guided semi-rational design to reprogram phospholipase D into industrially robust enzyme - Xiao-Li Kong; Peng Zhang; Zheng-Qiang Qin; Chang Su; Heng Li; Zhen-Ming Lu; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2026)

Cloning and functional analysis of MdCRCT1 in the regulation of drought tolerance in apple - Xiao-Wen Li; Ya-Qi Liu; Jing-Yi Su; Xin-Rong Shi; Chang Li; Xue Wang; Qi-Fei Wu; Xuan He; Hong-Jian Cao; Xiao-Fei Wang; Ting-Ting Zhang (Physiology and Molecular Biology of Plants, 2026)

The eastern branch fault model of the Tanlu Fault zone and its controlling effect on hydrocarbon accumulation: A case study of southern section of Bohai Sea - Ji-mei Deng; Shi-qiang Xia; Wen-hui Huang; Peng Wu; Gang Han; Hong Li (Applied Geophysics, 2026)

Extracting cropping patterns from remotely sensed images in a mixed single-, double-, and triple-cropping region of Southern China - Yifan Li; Chen Cheng; Xiaoming Shi; Hong Chi; Yifei Han; Fei Zhao; Jinliang Huang; Feng Ling (Environmental Monitoring and Assessment, 2026)

Genetic effects on feeding habits: An integrated analysis of intestinal histomorphology, digestive enzyme activities, and multi-omics in hybrids from Micropterus salmoides ♀ × Lepomis cyanellus ♂ - Haitao Zhong; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Hong Chen; Mingli Liu; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

Mitigation of membrane fouling by electric field in anaerobic membrane bioreactor for domestic sewage treatment - Peng Xiao; Hong Zhao; Yajun Li; Jinyuan Jiang; Wei Tan; Haoyang Song; Dongni Shi; Xuwen He; Jian Wang (Journal of Environmental Chemical Engineering, 2026)

Zircon U-Pb dating and geochemistry of the Paleoproterozoic tuffs from the Nsama formation in northeastern Zambia - Jun-ping Ren; A-lei Gu; Hong-wei Sun; Li-bo Zuo; Jie Wang; Bao-jin Zhao; Evaristo Kasumba; Shi Xing; Zi-jiang Liu; Jin-meng Dong; Jin-rui Zhang; Ji-hai Chen (Journal of African Earth Sciences, 2026)

Zinc isotopic fractionation during magmatic differentiation and hydrothermal processes: implications for Li mineralization in the Jiajika granitic pegmatites, Sichuan, China - Jia-Wen Liu; Shi-Hong Tian; Xian-Lei Geng; Ying-Li Gong; Lu Chen; Shi-Qi Huang (Geochimica et Cosmochimica Acta, 2026)

DeepLrn-Source: Deep learning powered landslide source identification - Lu-Yu Ju; Ze-Ning Zhao; Shi-Hao Xiao; Yuan-En Pang; Jian He; Yun-Hong Lv; Ruo-Chen Jiang; Xin He; Li-Min Zhang (Engineering Geology, 2026)

A power-law relationship between bulk modulus and permeability in fractured sandstone: Insights from tidal analysis - Xu-Lin Tang; Xiao-Wei Jiang; Zhe-Ming Shi; Zhi-Yu Qi; De-Qiang Mao; Xu-Sheng Wang; Yan Zhang; Li Wan; Hong-Bin Yan (Engineering Geology, 2026)

Predictive design of UV-curable bio-based polyurethane acrylate adhesives: Integrating viscoelasticity, adhesion, and controlled degradation - Bowen Xu; Weiyi Wang; Honghu Li; Gaoteng Shi; Hong Jiang; Chang Su; Shaoyu Wang; Tong Wan; Biao Wang; Bowen Cheng (Chemical Engineering Journal, 2026)

Rational design of carbon dots with pyrrole rings for visible in vitro diagnosis of vulnerable atherosclerotic plaque - Xuelian Wang; Wanting Fu; Minye Ji; Jian Zhang; Jia Qi; Junli Zuo; Ying Chen; Yan He; Qingwen Gu; Hong Wu; Zhilei Cong; Jinping Li; et al. (Chemical Engineering Journal, 2026)

Design of millimeter-sized porous carbon spheres guided by hydrodynamic principles - Xiao-Dong Shi; Cheng-Tong Wang; Wen-Cui Li; Hong-Lei Wang; An-Hui Lu (Chemical Engineering Journal, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

Effects of Conventional and Biodegradable Microplastics on Soil Physicochemical Properties and Microorganisms - Haixia Liu; Meng Li; Hong Yu; Lingling Shi (Agricultural Research, 2026)

Gonadogenesis in Farmed Bivalves: Factors Driving Sex Differentiation and Gametogenesis - Ahmed Mokrani; Chenyu Shi; Pierre Boudry; Liliana Milani; Kazue Nagasawa; Hong Yu; Qi Li; Shikai Liu (Reviews in Aquaculture, 2026)
Optimization of aquaculture output requires a thorough assessment of growth and reproductive performance in farmed fish and shellfish, as a clear understanding of the reproductive trait regulation is essential for selective breeding programs. This review aims to provide a comprehensive synthesis of gonadogenesis and its regulatory mechanisms in farmed bivalves, while highlighting key knowledge gaps that remain to be addressed. In the first section, we present an overview of germ cell and associated somatic cell development and interaction, review sex determination/differentiation, and describe the reproductive modes and gametogenic processes observed in these sessile organisms following sexual maturation. Secondly, we outline current knowledge of the mechanistic regulatory processes controlling these traits, including the roles of key genes, epigenetic control, and transcriptional regulators. Furthermore, we integrate recent molecular, cellular, and physiological findings, while critically highlighting key points where knowledge remains limited or incomplete, and where further validation and investigation are required. Finally, we summarize recent advances concerning the effect of external factors and elucidate how environmental factors such as water temperature, food availability, and chemical contaminants mechanistically affect gonadogenesis. Despite advancement and significant progress driven by hatchery technologies and sophisticated research methodologies, a comprehensive understanding of the interactions between environmental and genetic factors shaping this peculiar process remains elusive. Future research incorporating multi‐omics approaches holds great promise for disentangling the genetic and regulatory architecture underlying gonadogenesis in these organisms, hence improving aquaculture production and breeding programs.

Docosahexaenoic acid alleviates Ornidazole toxicity related to spermatogenic dysfunction by modulating PPARγ-dependent ER-mitochondrial uncoupling - Chuwei Li; Shanmeizi Zhao; Chongli Shi; Shanshan Sun; Zhaowanyue He; Yao Xu; Lu Zheng; Ting Tang; Shengjie Qiu; Kuan Liang; Hong Zhang; Zhichuan Zou; et al. (Science China Life Sciences, 2026)

Isolation of new sesquiterpene glycosides from Dendrobium nobile and evaluation of their antitumor activity - Gu Min; Shu-chang Gao; Xiao-li Ma; Xiao-peng Huang; Yi-wei Chen; Xu-liu Shi; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Hydrodynamic control on the interannual variability of algal bloom in the Pearl River Estuary from 2021 to 2024: evidences from buoy data and hydrodynamic modeling - Heng Zhang; Zijian Zhang; Xinfeng Zhao; Hong Yang; Tong Li; Zhen Shi; Kaikai Hu; Guang Zhang (Marine Pollution Bulletin, 2026)

Molecular insights into the coupled transformation of dissolved organic matter and arsenic in lake sediment driven by algal input under redox fluctuations - Yuanhang Li; Zhaoying Shen; Shaokang Zhang; Hang Fu; Yuheng Sun; Shoujuan Tang; Hong Huang; Lei Shi (Water Research, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Biological ponds enhanced with autotrophic moving bed biofilm reactor for upgrading rural wastewater treatment plant effluent: performance and microbial mechanisms - Wenqing Li; Zhicheng Shi; Junming Hong; Mulan Zhu (Bioresource Technology, 2026)

Optimizing the keratin degradation activity of keratinase via in silico and molecular engineering approaches - Yu-Xin Chen; Xiang-Lan Xi; Chang Su; Meng-Ting Tan; Heng Li; Jin-Song Gong; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2026)

Endoplasmic Reticulum Stress in the Keratinocytes Contributes to Chronic Itch by Activation of Lipocalin 2/MC4R/TRPV1 Pathway - Wei Ge; Yu Feng; Li Zhang; Qian-Liang Wang; Cheng-Wei Zhang; Zhi-Hong Wang; Guo-Kun Zhou; Shi-Yu Sun; Xiu-Hua Miao; Tong Liu; Bin Wu; Jun Yan (Neuroscience Bulletin, 2026)

Hypothalamic Oxytocin Neuronal Activation Induces Bipolar-Like Mood Changes in Mice in a Sex- and Dosage-Dependent Manner - Hong Tan; Shizhen Jin; Wenjin Lv; Lingyu Guo; Peiran Jiang; Yongjian Li; Mengjia Shi; Danting Wang; Yongcheng Wang; Aimin Bao (Neuroscience Bulletin, 2026)

Dynamic Obstacle Avoidance Algorithm for Unmanned Vessels Based on FDWA and IBA*—IGWO Fusion - Min Wang; Jinwen Gao; Chenhao Li; Mei Hong; Huaihai Guo; Hanfei Xie; Minghang Shi (Journal of Marine Science and Engineering, 2026)
This paper proposes a dynamic obstacle-avoidance algorithm for unmanned surface vehicles (USVs) that combines a Fuzzy-enhanced Dynamic Window Approach (FDWA) with an Improved Bidirectional A*–Improved Grey Wolf Optimizer (IBA*–IGWO) framework. Firstly, the traditional dynamic window method (DWA) is improved by adopting an initial heading angle optimization strategy to reduce the heading deviation of unmanned vessels during cruising. Secondly, a fuzzy controller is introduced, which can adaptively adjust the weight coefficients in the cost function of the DWA algorithm based on the current position of the unmanned vessel, surrounding environmental information, etc., to improve obstacle avoidance ability and adaptability in different environments. Finally, using the global static cruise route provided by the IBA*–IGWO algorithm, key nodes are selected as local endpoints for the FDWA algorithm to ensure that the unmanned vessel can perform cruise tasks according to the optimal plan during navigation and make dynamic adjustments in case of emergencies. The simulation results demonstrate the feasibility of the proposed method in handling unknown and dynamic obstacles under the current grid-based experimental settings, while enabling the USV to return to the pre-planned global route after local obstacle avoidance. These results provide a basis for further development toward more robust and rule-aware autonomous navigation in realistic maritime environments.

Planar chiral [2.2]paracyclophane biarylphosphine (PCP-BPhos) libraries: rational design, catalytic synthesis, and applications - Mingjie Li; Jingyi Bai; Hong-Yu Qu; Wen-Hua Zheng; Minyan Wang; Zhuangzhi Shi (Science Bulletin, 2026)

Multi-pathway nutrient replenishment mechanisms sustaining the transboundary green tides region in the Southern Yellow sea - Xin Li; Hong Gao; Chuansong Zhang; Xiaoyong Shi (Marine Environmental Research, 2026)

Biogas slurry substitution for chemical fertilizer under fertigation enhances soil fertility and maize yield sustainability: A meta-analysis - Yue Jiang; Bin Shi; Run Xue; Hong Li; Bingyu Li; Luya Wang; Nuo Li (Journal of Environmental Management, 2026)

Flow-driven piezo-photocatalytic synergy in Bi24O31Br10/β-PVDF membranes: Interfacial electron transfer-mediated enhancement of tetracycline degradation - Yixuan Hong; Yanhua Cui; Zengkai Wang; Jian Ye; Chunyan Li; Weilong Shi; Chao Yan (Journal of Environmental Chemical Engineering, 2026)

Fouling behavior and cleaning strategy during treatment of practical refractory organic wastewater using anaerobic ceramic membrane bioreactor - Ruihui Chen; Lixiu Shi; Xinsen Li; Hongming Yang; Sheng Xiang; Mohd Fadhil MD Din; Eli Hendrik Sanjaya; Lu Peng; Zhengwang Wu; Chengcheng Lin; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Corrigendum to “All-trans-retinoid acid (ATRA) suppresses chondrogenesis of rat primary hind limb bud mesenchymal cells by downregulating p63 and cartilage-specific molecules” [Environ. Toxicol. Pharmacol. 38(2) (2014) 460–468] - Yun-guo Wang; Peng Xie; Yun-gong Wang; Xue-dong Li; Tao-gen Zhang; Zhao-yong Liu; Quan Hong; Shi-xin Du (Environmental Toxicology and Pharmacology, 2026)

Engineering Cu-enhanced Mn-based Prussian blue analogue with boosted dual-redox activity for efficient and fast capacitive deionization - Zhiqiang Wu; He Ren; Hao Zhou; Jianeng Ji; Haiyun Ding; Chunyan Li; Minjie Shi; Ying Hong; Jun Yang (Desalination, 2026)

High-density microfluidic Chip (HD-μChip) for multiplex detection in miniaturized immunoassays - Yiran He; Min Wang; Zhaoxu Luo; Xiaodong Ma; Min Jiang; Yanhua Chen; Jingyi Qin; Yayun Gu; Xin Li; Ying Shi; Hong Wang; Ye Shen; et al. (Chemical Engineering Journal, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Migration behaviour of heavy metals and vitrification characteristics in melting of municipal solid waste incineration fly ash - Quanming Li; Yajie Gao; Chao Geng; Xianfeng Shi; Hong Zhang; Cheng Chen; Yukai Wang; Jiaqi Chang; Yajie Wang; Ziyi Ding (ENGINEERING Environment, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Epidemiological and evolutionary analysis of porcine circovirus type 2 within pig populations in central China during 2021-2024 - Jia-Xin Li; Hao Li; Feng-Shuo Wang; Yun-Yun Li; Guang-Cai Wang; Hong-Lei Zhang; Xue-Yan Ding; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Numerical investigation on hydrodynamic characteristics of floating breakwater with wings using a coupled SPH method - Xin Chen; Ming-yuan Li; Peng-cheng Shi; Hong-lei Lyu; Jie Cui (Marine Georesources & Geotechnology, 2026)

Genipin ameliorates cholestatic liver injury in Mdr2−/− mice: the role of gut microbiota modulation by its dialdehyde intermediates - Junli Jin; Lulu Zhu; Chengjiang He; Haiping Deng; Ni Li; Hong Pan; Fuguo Shi (Toxicology and Applied Pharmacology, 2026)

Molecular trade-offs in methane adsorption-diffusion behavior induced by matrix acidification of bituminous coal - Jiexin Lu; He Li; Shiliang Shi; Quanle Zou; Yi Lu; Yidu Hong; Qing Ye (Fuel, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Efficient capillary electrophoretic analysis of anthraquinones and phenolic acids in functional foods using a novel deep eutectic solvent–in–deep eutectic solvent microemulsion - Kai-Yang Fan; Shi-Qi Niu; Tian Zhang; Jun Cao; Li-Hong Ye (Food Chemistry, 2026)

Combining protein fibrosis with dynamic non-covalent crosslink to improve the mechanical properties of high internal phase emulsion and its application in hollow model printing - Mengjia Guo; Xiaoxiao Hong; Jiawang Shi; Zhiqian Lin; Huajun Jian; Yu Cheng; Minhao Xie; Weiwei Li (Food Hydrocolloids, 2026)

Nematode predation mitigates microbial competition to sustain the plant growth-promoting effect of Streptomyces - Ke-Fan Huo; Jing-Nan Zhang; Elly Morriën; Ping Liu; Neil B. McLaughlin; Kai-Hong Bai; Zhen-Long Wang; Shi-Xiu Zhang; Lu-Jun Li (European Journal of Soil Biology, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

YOLOv11-SDiseasedFishNet:Recognition of body surface symptoms of diseased fish based on automatic combination augmentation and multi-scale feature fusion - Zijian Wu; Jian Li; Rui Shi; Hongjing Dai; Zhibo Cui; Yue Wang; Hong Yu (Aquaculture, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Seasonal dynamics of plankton networks and copepod selection strategies in the laver cultivation area of Haizhou Bay, China: based on sparse correlations for compositional data analysis - Sen Li; Hong Huang; Jinchen Yu; Tao Sun; Shuo Chen; Jin Zhou; Yunrong Shi; Peng Zhang; Jieqing Yang (Marine Environmental Research, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Structure-optimized hollow carbon spheres from lignite for advanced lithium–sulfur batteries - Yao Huang; Long-Jun Zhang; Wei Wang; Zhan-Ku Li; Xu Liu; Hong-Lei Yan; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; et al. (Fuel, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Unlocking the potential of konjac (Amorphophallus konjac K. Koch) Starch: A review on extraction, structure, properties, and potential applications - Gangpeng Shi; Yan Hong; Li Cheng; Lingjin Li; Zhengbiao Gu (Food Hydrocolloids, 2026)

Interpenetrated hierarchical polyzwitterionic hydrogels promote decellularized small-diameter vascular grafts regeneration - Qi-Ying Wu; Chun-Yang Chen; Jin-Chang Li; Ze-Guo Chen; Si-Cheng Chen; Chao Xie; Si-Xi Liu; Zi-Han Liu; Zhong-Shi Wu; Yu-Hong Liu (Chemical Engineering Journal, 2026)

Intelligent Control System for Particulate Matter: Real-Time Monitoring and Pollution Source Identification for Enhanced Efficiency - Peng Shi-Tao; Li Long-Chuang; Ye Yin; Hong Ning-ning; Zhang Jing; Chen Zi Jing; Du Hong-Bo (Water, Air, & Soil Pollution, 2026)

Hierarchical Framework for Reservoir Co-management: A Cross-scale Reservoir Dispatch Paradigm Balancing Energy and Morphogenic Flow Needs - Hong Zeng; Tian-Yao Zhang; Yi-Ming Liao; Guang-Wen Ma; Ji-Dong Li; Wei-Bin Huang; Yan-Mei Zhu; Shi-Jun Chen (Water Resources Management, 2026)

The DTH8-SD1 pair regulates panicle architecture in rice - Su Su; Jun Hong; Ling Li; Xiaofei Chen; Cai Chen; Jianxin Shi (Theoretical and Applied Genetics, 2026)

Immunotherapy checkpoint inhibitor-combination therapy versus chemotherapy alone among Chinese population in cholangiocarcinoma treatment: a systematic review and meta-analysis - Li Shi; Wei Du; Juan Miao; Xi-Yuan Peng; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Si-Qi Gao; Hong-Lin Chen (European Journal of Clinical Pharmacology, 2026)

Development of a high-throughput LLE-UPLC-QqQ-MS/MS method and comprehensive profiling of urinary steroid hormones in Chinese elderly adults - Xiao Ma; Huimin Ren; Li Zhao; Xiaojie Guo; Jiran Zhang; Juan Liu; Xiaona Wang; Mengyao Wang; Yifu Lu; Shilu Tong; Hongyang Cui; Hong Chang; et al. (Analytica Chimica Acta, 2026)

Adaptive frequency-domain synthesis and performance evaluation for wideband multi-antenna signals - Xuejian Li; Hong Ma; Yiwen Jiao; Tao Wu; Xueshu Shi; Hongbin Ma; Yuxin Wang (Advances in Space Research, 2026)

Fused Geophysical–Contrastive Learning Model for CYGNSS-Based Sea Surface Wind Speed Retrieval in Typhoon Regions - Yun Zhang; Zelong Teng; Shuhu Yang; Qingjing Shi; Jiaying Li; Fei Guo; Bo Peng; Yanling Han; Zhonghua Hong (Journal of Marine Science and Engineering, 2026)
Global Navigation Satellite System Reflectometry (GNSS-R) provides a vital means for sea surface wind speed retrieval, yet its application under extreme typhoon conditions remains challenging. Conventional geophysical models (GMFs) saturate in high wind speed regimes (>20 m/s), and deep learning models (e.g., CNNs) are constrained by data sparsity and feature complexity in typhoon environments. To address these issues, we propose a Comparative Learning method of CNN-Transformer with GMF fusion (CLCTG). The CNN branch extracts local coupling patterns, the Transformer branch models global dependencies, and Kullback–Leibler (KL) divergence loss is used for contrastive learning to heighten sensitivity to complex typhoon wind fields. The GMF branch serves as a physical reference/anchor in the low- to moderate-wind-speed range ( 30 m/s range. To further improve high-wind-speed predictions, we introduce environmental features based on their correlation with wind speed; ablation experiments demonstrate that the combined use of environmental parameters and CYGNSS features maximizes overall accuracy. Testing on five typhoons from the Eastern and Western Hemispheres confirms CLCTG’s generalization across diverse geographic contexts, and branch-wise comparisons validate its structural advantages. Buoy observations show peripheral errors below 3 m/s and physically consistent wind speed gradients in the core region. These results indicate that multi-source fusion of CYGNSS and environmental data, coupled with contrastive learning and physical reference, offers a reliable and efficient solution for typhoon wind speed retrieval.

SfFPPS genes mediate reproduction and insecticide-induced resurgence in Sogatella furcifera - Cao Zhou; Zi-Han Xu; Jiang-Ling Chen; Xin Li; Shi-Yan Zhang; Hong Yang; Dao-Chao Jin (Pesticide Biochemistry and Physiology, 2026)

Ketamine's brain spatial distribution and metabolic effects in a mouse model of anxiety: Insight into in situ mass spectrometry imaging and metabolomics methods - Hong Yang; Weihao Fan; Xinyu Yang; Ying Wei; Li Xiao; Hongkun Yang; Linzhi Jiang; Jian Li; Kaiting Shi; Shuang Zhao; Lin Yang; Yi Ye; et al. (NeuroToxicology, 2026)

Mechanistic insights into the enhancement of azithromycin biodegradation by extracellular polymeric substances: Roles of metabolic activity, electron transfer, and reactive oxygen species - Jian-Gang Zhou; Ming-Hong Wei; Shi-Jie Wang; Li Chen; Muhammad Wajid Ullah; Hong-Tao Liu; Su Sun (Journal of Hazardous Materials, 2026)

Cold plasma-functionalized chitosan nanocomposite films with BCp12: Antimicrobial and barrier properties in food packaging - Tingting Yang; Yi Li; Xiaoyan Yu; Zuyan Duan; Mingmin Yang; Wenjie Li; Jiarui Yang; Hong Li; Yanan Shi (Innovative Food Science & Emerging Technologies, 2026)

Effects of different drying methods on the physicochemical properties, antioxidant activity and gut microbiota fermentation behaviours of polysaccharides from Schizophyllum commune - Lihong Fan; Chaomin Yin; Haina Ma; Jing Wen; Maofen Yi; Zhenshun Li; Xiuzhi Fan; Defang Shi; Zhicheng Huang; Jianhui Qiu; Hong Gao (Food Research International, 2026)

Comparison of physicochemical properties of water- and alkaline-extracted polysaccharides from Schizophyllum commune and their anti-obesogenic effects in vivo - Chen Li; Chaomin Yin; Jiangtao Li; Jing Wen; Lihong Fan; Haina Ma; Xiuzhi Fan; Defang Shi; Wei Yu; Jianhui Qiu; Hong Gao (Food Chemistry, 2026)

Isomeric halide engineering of self-assembled hole-selective layers for efficient indoor perovskite photovoltaics - Zhong-En Shi; Yi-Ting Hong; Cheng-Chieh Lu; Po-Cheng Shih; Shih-I Lu; Hsiao-Chi Hsieh; Sie-Rong Li; Yu-Che Lin; Zheng-Xuan Cai; Yan-Duo Lin; Chih-Ping Chen (Chemical Engineering Journal, 2026)

Schizophyllum commune polysaccharide ameliorates diet-induced obesity by regulating the Faecalibaculum rodentium/indole-3-lactic acid/microRNA axis - Chaomin Yin; Chen Li; Xiuzhi Fan; Defang Shi; Jiangtao Li; Jianhui Qiu; Fen Yao; Wei Yu; Hong Gao (Carbohydrate Polymers, 2026)

Thermotropic glass vs. vertical shading: Evaluation of building energy, daylighting and thermal comfort performance - Xuan Yang; Kexin Li; Yilin You; Shaosen Wang; Feng Shi; Yiming Xu; Yue Yang; Xiaoqiang Hong (Building and Environment, 2026)

7,8-Dihydroxyflavone ameliorates bone loss by regulating TRKB/AKT/FOXO3a pathway in a mouse model of alzheimer’s disease - Dong Liu; Xiaoxiong Li; Peng Shi; Wenjuan Hong; Jie Huang; Mingliang Hou; Linqiu Ma; Qirong Liao; Hongyan Yang; Xiaoyan Fu; Huadong Zhou; Jing Lu; et al. (Psychopharmacology, 2025)

Occurrence and remediation of chlorinated paraffins in global environmental matrices: Levels, trends, and future prospects - Yongyi Ma; Qianqian Li; Guijin Su; Huangnan Duan; Tieyu Wang; Jong Seong Khim; Seongjin Hong; Bohua Sun; Jing Meng; Bin Shi (Critical Reviews in Environmental Science and Technology, 2025)

Biofilm formation by Gallibacterium anatis depends on TolC-mediated initial attachment of cells - Zi-cong Shi; Jin-li Zhai; Jing-yue Yu; Zeng Wang; Hong-ying Liu; Xia Yang; Xin-wei Wang (The Veterinary Journal, 2025)

A rapid extraction method via cascaded successive variational mode decomposition: Case studies on ship-radiated noise and underwater LiDAR - Haonan Shi; Deyue Hong; Haihan Zhao; Zhiwen Qian; Jingsheng Zhai; Xiaobo Li (Ocean Engineering, 2025)

RAD-seq reveals Cenozoic shifts in the palaeogeographic distribution of Trigonobalanus verticillata across the Indochina Peninsula and Malay Archipelago - Ling Hu; Pei-Han Huang; Yi-Gang Song; Shook Ling Low; Guo-Xiong Hu; Shi-Shun Zhou; Lang Li; Yun-Hong Tan; Hong-Hu Meng; Yu-Peng Cun; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Facile synthesis of high-performance crystalline zirconium phosphate adsorbents and its ammonium ion intercalation mechanism for next-generation hemodialysis - Jingwen Feng; Jianjun Cheng; Jingwen Li; Susu Jia; Feiping Cao; Jiajin Feng; Dapeng Zhou; Jiahua Shi; Choon-Hong Tan; Hongjun Liu (Journal of Environmental Chemical Engineering, 2025)

Revealing flavor improvement in whey-based cold brew coffee: characteristic flavor compounds and formation mechanisms - Dan Zhao; Yi Li; Zuyan Duan; Jiarui Yang; Wenjie Li; Xiaoyan Yu; Aixiang Huang; Hong Li; Yanan Shi (Food Chemistry, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Uncovering the gut microbiome and antibiotic resistome of mammals on the Tibetan Plateau - Chen Tian; Zecheng Tang; Xiaoyu Zhang; Xueqin Yao; Yitian Li; Daohua Zhuang; Yu Luo; Teng Li; Liyan Bai; Fangfang Zhao; Lei Zhu; Guolin Shi; et al. (Science China Life Sciences, 2025)

Simultaneous estimation of Bouguer gravity anomaly and near-surface density using Bayesian approach: A Yunnan case study - Feng-gui Niu; Shi Chen; Yong-bo Li; Hong-lei Li; Yuan-yuan Niu; Yu-hang Pan (Applied Geophysics, 2025)

Optimizing Ventilation Systems for Dual Objectives: Enhancing Thermal Comfort and Controlling Droplet Dispersion - Caiyue Song; Benben Kong; Mengmeng Cheng; Yu Li; Hong Shi (Aerosol Science and Engineering, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Exploring the main and interactive effects of urban morphology on land surface temperature across different functional zones: A local geoshapley analysis based on XAI - Jin-Tao Yang; Xing-Wen Zhou; Xu Chen; Xiong Yao; Mao Li; Ming-Hui Yin; Fei Dong; Shi-Hong Yan; Jia-Liang Zhao (Sustainable Cities and Society, 2025)

Seismic performance of utility tunnel and internal pipeline system based on fuzzy probability analysis - Jinqiang Li; Hong Hao; Zilan Zhong; Yuebo Shi; Xiuli Du (Soil Dynamics and Earthquake Engineering, 2025)

Current status and future emission reduction pathways of NOx in China - Qian Wu; Song Hong; Lanzhou Chen; Peiyue Tu; Dan Wang; Yushan Li; Chaoqing Huang; Shuai Shi; Bin Chen; Chao He (Science of The Total Environment, 2025)

Combining biochar and lime amendments for remediation of Cd-contaminated paddy soil around e-waste dismantling site: a study from laboratory to field - Hailong Lu; Kewei Li; Yangxiaoxiao Shi; Jackson Nkoh Nkoh; Zhineng Hong; Renkou Xu; Jun Jiang (Journal of Environmental Management, 2025)

The bioaccessible and labile contents of As(Ⅲ) and As(V) in four typical soils in China assessed by different methods - Yangxiaoxiao Shi; Linyu Guo; Kewei Li; Jing Yan; Jun Jiang; Zhineng Hong; Renkou Xu (Journal of Environmental Sciences, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

EPA-enriched phospholipids and DHA-enriched phospholipids prevent dexamethasone-induced skeletal muscle atrophy via regulating protein turnover and mitochondrial quality - Ying-Chao Li; Shi-Xiang Wu; Qing-Yan Zou; Yan Zheng; Zi-Jian Wu; Xin-Yue Zhao; Xiang Gao; Yu-Hong Yang; Lei Du (Food Research International, 2025)

Smartphone-assisted Ce-POM/CuBTC peroxidase-like colorimetric detection of H2O2 and ascorbic acid in food samples - Yiyi Zhang; Haibo Zhang; Chengyuan Ma; Yihang Yang; Xuan Mo; Yuan Shi; Zhijia Yin; Hong Li; Lin Sun (Food Chemistry, 2025)

Comprehensive analysis of microbial communities, metabolites, and biogenic amines in bagged fermented chili paste at varying salt levels - Wei-Qin Deng; Zhen-Ming Lu; Ze-Liang Wang; Si-Qiang Jiang; Xiong-Bo Li; Zhi-Yi Fan; Xiao-Juan Zhang; Li-Juan Chai; Qi-Sheng Zhang; Jin-Song Shi; Gong Chen; Zheng-Hong Xu (Food Bioscience, 2025)

Finite strain solution for circular tunnels in strain-softening rock during its lifecycle based on unified strength theory - Xu-Guang Yu; Hong Zheng; Tao Wan; Shi-Cheng Li; Yu Liang (Computers and Geotechnics, 2025)

Constructing high-performance solid-state electrolyte interface and anchoring residual solvents for long-cycle lithium-metal batteries - Shi Zhou; Min Liu; Bangfu Yin; Xiaoyi Chen; Lingguang Yi; Linqing Wang; Jiali Liu; Huahui Zhao; Jun Li; Li Yang; Hong Liu; Xianyou Wang (Chemical Engineering Journal, 2025)

Nitrogen-doped hydrothermal carbon as a catalyst for selective alkoxyphenol production from pine pyrolysis - Dong-hong Nan; Cheng-bo Zhang; Qi Niu; Shi-yu Feng; Bin Hu; Ji Liu; Kai Li; Qiang Lu (Biomass and Bioenergy, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

YOLOv11-OPNet: dual-modality framework for fishing vessel detection in complex long-range maritime scenarios - Jian Li; Hong Yu; Rui Shi; Zhibo Cui; Hongjing Dai; Zijian Wu; Yue Wang (Aquaculture International, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

The efficient green bio-manufacturing of Vitamin K 2 : design, production and applications - Li-Yang Xu; Yi-bin Qiu; Xiao-mei Zhang; Chang Su; Jing-Song Shi; Zheng-Hong Xu; Hui Li (Critical Reviews in Food Science and Nutrition, 2025)

Regulating community redox metabolism for systematic mitigation of antibiotic chemical and biological risks - Ke Shi; Wen-Bin Xu; Han-Lin Cui; Li-Ying Zhang; Jing-Yi He; Wei-Wei Ben; Cheng-Yuan Su; Shu-Hong Gao; Ai-Jie Wang; Bin Liang (Water Research, 2025)

Key challenges and strategies for promoting eye health in China - Xueli Yang; Yiqing Wang; Wenjuan Zhuang; Wenfang Zhang; Zhaohui Li; Yanming Huang; Hong Zhang; Hong Yan; Haokun Zhang; Yi Lei; Weiyun Shi; Youxin Chen; et al. (Science Bulletin, 2025)

Geochemistry of organic-rich black shales from the Ediacaran Salt Range Formation (Sub-Himalayas, Pakistan): Implications for paleoecology and paleoenvironment - Sajjad Ali; Meijun Li; Hongfei Lai; Rizwan Sarwar Awan; Shengbao Shi; Hong Xiao; Imtiaz Ali Hakro; Ashar Khan; Khawaja Hasnain Iltaf (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Research on the oxidative decomposition of 1,2-bis(2,4,6-tribromophenoxy)ethane induced by •OH, SO4-•, and O3: Transformation mechanism, kinetics, and toxicity assessment - Yang Long; Liming Tai; Shi Yan; Jinbao Huang; Hong Wang; Xinsheng Li; Hao Cheng; Li Jin (Journal of Environmental Chemical Engineering, 2025)

Tailoring molecular structure of coal tar for monolithic phenolic aerogels to reduce enthalpy for solar desalination - Yu Han; Hong-Lei Yan; Zhan-Ku Li; Wei-Dong Zhang; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui; Lun-Jing Yan (Journal of Environmental Chemical Engineering, 2025)

Investigation on the decomposition mechanism of tetrabromobisphenol A: Reaction with reactive free radicals and ozone molecules - Yang Long; Jinbao Huang; Liming Tai; Shi Yan; Hong Wang; Shengju Jin; Li Jin (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Innovative assessment of CO2 storage potential in China's shale oil fracturing: A storage index-well layout approach - Wenrui Shi; Meiyu Guo; Jianfeng Li; Zisang Huang; Pu Hong; Pengfei Wang; Yijiang Feng; Hongyan Zhao; Hankui K. Zhang (Gas Science and Engineering, 2025)

Curcumin-mediated photodynamic treatment efficiently inhibits Bacillus cereus and extends the shelf-life of flat rice noodles - Hao-Ran Ji; Jia-Jun Yan; Zi-Hui Chen; Wen-Li Shi; Li-Wen Chen; Juan Wang; Yu Ding; Ai-Min Jiang; Bing Du; Cai-Hu Liao; Hong-Tao Lei; Quan Zhou; et al. (Food Research International, 2025)

Mitochondrial DNA leakage and micronucleus formation activate the cGAS–STING pathway in aristolochic acid I-induced nephritis - Yu yang Lei; Yu shi Hu; Yi yi Cao; Jing Xi; Yu ning Ma; Xiao hong Zhang; Qin wen Gao; Ji an Fu; Xin yu Zhang; Li Su; Yang Luan (Food and Chemical Toxicology, 2025)

Multidimensional mechanism investigation on improving the pretreatment performance and enzymatic saccharification of bamboo with choline chloride-based deep eutectic solvents - Yu Sheng; Yao-yao Jin; Hai-yan Yang; Zheng-jun Shi; Chun Shi; Da-wei Wang; Tao-hong Li; Jing Yang (Chemical Engineering Journal, 2025)

Synergistic ion adsorption and electron transfer in porphyrin-based conjugated microporous polymers enabling stable Zn anodes - Wei-Hai Yi; Wen-Jie Shi; Min-Peng Li; Hong-Yan Li; Cai-Xia Zheng; Xin-Ying Ren; Qi Zhou; Mao-Cheng Liu (Chemical Engineering Journal, 2025)

Thermal p-n junctions: a macroscopic thermal diode based on heterogeneous materials - Yue Zhang; Baotong Li; Pengfei Sun; Yu Hou; Jun Hong; Meng Shi; Liang Zeng; Qingfang Liu (Chemical Engineering Journal, 2025)

Mechanically responsive self-reinforced polyurethane elastomers with cyclodextrin metal-organic framework structure for high impact resistance - Jing Lv; Xiaodong Li; Ni Zhai; Tianhao Wu; Chengwang Shi; Hong Yu; Wei Zhang; Tenglong Ma; Hao Jiang; Meishuai Zou (Chemical Engineering Journal, 2025)

An ingenious structural design of NiCu-MOF bar-like nanosheet array: harnessing synergistic effects to attain exceptional ammonia oxidation performance - Guang-Lan Li; Yu-Hui Shi; Ri-Yang Huang; Tian-Ge Ma; Qian Zhuo; Ling Xu; Fei Jiang; Yu-Kun Zhai; Yong-Hou Xiao; Hong-Jiang Li; Yang Yan; Yun Zhao (Chemical Engineering Journal, 2025)

High-entropy sulfide and nanozyme hybrid system with synergistic interface-engineering: Ultra-sensitive photoelectrochemical detection of chloramphenicol - Yi-Hong Chen; Ai-Jun Wang; Ya-Cheng Shi; Li-Ping Mei; Pei Song; Tiejun Zhao; Jiu- Ju Feng (Chemical Engineering Journal, 2025)

Effect of ibuprofen on the behavior, histopathology, antioxidant system, DNA damage, and apoptosis of Asian freshwater clams (Corbicula fluminea) - Yun-xia Hou; Xiang-sheng Hong; Shi-yin Tang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jian-hui Qin; Jin-miao Zha (Aquatic Toxicology, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Molecular docking-based design of novel tricyclic tetrahydropyridothienopyrimidinone derivatives as AChE/MAO-B dual inhibitors - Juan Zhang; Yue Li; Jia-Dong Shao; Guo Wei; Nai-Yu Zhang; Kong-Kai Zhu; Kai-Ming Wang; Cheng-Shi Jiang; Jia-Hong Wang (Molecular Diversity, 2025)

New clicked hydrophobic 2,9-bis-triazolyl-1,10-phenanthroline ligands used as extractants for actinide/lanthanide separation: Towards deep purification - Xuan Fu; Yang Liu; Heng-Yi Zhou; Cong-Zhi Wang; Tao-Yuan Xiu; Zhe Xiao; Hong-Bin Tang; Zhi-Wei Huang; Zhi-Heng Zhou; Li-Yong Yuan; Ze-Yi Yan; Wei-Qun Shi (Journal of Hazardous Materials, 2025)

Estrogenic and transgenerational effects of perfluorocarboxylic acids through estrogen-related receptor γ pathway - Sha Shi; Wei Zheng; Xi-Long Zhang; Minjie Li; Cheng Ye; Lu Chen; Wen-Jun Hong; Chuan-Hai Li; Huiyu Chi; Fangfang Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Evolution of characteristic components from retired wind turbine blades in multiple thermal atmospheres: thermal decomposition characterization and kinetic behavior - Haoyun Liu; Pei Li; Yonggang Zhou; Jinsong Zhou; Jianzhong Shi; Bing Hong (Journal of Environmental Management, 2025)

Effect of anticyclonic eddies on the production and emission of marine dimethylsulfide in the northern South China Sea - Jin-Wei Wu; Feng Xu; Shi-Bo Yan; Gao-Bin Xu; Yu-Cheng Jiang; Xiao-Ran Li; Xing Zhai; Li-Min Zhou; Hong-Hai Zhang; Zhao-Hui Chen (Global and Planetary Change, 2025)

Investigation on quality discrepancies of Soy Sauce Aroma Baijiu: Flavor chemical characteristics in single-source and cross-source samples - Chen Li; Xiao-Juan Zhang; Shi-Yi Wang; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Bo Yang; Cai-Hong Shen; Zheng-Hong Xu (Food Control, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Multiple endogenous aldehydes amplify acetaminophen-induced liver injury - Hong Pan; Qi Luo; Qiuyi Jing; Lin Chen; Ni Li; Chao Fang; Fuguo Shi (Chemico-Biological Interactions, 2025)

Isoliquiritigenin alleviates radiation-induced intestinal injury in lung cancer by inhibiting TNF-α/caspase3 signaling pathway - Ya-ping Chen; Liang-liang Shi; Yang-yang Li; Yi-Ming Zhang; Shang-zu Zhang; Hong-dou Hou; Yan Chen; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

DNA Barcode Reference Library and Undetected Diversity of Fish Species in the Yuanjiang River, China - Xian Shi; Chunni Kou; Chengdong He; Hong Deng; Hongfu Yang; Xinhui Li; Mingdian Liu; Yaqiu Liu; Jie Li; Weitao Chen (Fishes, 2025)
The Yuanjiang River, situated in the upper reaches of the Red River, is a crucial component of a biodiversity hotspot in the mountains of southwestern China, supporting a high diversity of fish species. Nevertheless, systematic research on fish diversity in the Yuanjiang River is scarce, scattered, and outdated. In our study, we produced 764 DNA barcodes belonging to 64 fish morphospecies to evaluate fish diversity in the Yuanjiang River. Barcoding gap analysis and DNA-based delimitation approaches achieved a high identification success rate (>93%), indicating that DNA barcoding is a practical approach for delimiting fish in the Yuanjiang River. However, four species were characterized by high levels of intraspecific divergence, generating multiple clades and/or molecular operational taxonomic units (MOTUs), suggesting that these species might comprise undetected species. Meanwhile, two closely related species within the genus Schistura, i.e., S. callichroma and S. caudofurca, cannot be delimited by the DNA barcoding technique, which is indicative of recent speciation. In summary, this study established a reliable DNA barcode reference library for fish species in the Yuanjiang River and revealed previously unknown fish diversity.

Acute alkalinity stress triggers kidney histopathology, oxidative-immune dysregulation, and MAPK/TGF-β signaling pathways activation in Scatophagus argus - Lingwei Kong; Adili Abudu; Lei Yang; Minghui Ye; Yulei Zhang; Yucong Hong; Huapu Chen; Guangli Li; Gang Shi; Changxu Tian (Aquaculture, 2025)

Efficient and selective gold recovery from practical e-waste and electroplating wastewater using protein crystals - Xiao-Qian Jin; Jia-Lei Li; Chen-Yuan Li; Liang-Liang Chen; Xue-Ting Wang; Wen-Pu Shi; Jun-Bin Xiong; Rui Zhang; Wei-Hong Guo; Da-Chuan Yin (Resources, Conservation and Recycling, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Isolation of dihydroagarofuran sesquiterpene from the fruits of Tripterygium hypoglaucum and evaluation of their anti-inflammatory activity - Shi-Li Wu; Xing Yang; Wen-Xiu Ning; Gang-Yun Wu; Xin-Yu Dai; Yu Zhang; Duo-Zhi Chen; Xiao Ding; Hong-Ping He; Wei Zhou; Xiao-Jiang Hao (Phytochemistry, 2025)

Unraveling the toxic trio: Combined effects of thifluzamide, enrofloxacin, and microplastics on Mytilus coruscus - Ze-Ming Zhang; Hao Liu; Hong-Lin Zuo; Yi-Nan Wang; Ai-Li Sun; Jiong Chen; Xi-Zhi Shi (Journal of Hazardous Materials, 2025)

Cultured biomass enhances the flavor and nutrition characteristics of biomass/plant hybrid cultured meatballs - Zi-Qing Meng; Chang-Bo Tang; Tian-yi Tao; Wenjuan Song; Chun-Bao Li; Jun Qi; Shi-jie Ding; Guang-Hong Zhou (Food Research International, 2025)

Impact of environmental salinity on the MAPK-NFAT5 pathway in Trachemys scripta elegans and its role in osmoregulaton - Xin Niu; Yingnan Lu; Yue Yuan; Jiao Li; Yunjuan Xiao; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Two-dimensional nitrogen-doped carbon nanosheets-coated porous SiO composites sponges for durable anode materials of high-energy lithium-ion batteries - Zaohong Zhang; Weichen Chen; Jie Tian; Kai Zhang; Carlos Ponce de León Albarrán; Chuan Wu; Zhicong Shi; Zibiao Li; Jia Hong Pan (Chemical Engineering Journal, 2025)

SGLT2i continuously prevents cardiac hypertrophy by reducing ferroptosis via AMPK up-regulation - Bing-bing Zhao; Jiao Wang; Lu-lu Zhang; Chao Li; Hong-hong Xue; Li Zhao; Qing-hua Han; Hong-tao Shi (Molecular and Cellular Biochemistry, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Decoding plant‐induced transcriptomic variability and consistency in two related polyphagous mites differing in host ranges - Lei Chen; Li‐Xue Guo; Xin‐Yue Yu; Shi‐Mei Huo; Ary A. Hoffmann; Jia‐Yi Zhou; Jing‐Tao Sun; Xiao‐Yue Hong (Molecular Ecology, 2025)
The diet breadth of generalist herbivores when compared to specialists tends to be associated with greater transcriptional plasticity. Here, we consider whether it may also contribute to variation in host range among two generalists with different levels of polyphagy. We examined two related polyphagous spider mites with different host ranges, Tetranychus urticae (1200 plants) and Tetranychus truncatus (90 plants). Data from multiple populations of both species domesticated on common beans and transferred to new plant hosts (cotton, cucumber, eggplant) were used to investigate transcriptional plasticity relative to population‐based variation in gene expression. Compared to T. truncatus , T. urticae exhibited much higher transcriptional plasticity. Populations of this species also showed much more variable expression regulation in response to a plant host, particularly for genes related to detoxification, transport, and transcriptional factors. In response to the different plant hosts, both polyphagous species showed enriched processes of drug/xenobiotics metabolism, with T. urticae orchestrating a relatively broader array of biological pathways. Through co‐expression network analysis, we identified gene modules associated with host plant response, revealing shared hub genes primarily involved in detoxification metabolism when both mites fed on the same plants. After silencing a shared hub CYP gene related to eggplant exposure, the performance of both species on the original bean host improved, but the fecundity of T. truncatus decreased when feeding on eggplant. The extensive transcriptomic variation shown by T. urticae might serve as a potential compensatory mechanism for a deficiency of hub genes in this species. This research points to nuanced differences in transcriptomic variability between generalist herbivores.

Machine learning strategy secures urban smart drinking water treatment plant through incremental advances - Yu-Qi Wang; Hong-Cheng Wang; Zi-Jie Xiao; Ling-Jun Bu; Jiuling Li; Xiao-Chi Feng; Bin Liang; Wen-Zong Liu; Fei-Yun Sun; Shi-Qing Zhou; Ai-Jie Wang (Water Research, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Diversity-enhanced hyper-heuristics for multi-objective dynamic flexible job shop scheduling - Yuan Shi; Yaoming Yang; Bingdong Li; Hong Qian; Hao Hao; Aimin Zhou (Swarm and Evolutionary Computation, 2025)

Characterization of Sphingomicrobium aquimarinum sp. nov. and Sphingomicrobium maritimum sp. nov. highlights astaxanthin-producing bacteria in the family Sphingomonadaceae - Dao-Feng Zhang; Hong-Chuan Wang; Shi Shi; Tian-Pu Li; Dan-Yuan Guo; Zi-Wen Yang; Yang Yuan; Jianke Huang; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

New micro- and macro- perspective on the removal process of 1H-benzotriazole by UV/PDS: Degradation mechanism, kinetics and multi-factor impact on removal efficiency - Juan Dang; Li-ao Gao; Xue Jia; Xiao-meng Zhang; Hong-jin Wu; Shi-bo Zhang; Qing-zhu Zhang; Shuai Tian (Journal of Environmental Management, 2025)

Reservoir evolution and property prediction of the Paleogene Apollonia Formation, Western Desert, Egypt - Yongjie Hu; Hong Zhang; Zixuan Liu; Edgar Cross; Ying Li; Shuyuan Shi; Hongxia Liu; EmadEldin Ramy; Rongtu Ma; Chunfang Cai (Journal of African Earth Sciences, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Life-cycle monitoring on compressively loaded ductile concrete structures based on CFRP self-sensing - Gui-hua Xie; Shu-yang Wang; Shi-quan Li; Hong-yun Xia; C.M. Wang (Engineering Structures, 2025)

Equal-straw produced biochar continuous incorporation substitutes straw returns for global warming mitigation: An appraisal based on five-year field experiment - Wei Zhang; Jun-Sheng Lu; Shi-Qing Li; Tian-Tian Hu; Xiao-Hong Tian (Chemical Engineering Journal, 2025)

Improving in-situ spectral estimation of wetland soil organic carbon by integrating multiple optimization strategies - Hongyi Li; Jiangtao Yang; Bifeng Hu; Yibo Geng; Qian Zhu; Yongsheng Hong; Yi Lin; Jie Peng; Wenjun Ji; Songchao Chen; Zhou Shi (CATENA, 2025)

Cytogenetic characterization of a novel wheat-rye 2R (2D) substitution line YT9 conferring powdery mildew resistance from the three-leaf stage and physical mapping of PmYT9 - Hanwen Yan; Guohao Han; Tiantian Gu; Zhipeng Shi; Lijun Cao; Jing Wang; Hong Liu; Chenlong Wang; Shiyu Zhuo; Lihui Li; Diaoguo An (Theoretical and Applied Genetics, 2025)

Effects of Microclimates on Species Richness of Epiphytic and Non‐Epiphytic Bryophytes Along a Subtropical Elevational Gradient in China - Zun Dai; Hong‐Wei Zhang; Hong Qian; Min Li; Rui‐Ping Shi; Zhao‐Chen Zhang; Jian Zhang; Hong‐Qing Li; Jian Wang (Journal of Biogeography, 2025)
Aim Biodiversity patterns along elevational gradients have been well documented for vascular plants and terrestrial vertebrates, but we know relatively little about the elevational patterns of bryophytes and their underlying mechanisms, especially the effect of forest microclimate on epiphytic and non‐epiphytic bryophytes. Here we study the influence of microclimates on the richness of epiphytic and non‐epiphytic bryophytes as a whole, and for liverworts and mosses separately, in forests along an elevational gradient ranging from 369 to 1476 m in a subtropical region. Location Mt. Tianmu in eastern China. Methods We sampled bryophytes in each of 16 vegetation plots, each of the size of 20 by 20 m, along the elevational gradient and distinguished between mosses and liverworts and between epiphytic and non‐epiphytic species. We measured climate conditions at local sites. Species richness of bryophytes along the elevational gradient was related to six microclimate variables, using correlation and regression analyses and a variation partitioning approach. Results Overall, species richness of bryophytes showed a slightly decreasing trend with elevation, and epiphytic and non‐epiphytic bryophyte richness showed different elevational patterns. Compared to non‐epiphytic bryophytes, species richness of epiphytic bryophytes was more influenced by air microclimate. We also found that species richness of bryophytes was influenced by both microclimate extreme variables and microclimate seasonality variables. In sum, utilising in situ air and soil microclimatic monitoring data, our study offers a more accurate assessment of the relationship between bryophyte species richness and their habitats. Main Conclusions Our results highlight the importance of considering the ecological differences between mosses and liverworts, and distinguishing between microhabitats of sampled bryophyte assemblages when exploring the patterns and drivers of bryophyte diversity along elevational gradients.

Retraction notice to “Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica)” [Chemosphere 352 (2024) 141430] - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2025)

Evaluation of biological nitrogen removal performance using loofah agricultural waste for treatment of low C/N wastewater - Shi-Ying Sun; Hong-Ji Li; Tao Zhang; Jing Yang; Li-Jun Chen (Journal of Water Process Engineering, 2025)

The nuclear receptor gene SfE75 regulates the molting of Sogatella furcifera - Yi-Ming Wang; Yan-Yu Wang; Ming-Fu Gong; Shi-Yan Zhang; Jiang-Ling Chen; Xin Li; Cao Zhou; Hong Yang (Journal of Asia-Pacific Entomology, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Time series comparative genomics analysis reveals the adaptive evolution of caproic acid-producing bacteria to the long-term liquor brewing environment - Gan-Lin Li; Jun-Lan Mei; Li-Juan Chai; Xiao-Zhong Zhong; Ya-Ning Song; Zhen-Ming Lu; Xiao-Juan Zhang; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2025)

Stresses in the food chain and their impact on antibiotic resistance of foodborne pathogens: A review - Yun Li; Yufan Wu; Jingdong Shao; Juping Shi; Lu Sun; Yi Hong; Xiang Wang (Food Microbiology, 2025)

Nutrients and metal(loid)s in surface sediments of the Chishui River: A DGT-based assessment of the last natural tributary of the upper Yangtze River (China) - Wei Xia; Tian-Xin Zhang; Xue Li; Yanpeng Gao; Richard W. Jordan; Hong Su; Shi-Jun Jiang; Yang-Guang Gu (Environmental Research, 2025)

Oxygen self-supplying nanocomposite with enhanced photodynamic immunomodulatory against planktonic, biofilm and intracellular MRSA infection - Xiangjun Chen; Xiao Liu; Weiwei Li; Xuanxiang Zhai; Xiaoyi Shi; Wenting Li; Wei Hong (Chemical Engineering Journal, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

DNA damage may cause the reproductive differences between the male tetraploid fish and diploid red crucian carp - Haitao Zhong; Hong Chen; Mingli Liu; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2025)

The functional role of arbuscular mycorrhizal fungi in enhancing soil organic carbon stocks and stability in dryland - Meng-Ying Li; Wei Wang; Hai-Hong Yin; Yinglong Chen; Muhammad Ashraf; Hong-Yan Tao; Shi-Sheng Li; Wen-Ying Wang; Chang-Lang Yang; Yun-Li Xiao; Li Zhu; You-Cai Xiong (Soil and Tillage Research, 2025)

Revealing the miscibility chemistry of ionic liquids in water-in-salt electrolytes toward high-voltage and high-temperature aqueous potassium-ion supercapacitors - Jianchao Chen; Guanghao Zhang; Hong Zhang; Shuxian Zhang; Qingyu Li; Chunyan Zhu; Xiaoge Man; Zhiwei Zhang; Yuanchang Shi; Tao Li; Ye Han; Mengqi Zhang; et al. (Science Bulletin, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Antimicrobial polyketides from the endophytic fungus Fusarium asiaticum QA-6 derived from medicinal plant Artemisia argyi - Xiao-Shan Shi; Sui-Qun Yang; Xiao-Ming Li; Yan-He Li; Dun-Jia Wang; Xin Li; Ling-Hong Meng; Xing-Wang Zhou; Bin-Gui Wang (Phytochemistry, 2025)

Sensitivity and vulnerability of vegetation to meteorological drought in Yunnan Province, southwest China - Hong Xu; Xiumei Shi; Jinxin Cheng; Meng Li (Journal of Environmental Management, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Construction of multi-metal interspecies correlation estimation models based on typical soil scenarios - Ruyu Fu; Xuedong Wang; Ying Xue; Jianming Hong; Mengjia Li; Wanyang Shi (Environmental Research, 2025)

Microplastics reduced the natural attenuation of antibiotic resistance genes in fertilized soils - Jin-Tao Yang; Yu Zhang; Shi-Yu Xiong; Hai-Jing Wei; Wan-Ting Zhang; Xin-Lei Lian; Xiao-Li Xu; Hong-Xia Jiang; Jian Sun (Environmental Pollution, 2025)

An intrinsic dendrites-free aqueous ammonium-iodine battery: Structural design, miniaturization and scale up - Minglong He; Junjie Shi; Anyu Zhang; Yuying Xu; Qing Wu; Li Wen; Qi Hong; Yang Yue; Siliang Wang (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Description of Cytobacillus Mangrovibacter sp. nov., and Cytobacillus Spartinae sp. nov., Isolated from Mangrove Sediment - Huai Shi; Manik Prabhu Narsing Rao; Qian-Qian Chen; Syed Raziuddin Quadri; Wen-Jun Li; Guo-Hong Liu (Current Microbiology, 2025)

Penicipyrrolidines A−N, pyrrolidine derivatives with inhibitory effects on EMT and fibroblast activation from the mangrove-derived fungus Penicillium sp. DM27 - Li-Ming He; Xuan Deng; Li-Hua Ni; Shi-Qi Cai; Jinhu Chen; Zejin Liao; Mengke Zhang; Hua Shui; Kong-Kai Zhu; Song Wu; Ping Gao; Ariel M. Sarotti; et al. (Marine Life Science & Technology, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Mechanism of hypoxia tolerance improvement in hybrid fish Hefang bream - Ming Wen; Chunchun Zhu; Yuhua Tang; Hong Zhang; Zheng Liu; Siyu Wang; Min Tao; Li Hu; Wenting Rao; Shengnan Li; Dingbing Gong; Shi Wang; et al. (Aquaculture, 2025)

FNDC5 alleviates Ox-LDL-induced HUVECs dysfunction by inhibiting ferroptosis through AMPK/Nrf2 signaling - Yipeng Du; Hong Ouyang; Huiyong Wang; Jian Shi; Yuanqing Li; Lingling Xu; Caiyun He; Xiudi Pan; Huidong Long (Tissue and Cell, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

Structural characterization of biohumic acid from Hongshaquan lignite degraded by Bacillus sp. XK1 and its application in the Brassica chinensis L. Growth - Chen Shi; Ya-Kun Wang; Long Yan; Yu-Hong Kang; Guang-Hui Liu; Yong Gao; Jin-Jun Bai; Yan-Jun Li; Ai-Min Wang; Ya-Nan Zhu; Xian-Yong Wei (Fuel, 2025)

Fabrication of oat β-glucan-starch composite systems by sequential extraction as batters for deep-fried mushrooms to prevent oil penetration - Yanan Wang; Qifeng Wang; Xueying Shi; Shuanglong Yang; Jianan Chen; Tao Hong; Hui Ni; Tiejing Li; Wentao Su; Yuxiao Wang (Food Chemistry, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Performance and mechanism of nano Fe-Al bimetallic oxide enhanced constructed wetlands for the treatment of Cr(VI)-contaminated wastewater - Fanlong Kong; Wenpeng Wang; Xiaoyan Wang; Hong Yang; Jianguo Tang; Yue Li; Jiaxin Shi; Sen Wang (Environmental Research, 2025)

Urbanization Gradients Affect Occurrence and Distribution of Antibiotic Contamination in the Baixi Reservoir and Yongjiang Estuary, China - Chun-Li Zheng; Gang Liu; Jin-Mao Shi; Hong-Kai Liao (Bulletin of Environmental Contamination and Toxicology, 2025)

Impact of Typhoon Path on Storm Surge in Shandong Peninsula - Hongyuan Shi; Yongkang Sun; Jiwei Sun; Longsheng Li; Shengnian Zhao; Xin Hong; Qingjie Li; Haixia Wang; Xiaofan Yuan (Journal of Ocean University of China, 2025)

Exploring Boundary Layer Physics and Atmospheric Chemistry in Megacities: Insights from the Beijing 325 m Meteorological Tower - Yele Sun; Zifa Wang; Linlin Wang; Xueling Cheng; Weiqi Xu; Yu Shi; Wei Zhou; Yan Li; Fei Hu; Zhiqiu Gao; Zhongxiang Hong (Advances in Atmospheric Sciences, 2025)

Proteomic Analysis Reveals That Dietary Supplementation with Fish Oil Enhances Lipid Metabolism and Improves Antioxidant Capacity in the Liver of Female Scatophagus argus - Jingwei He; He Ma; Dongneng Jiang; Tuo Wang; Zhiyuan Li; Gang Shi; Yucong Hong; Chunhua Zhu; Guangli Li (Fishes, 2025)
The impact of dietary lipid sources on nutrient metabolism and reproductive development is a critical focus in aquaculture broodstock nutrition. Previous studies have demonstrated that fish oil supplementation modulates the expression of genes involved in steroid hormone synthesis, glucose, and lipid metabolism promoting ovarian development in female Scatophagus argus (spotted scat). However, the effects of fish oil on hepatic function at the protein level remain poorly characterized. In this study, female S. argus were fed diets containing 8% fish oil (FO, experimental group) or 8% soybean oil (SO, control group) for 60 days. Comparative proteomic analysis of liver tissue identified significant differential protein expression between groups. The FO group exhibited upregulation of lipid metabolism-related proteins, including COMM domain-containing protein 1 (Commd1), tetraspanin 8 (Tspan8), myoglobin (Mb), transmembrane protein 41B (Tmem41b), stromal cell-derived factor 2-like protein 1 (Sdf2l1), and peroxisomal biogenesis factor 5 (Pex5). Additionally, glucose metabolism-associated proteins, such as Sdf2l1 and non-POU domain-containing octamer-binding protein (Nono), were elevated in the FO group. Moreover, proteins linked to inflammation and antioxidant responses, including G protein-coupled receptor 108 (Gpr108), protein tyrosine phosphatase non-receptor type 2 (Ptpn2), Pex5, p120 catenin (Ctnnd1), tripartite motif-containing protein 16 (Trim16), and aquaporin 11 (Aqp11), were elevated in the FO group, while proteins involved in oxidative stress, such as reactive oxygen species modulator 1 (Romo1), cathepsin A (Ctsa), and Cullin 4A (Cul4a), were downregulated. These proteomic findings align with prior transcriptomic data, indicating that dietary fish oil enhances hepatic lipid metabolism, mitigates oxidative stress, and strengthens antioxidant capacity. Furthermore, these hepatic adaptations may synergistically support ovarian maturation in S. argus. This study provides novel proteomic-level evidence supporting the role of fish oil in modulating hepatic lipid and energy metabolism, thereby elucidating the role of fish oil in optimizing hepatic energy metabolism and redox homeostasis to influence reproductive processes, advancing our understanding of n-3 long-chain polyunsaturated fatty acids (n-3 LC-PUFA) in teleost liver physiology.

Responses of zebrafish to chronic environmental stressors: anxiety-like behavior and its persistence - Xiao-hong Li; Cheng Fu; Xue-ting Tan; Shi-jian Fu (Frontiers in Marine Science, 2025)
Introduction Fish in natural ecosystems face long-term environmental stressors, with anxiety being a critical stress response. This study investigates how chronic stressors—predators, social isolation, and caffeine—affect anxiety-like behavior and cortisol levels in zebrafish ( Danio rerio ), and examines the persistence of these effects post-stressor removal. Methods Zebrafish were exposed to three stressors for 14 days. Anxiety-like behavior and cortisol levels were measured for up to 28 days following the removal of the stressors. Results Chronic predator stress significantly increased anxiety-like behavior and cortisol levels, persisting for at least seven days post-removal. Social isolation reduced anxiety-like behavior and cortisol levels, with effects lasting no less than one day after re-socialization. Caffeine induced temporary anxiolytic effects, reversing one day post-withdrawal and persisting for at least seven days, while cortisol levels remained elevated. Discussion Zebrafish exhibit stressor-specific behavioral and physiological changes with varying persistence. These findings enhance understanding of fish responses to environmental stressors, offering insights into their survival strategies and ecosystem health.

Coastal redox shifts over the past 167 years and preservation of total organic carbon and total nitrogen - Yang-Guang Gu; Hai-Song Li; Hong Su; Richard W. Jordan; Rui-Ze Liang; Shi-Jun Jiang (Marine Pollution Bulletin, 2025)

Chronic sublethal exposure to chlorantraniliprole inhibits growth and development by disrupting the sugar and fatty acid metabolism in Spodoptera frugiperda - Xiao-Guang Liu; Qing-Ge Wang; Xiao-Ming Liu; Xiang Li; Meng-Fang Du; Cai-Hong Tian; Yun-Hui Zhang; Shi-Heng An (Pesticide Biochemistry and Physiology, 2025)

Chloroplast state transitions modulate nuclear genome stability via cytokinin signaling in Arabidopsis - Yajun Zeng; Sujuan Duan; Yawen Wang; Zhifeng Zheng; Zeyi Wu; Meihui Shi; Manchun Wang; Lan Jiang; Xue Li; Hong-Bin Wang; Hong-Lei Jin (Molecular Plant, 2025)

Perfluorobutanoic acid: A short-chain perfluoroalkyl substance exhibiting estrogenic effects through the estrogen-related receptor γ pathways - Fangfang Li; Lu Chen; Sha Shi; Wen-Jun Hong; Minjie Li; Liang-Hong Guo (Journal of Hazardous Materials, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Electroosmotic-driven coiled hydrogel-based yarn muscles - Xinghao Hu; Jinchang Jiang; Hailong Wei; Jiayu Chen; Zhanyuan Wang; Ghassen Mhenni; Hong Li; Hongwei Hu; Shengping Dai; Shi Hyeong Kim; Jianning Ding (Chemical Engineering Journal, 2025)

Synthesis of furan-based cationic biopolyamides and their removal abilities for perfluoroalkyl and polyfluoroalkyl substances - Hong-Hui Shu; Liu-Qi Shi; Hui-Qin Zhang; Yun Liu; Sheng-Li Han; Jing-Yi Rao; Cheng-Mei Liu (Chemical Engineering Journal, 2025)

Comamonas squillarum sp. nov., Isolated from Intestine of Red Swamp Crayfish (Procambarus clarkii) - Shi Shi; Dao-Feng Zhang; Hong-Chuan Wang; Fu-Hui Jiang; Li-Fan Cui; Ying Huang (Current Microbiology, 2025)

Erwinia aeris sp. nov., A Novel Bacterium Isolated from the Surface of an Ore in Hubei Province, China - He-Bao Guo; Hong-Tu Zhu; Yi-Fan Zhang; Fu Yang; Xiao-Tong Ma; Shi-Gui Li; Hai-Lei Wei; Xiao-Xia Zhang (Current Microbiology, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Upper Ordovician conodonts from the Taoqupo section in the southwestern margin of the North China Craton - Shi-Xiao Li; Xiu-Chun Jing; Hong-Rui Zhou; Xun-Lian Wang; Yang Shen; Qiang Fang; Zhen-Tao Wang (Palaeoworld, 2025)

Microplastics-exposure experience aggravates the accumulation of diarrhetic shellfish toxins (DSTs) in thick-shell mussel Mytilus coruscus through impairing detoxification processes - Kuan-Kuan Yuan; Ying-Ying Yu; Yu-Jie Liu; Xiu-Lin Yang; Yan-Hang Mo; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Journal of Hazardous Materials, 2025)

Pacific Walker Circulation modulated millennial-scale East Asian summer monsoon rainfall variability over the past 40 kyr - Yi Zhong; Yuxing Liu; Xiaojing Du; Xiaoxu Shi; Xing Xu; Zhengyao Lu; Stefanie Kaboth-Bahr; Mark J. Dekkers; Juan C. Larrasoaña; Keiji Horikawa; Chijun Sun; Liang Ning; et al. (Global and Planetary Change, 2025)

Relationship between pyrolytic sulfur migration behavior and structural composition of high-sulfur fat coal - Zhan-Ku Li; Zheng-Zhi Zhang; Kai Zhang; Hong-Lei Yan; Jing-Chong Yan; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Shi-Gang Kang; Heng-Fu Shui (Fuel, 2025)

Optimized near infrared reflectance model based on preprocessing selection strategy for rapid analysis of 2-acetyl-1-pyrroline content in rice flour - Li-Hong Xie; Shao-Qing Tang; Gao-Neng Shao; Zhong-Hua Sheng; Shi-Kai Hu; Xiang-Jin Wei; Gui-Ai Jiao; Ling Wang; Pei-Song Hu (Food Control, 2025)

Impact of different continuous fertilizations on the antibiotic resistome associated with a subtropical triple-cropping system over one decade - Jin Zheng; Ya-Ying Li; Yu-Sheng Lu; Dan Wang; Chong Liu; Huan-Long Peng; Chao-Hong Shi; Kai-Zhi Xie; Kun Zhang; Li-Li Sun; Chang-Min Zhou; Wen-Jie Gu (Environmental Pollution, 2025)

Eleutherococcus giraldii (Harms) Nakai: a review of botany, traditional uses, phytochemistry, pharmacology and quality control - Ling Li; Jie Zhang; Li-wen Zhong; Rui Gu; Shi-hong Zhong (Phytochemistry Reviews, 2025)

A rare tetrahydroimidazopyridine from the marine-derived fungus Paraconiothyrium sp. YK-03 - Wen-Ke Gao; Xiao-Yan Song; Shi-Wei Li; Bian-Xia Xue; Hong-Hua Wu; Li-Hua Zhang; Yue-Hu Pei (Natural Product Research, 2025)

The research of nicotinamide and β-arbutin on reducing melanin content in the skin of leopard coral grouper (Plectropomus leopardus) - Zhi Bin Sun; Shi Ying Liu; Xin An Wang; Ai Jun Ma; Zhi Hui Huang; Zhi Feng Liu; Wei Heng Sun; Peng Fei Yan; Dong Hui Gou; Hui Yu Xiao; Hao Zhe Li; Vorathep Muthuwan; et al. (Aquaculture, 2025)

Immunosuppressive leucosceptrane-type sesterterpenoids with antipodal cyclopentenones isolated from Leucosceptrum canum - Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Ting-Ting Zhou; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Anti-inflammatory oxazole-, nitro- and hexahydropyrrolo[2,1-b]oxazole-containing abietane diterpenoid alkaloids from Salvia miltiorrhiza - Li-Xia Wang; Shao-Jie Shi; Li-Ping Long; Xiao-Ping He; Peng Zhang; Xiao-Wen Yang; Yan Liu; Xue-Mei Niu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Aero-elastic characteristics of a wing in different proximity to the free surface - Ying-Hong Li; Shi-Li Sun; Hui-Long Ren; Jian Hu; Jia-Wei Chen (Ocean Engineering, 2025)

Construction of S-scheme BiOCl/Bi24O31Cl10 heterojunction by thermally induced in-situ phase transition strategy for photocatalytic degradation of ciprofloxacin - Yuan Wei; Chao Liu; Xin Li; Hong-Yu Wang; Yu-Miao Yang; Gao-Feng Shi; Guo-Ying Wang (Journal of Water Process Engineering, 2025)

Yeast community in the first-round fermentation of sauce-flavor Baijiu: Source, succession and metabolic function - Zheng-Pei Chen; Qian Cao; Tian-Tian Meng; Wei Shi; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Fu-Wei Chen; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; et al. (Food Research International, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Development of a platform strain for integration expression of phospholipase D and its application in improving phosphatidylserine content of egg yolk - Peng Zhang; Xiao-Li Kong; Jin-Song Gong; Zhi-Yuan Yao; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2025)

Enhancing Na+ transport in single atomic Fe-anchored hierarchical porous carbon anode in SIB: Implanting high energy azole - Zhuo Chen; Xing Lu; Yanan Zhang; Xingxing Zhang; Ke Zhang; Yang Shi; Tao Zhang; Shun Wang; Yali Li; Hong Wang; Wenhuan Huang (Chemical Engineering Journal, 2025)

Mechanism, diffusion, and kinetics characteristics of nitrocellulose denitrification revealed by DFT and MD - Shen Li; Zhong-Xin Liu; Shi-Ying Li; Ya-Jun Ding; Zhong-Liang Xiao; Jie Zhou; Xiao-Qing Wu; Hong-Lei Fan; Zheng-Hong Luo; Xi-Bao Zhang (Chemical Engineering Journal, 2025)

A comprehensive review on the application of neural network model in microbial fermentation - Jia-Cong Huang; Qi Guo; Xu-Hong Li; Tian-Qiong Shi (Bioresource Technology, 2025)

Experimental study on the sedimentary structure of tailings storage facilities - Zhijie Duan; Quanming Li; Hai Shi; Jinglong Chen; Songli Jin; Hong Zhang (Journal of Soils and Sediments, 2025)

Huanglian decoction prevents and treats radiation-induced intestinal injury in lung cancer by regulating endoplasmic reticulum stress - Liang-liang Shi; Ya-ping Chen; Hao-ming Guo; Xue-peng Wang; Yang-yang Li; Shuai-zhe Wang; Shang-zu Zhang; Qi-hong Zhuo; Yong-qi Liu; Ben-jun Wei; Li-ying Zhang (Journal of Natural Medicines, 2025)

Inhibition of CB1R in the Hypothalamic Paraventricular Nucleus Ameliorates Hypertension Through Wnt/β-Catenin/RAS Pathway - Hong-Li Gao; Yu Yang; Hua Tian; Li-Yan Fu; Kai-Li Liu; Xiu-Yue Jia; Xiao-Lian Shi; Yu-Ming Kang; Xiao-Jing Yu (Cardiovascular Toxicology, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Evaluation of a transgenic tg(Hspa8b: GFP) Nile tilapia for monitoring of stress and anti-stress effects of the influence of temperature and vibration - Zhi Lei Yao; Jia Yue Li; Xiao Wang; Hong Ju Chen; Shi-Jin Jiang; Yan Zhao; Xiang Shan Ji (Aquaculture International, 2025)

Corrigendum: Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)

Potassium status and the risk of type 2 diabetes, cardiovascular diseases, and mortality: a meta-analysis of prospective observational studies - Yahui Fan; Min Wu; Lu Ding; Huixin Ji; Jinping Zhao; Xiaohui Li; Zhaofang Li; Sijiao Liu; Hong Jiang; Jia Shi; Haoyuan Lei; Mingxu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Two-stage estimation of hourly diffuse solar radiation across China using end-to-end gradient boosting with sequentially boosted features - Lu Chen; Haoze Shi; Hong Tang; Xin Yang; Chao Ji; Zhigang Li; Yuhong Tu (Remote Sensing of Environment, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Investigation on nitrogen migration and transformation during hydrothermal conversion of glucose and xylose in N-rich solution recycled from hydrothermal treatment of fiberboard - Li Zhang; Yi Wei; Yuan Yin; Xiang Liu; Shu Zhang; Lei Shi; Juntao Wei; Hong Zhang; Alexander N. Kozlov; Maxim V. Penzik; Deliang Xu (Journal of Cleaner Production, 2024)

Nitrogen and sulfur metabolism in anaerobic hydrogen-producing microbiome as a challenge for 2,4-DCP dechlorination - Jiunn-Jyi Lay; Shi-Hong Li; Chang-Lung Han; Wei-Zhen Zhong (Journal of Environmental Chemical Engineering, 2024)

The changes of fungal community and flavor substances in Yunnan-style sausages: A comparative analysis of different drying methods - Lifen Shi; Qi Wang; Zhengze Xie; Chunxia Wu; Tingting Peng; Xuruo Nian; Lang Li; Hong Li; Tao Chen (Food Chemistry, 2024)

Seasonality shapes the microbiota and metabolome of strong-flavor Baijiu during fermentation and affects its flavor characteristics - Li-Juan Chai; Jing-Yi Zhang; Tao Gao; Long-Yun Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Jin-Song Shi; Xiang Chen; Zheng-Hong Xu (Food Bioscience, 2024)

Valence-dependent dynamics: quantitatively understanding arsenic reallocations on iron oxyhydroxide mediated by microbial respiration - Zebin Hong; Kai Liu; Fangbai Li; Thomas Borch; Yundang Wu; Congjian Liao; Xiaoxia Zhou; Tongxu Liu; Qiantao Shi; Liping Fang (Chemical Geology, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Optimizing personal comfort: Short-term personalized heating impact on sanitation workers' thermo-physiological responses - Chujian Gu; Yang Li; Chen Shi; Bojun Zhang; Shufan He; Bo Hong (Building and Environment, 2024)

Serum soluble interleukin-2 receptor alpha may predict tubulointerstitial inflammatory cell infiltration and short-term disease progression in immunoglobin A nephropathy - Chenqi Xu; Kunming Pan; Jie Li; Yang Li; Shi Jin; Yiqin Shi; Jie Teng; Xiaoqiang Ding; Xialian Xu; Hong Liu (Immunologic Research, 2024)

Decoding the Qu-aroma of medium-temperature Daqu starter by volatilomics, aroma recombination, omission studies and sensory analysis - Sheng-Bing Yang; Jun-Jie Fu; Jia-Huan He; Xiao-Juan Zhang; Li-Juan Chai; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Zhen-Ming Lu; Zheng-Hong Xu (Food Chemistry, 2024)

Passive protection of chicken egg yolk immunoglobulin (IgY) against Streptococcus agalactiae infection in Nile tilapia (Oreochromis niloticus) - Linpeng Zhang; Yucong Hong; Kaihui Sun; Shuyan Zhao; Yanhan Bai; Shiyi Yang; Junjie Tao; Fei Shi; Fanbin Zhan; Li Lin; Zhendong Qin (Fish & Shellfish Immunology, 2024)

Molecular characterization, spatio-temporal expression patterns of crtc2 gene and its immune roles in yellow catfish (Pelteobagrus fulvidraco) - Wan-Hong Zeng; Zheng-Yong Wen; Xiu-Ying Wei; Yu He; Luo Zhou; Peng Hu; Qing-Chao Shi; Chuan-Jie Qin; Jun Wang; Rui Li; Xiao-Ying Jing; Wei Hu; et al. (Fish & Shellfish Immunology, 2024)

Preparation of novel magnetic ethylene glycol dimethacrylate-based molecularly imprinted polymer for rapid adsorption of phthalate esters from ethanol aqueous solution - Yuanhao Zhou; Shunying Li; Xiaoya Sun; Jun Wang; Haoxiang Chen; Qiangqiang Xu; Hong Ye; Shuangyang Li; Shengpeng Shi; Xianren Zhang (Environmental Pollution, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Influence of soil pH and organic carbon content on the bioaccessibility of lead and copper in four spiked soils - Jiaqi Cui; Hongbo Li; Yangxiaoxiao Shi; Feng Zhang; Zhineng Hong; Di Fang; Jun Jiang; Yujun Wang; Renkou Xu (Environmental Pollution, 2024)

In situ iron coating of amorphous boron and characterization of its energy release behavior - Hongyang Li; Hong Li; Chao Wang; Zhenfeng Shen; Shentao Zeng; Sujun Shi; Qing Cai; Wenqi Xu; Ran Wang; Cui Luo; Ying Liu (Chemical Engineering Journal, 2024)

A thermoresponsive metabolic nanomodulator for achieving photochemotherapy-sensitized cancer immunotherapy - Shun-Yu Wu; Xiao-Yu Zhu; Xinping Zhang; Yong-Xi Zhou; Shao-Zhe Wang; Yan-Hong Li; Shi-Jie Hao; Tian-Yu Wang; Xin-Wang Yu; Yuxin Guo; Guang-Yu Pan; Bin Xu; et al. (Chemical Engineering Journal, 2024)

Comparative efficacy of alkaline slag, biomass ash, and biochar application for the amelioration of different acidic soils - Ernest Uwiringiyimana; Hong-wei Lai; Ni Ni; Ren-yong Shi; Xiao-ying Pan; Jia-ning Gao; Md Romel Biswash; Jiu-yu Li; Xiu-min Cui; Ren-kou Xu (Plant and Soil, 2024)

Acinetobacter corruptisaponis sp. nov., Isolated from a Spoiled Bath Lotion - Ying-Si Wang; Gang Zhou; Hong-Bing Tao; Lei Gao; Bao-Zhu Fang; Xiu-Jiang Yang; Hong Peng; Xia Wen; Xiao-Mo Huang; Jie Wang; Wen-Jun Li; Qing-Shan Shi; et al. (Current Microbiology, 2024)

Refracturing shale gas wells in China: Doubling water consumption for enhanced gas recovery - Wenrui Shi; Jianfeng Li; Zisang Huang; Yijiang Feng; Pu Hong; Shaojia Lei; Yi Wu; Jianliang Wang; Meiyu Guo (Science of The Total Environment, 2024)

Roof greening in major Chinese cities possibly afford a large potential carbon sink - Chao Yang; Yinghui Zhang; Min Chen; Song Zhu; Yuzhi Tang; Zhixin Zhang; Wei Ma; Huizeng Liu; Junyi Chen; Bohui Tang; Dejin Zhang; Zhengdong Huang; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Lappanolides A−N, fourteen undescribed sesquiterpenoids from Saussurea costus (Syn. Saussurea lappa) and their anti HBV activity - Hong-Bo Li; Shi-Qun Bai; Teng-Yun Shu; Qiong Wang; Hao Chen; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Hydrodynamic characteristics of a seven blade highly-skewed propeller operating underneath a free surface - Ying-Hong Li; Shi-Li Sun; Jian Hu (Ocean Engineering, 2024)

RAD-seq data for Engelhardia roxburghiana provide insights into the palaeogeography of Hainan Island and its relationship to mainland China since the late Eocene - Pei-Han Huang; Tian-Rui Wang; Min Li; Zi-Jia Lu; Ren-Ping Su; Ou-Yan Fang; Lang Li; Shi-Shun Zhou; Yun-Hong Tan; Hong-Hu Meng; Yi-Gang Song; Jie Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Comparative genomics of Clostridium tyrobutyricum reveals signatures of environment-specific adaptation and metabolic potentials - Guan-Yu Fang; Li-Juan Chai; Zhen-Ming Lu; Xiao-Juan Zhang; Hong-Yu Xu; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

FTO mediates bisphenol F-induced blood-testis barrier impairment through regulating ferroptosis via YTHDF1/TfRc and YTHDF2/SLC7A11 signal axis - Yu Shi; Li Yin; Jiang-ying Li; Shi-meng Zhou; Na Wang; Hong-qiang Chen; Yong Zeng; Ya-wen Li; Wen-bin Liu (Environmental Pollution, 2024)

Overlapping hotspot tracks and melts from diffuse plume materials in the upper mantle generated intraplate seamount groups in the West Pacific - Xun Wei; Guo-Liang Zhang; Ji Zhang; Xue-Fa Shi; Paterno R. Castillo; Yan Zhang; Wan-Feng Zhang; Yi-Gang Xu; Hong-Yan Li; Hui Zhang (Earth and Planetary Science Letters, 2024)

Adsorption and nucleation mechanism of molten carbonate on nano-SiC surface - Yuxian Wang; Liu Shi; Xian Li; Xin Guo; Zhenzhong Hu; Wuyang Xiao; Xiangxi Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Chemical Engineering Journal, 2024)

A novel molecular structure parameter determination method for biomass thermochemical conversion mechanism investigation - Liu Shi; Bing Peng; Xian Li; Shuo Li; Yiming Sun; Zhenzhong Hu; Hongyun Hu; Guangqian Luo; Hong Yao (Chemical Engineering Journal, 2024)

Theoretical study of the reaction of organic peroxyl radicals with alkenes and their accretion products involved in the atmospheric nucleation - Biao Dong; Hong Ding; Huidi Zhang; Hu Zhao; Haojie Xu; Zhenyu Xu; Juanbao Wang; Yunfeng Li; Xiangli Shi (Atmospheric Environment, 2024)

Coral reefs of Pakistan: a comprehensive review of anthropogenic threats, climate change, and conservation status - Ishfaq Ahmad; Pu Guo; Mei-Xia Zhao; Yu Zhong; Xiao-Yun Zheng; Shu-Qi Zhang; Jian-Wen Qiu; Qi Shi; Hong-Qiang Yan; Shi-Chen Tao; Li-Jia Xu (Frontiers in Marine Science, 2024)
The coral reefs along Pakistan’s coastline are of ecological and economic significance. However, they are increasingly threatened by anthropogenic threats and climate change. These vulnerable ecosystems are declining due to various factors such as sedimentation, climate change, overfishing, destructive fishing practices, marine pollution, and tourism development. We found that 29%, 24%, 26%, 16% and 18% of the studies exceeding, marine pollution, overfishing/destructive fishing, coastal tourism, climate change and sedimentation, respectively; thus, indicating inadequate water quality status in part of Pakistan coastal water. These influences lead to several negative impacts, such as jeopardized coral health, decline in biodiversity, and the simplification of reef structures. In response to these threats, conservation efforts are imperative. This literature review provides an in-depth analysis of anthropogenic threats, climate change and the conservation of coral reefs in Pakistan. This review provides suggestions on how the country could better conserve its coral reef ecosystem. These include (1) initiatives such as establishing marine protected areas (MPAs), (2) encouraging sustainable fishing practices and reducing pollution, (3) developing the country as an ecotourism destination and implementing climate change adaptation measures, and (4) community engagement through awareness campaigns and fostering collaboration among, governmental organizations, non-governmental organizations (NGOs) and scientists. These comprehensive conservation policies address human-caused and other challenges, safeguarding their ecological, economic, and cultural relevance for future generations.

Torsemide Crystalline Salts with a Significant Spring-Parachute Effect - Xuezhen Deng; Weimin Shi; Kun Qian; Jie Yang; Siyu Yuan; Hong Li (AAPS PharmSciTech, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Developing thermal prediction models for children in outdoor environments - Yichen Li; Xiaoxi Wang; Jiaqi Li; Chen Shi; Bo Hong (Sustainable Cities and Society, 2024)

Estimating river discharge across scales with a novel regional gauging method driven by Sentinel satellite data - Hong Lin; Xiao Cheng; Junguo Liu; Qian Shi; Teng Li; Lei Zheng; Xuejiao Hou; Jinyang Du (Remote Sensing of Environment, 2024)

Comparison of Chinese medicine additives for antibiotic resistance risks in the Wuding chickens under high stocking density: Advantages and drawbacks - Hong Hu; Ying Huang; Changyou Shi; Anjian Li; Qianhui Mi; Kunping Wang; Zelong Zhao; Xi Bai; Hongbin Pan (Journal of Cleaner Production, 2024)

Alteration of soil pH induced by submerging/drainage and application of peanut straw biochar and its impact on Cd(II) availability in an acidic soil to indica-japonica rice varieties - Md Romel Biswash; Ke-wei Li; Ren-kou Xu; Ernest Uwiringiyimana; Peng Guan; Hai-long Lu; Jiu-yu Li; Jun Jiang; Zhi-neng Hong; Ren-yong Shi (Environmental Pollution, 2024)

Constructing local nanomolecular trap in a scalable, low-cost, and ultramicroporous metal–organic framework for efficient capture of greenhouse gases SF6 and CO2 - Shi-Ming Li; Qiang Zhang; Hong-Chan Jiang; Qing-Ling Ni; Liu-Cheng Gui; Xiu-Jian Wang; Tong-Liang Hu (Chemical Engineering Journal, 2024)

Spray of water-in-oil emulsified heavy oil with high water content - Ruo-Fan Shi; Yu-Feng Xi; Li-Tao Wang; Hong-Jun Lu; Xiao Zhang; Xin-Yue Zhang; Zi-Bin Huang; Pei-Qing Yuan (Chemical Engineering Journal, 2024)

Insight into volatile-char interaction mechanisms of biomass torrefaction based on three major components - Liu Shi; Shuo Li; Xian Li; Bing Peng; Zhenzhong Hu; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2024)

Central cell: the key to determine persistent pollen tube attraction or termination - Jiang-Guo Meng; Shi-Zhen Li; Hong-Ju Li (Science China Life Sciences, 2024)

Assessing the degree of impact from iceberg activities on penguin colonies of Clarence Island - Hong Lin; Xiao Cheng; Teng Li; Qian Shi; Qi Liang; Xinyu Meng; Shaoyin Wang; Lei Zheng (Acta Oceanologica Sinica, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Correction: FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2024)

Integrated analysis of the gonadal methylome and transcriptome provides new insights into the expression regulation of sex determination and differentiation genes in spotted scat (Scatophagus argus) - Kai-Zhi Jiao; Yu Li; Yuan-Qing Huang; Charles Brighton Ndandala; Gang Shi; Si-Ping Deng; Hong-Juan Shi; Hua-Pu Chen; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2024)

Fangchinoline inhibits mouse oocyte meiosis by disturbing MPF activity - Shi-Cai Gao; Ming-Zhe Dong; Bing-Wang Zhao; Sai-Li Liu; Jia-Ni Guo; Si-Min Sun; Yuan-Yuan Li; Yuan-Hong Xu; Zhen-Bo Wang (Toxicology in Vitro, 2024)

Phase I clinical trial of intracerebral injection of lentiviral-ABCD1 for the treatment of cerebral adrenoleukodystrophy - Qiu-Hong Wang; Jing Wang; Zhi-Pei Ling; Zhi-Qiang Cui; Jie Gong; Rui Zhang; Shi-Jun Li; Yang-Yang Wang; Rui Yang; De-Hui Huang; Wen He; Jing Gao; et al. (Science Bulletin, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Research on optimal allocation of surface ship formation based on index method and multi-objective programming - Zilong Guo; Mei Hong; Jian Shi; Yongchui Zhang; Longxia Qian; Hanlin Li (Ocean Engineering, 2024)

Influence of geological uncertainty on longitudinal deformation of tunnel based on improved coupled Markov chain - Qi-Hao Jiang; Jin-Zhang Zhang; Dong-Ming Zhang; Hong-Wei Huang; Jing-Kang Shi; Zhang-Lin Li (Engineering Geology, 2024)

Lateral holding behaviour of torpedo piles in spatially variable soil: Development of a probabilistic design approach - Jiang Tao Yi; Shi Jie Xu; Wu Hao Liu; Lin Ding; Zhen Wang; Hong Yu Tang; Xiao Bin Li (Computers and Geotechnics, 2024)

A lightweight and efficient hollow sunken carbon@MnO2/reduced graphene oxide composite for high-performance electromagnetic wave absorption - Yuxia Shi; Baoquan Liang; Hong Gao; Rui Zhao; Yingzan Zhuang; Qin Guo; Xianhan Shao; Hankun Wang; Mingliang Ma; Tingxi Li; Yong Ma (Chemical Engineering Journal, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Targeting GLUT1 degradation with assembling glycopeptide for cancer inhibition - Xia Wu; Jun Shen; Xingyue Jiang; Hong Han; Zenghui Li; Yatong Xiang; Dan Yuan; Junfeng Shi (Chemical Engineering Journal, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

A recombinase polymerase amplification–SYBR Green I assay for the rapid and visual detection of Brucella - Jiang Chang; Nan Wang; Jun-Peng Zhan; Shi-Jun Zhang; De-Ying Zou; Feng Li; Ying Zhang; Yan-Song Li; Pan Hu; Shi-Ying Lu; Zeng-Shan Liu; Hong-Lin Ren (Folia Microbiologica, 2024)

Late Mesozoic tectonic affinity of the Tengchong Block and southward extension of the Bangong-Nujiang Suture: constraints from Early Cretaceous granitic rocks in western Yunnan, SW China - Chen Wang; Gang Li; Zheng-Hong Liu; Shi-Jie Wang; Xi Chen; Yu Gao; Nuo Zhang; Yu-Fei Xuan (International Geology Review, 2024)

Two new benzophenones from the moss Pogonatum spinulosum - Wen-Bin Duan; An-tang Peng; Shi-Nong Yuan; Shao-Nan Wang; Bo-Wen Li; Xu-Hong Duan (Natural Product Research, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Mathematical modelling of a three-stage constructed rapid infiltration system for wastewater plant tailwater treatment - Yihao Shen; Xiejuan Lu; Jiakai Jiang; Hong Li; Chaoqun Len; Zhuo Shi; Feixiang Zan; Juan Mao; Jiaoyang Wang; Xiaohui Wu (Journal of Water Process Engineering, 2024)

Catalytic hydroconversion of aryl ethers to polycyclic alkanes over Ni@MCM-41/β composite zeolite: Aromatic α-carbon activation and hydrogen transfer mechanisms - Guang-Hui Liu; Wen-Ao Shi; Jun Li; Han Wang; Ai-Min Wang; Yu-Hong Kang; Yong Gao; Ni Bai; Jie Kang; Chen Shi; Xian-Yong Wei (Fuel, 2024)

Review on toxicology and activity of tomato glycoalkaloids in immature tomatoes - Li-hao Wang; De-hong Tan; Xue-song Zhong; Mei-qi Jia; Xue Ke; Yu-mei Zhang; Tong Cui; Lin Shi (Food Chemistry, 2024)

Seasonal variations and sources of atmospheric EPFRs in a megacity in severe cold region: Implications for the influence of strong coal and biomass combustion - Shi-Ming Jia; Mei-Hong Chen; Pu-Fei Yang; Liang Wang; Guo-Ying Wang; Li-Yan Liu; Wan-Li Ma (Environmental Research, 2024)

Rapid and highly sensitive colorimetric LAMP assay and integrated device for visual detection of monkeypox virus - Yadan Peng; Ruolan Hu; Shuang Xue; Yugan He; Lili Tian; Zehan Pang; Yile He; Yuqi Dong; Yinghan Shi; Shuqi Wang; Bixia Hong; Ke Liu; et al. (Analytica Chimica Acta, 2024)

Toward soil carbon storage: The influence of parent material and vegetation on profile-scale microbial community structure and necromass accumulation - Yu-Zhu Li; Xue-Lian Bao; Shi-Xin Tang; Ke-Qing Xiao; Cheng-Jun Ge; Hong-Tu Xie; Hong-Bo He; Carsten W. Mueller; Chao Liang (Soil Biology and Biochemistry, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

α-Fe2O3 nanorods on CoFe-LDH@MX via interfacial interactions for Congo red removal: Experimental and mechanistic studies - Xianyong Hong; Mingxing Shi; Linrui Li; Zhoutian Ding; Zhiren Zhao; Ping Du; Mingzhu Xia; Fengyun Wang (Journal of Environmental Chemical Engineering, 2024)

Effect of immersion time on bacterial community structure and sulfur metabolism in biofilm on concrete surface in sewer environment - Mengshu Hong; Zhaoguang Li; Xuan Shi; Qiang Fu; Shaohui Zhang; Chen Xie; Yinchu Tian; Ditao Niu (International Biodeterioration & Biodegradation, 2024)

Systematic engineering for efficient production of nicotinamide mononucleotide from d-xylose and nicotinamide in Escherichia coli - Chang Su; Lin Cheng; Jin-Song Gong; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Food Bioscience, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Study of the antivirus function mediated by STING in Micropterus salmoides - Jin-Quan Fan; Qian-Ming Hong; Li-Shi Liu; Qi Chen; Yi-Hong Chen (Fish & Shellfish Immunology, 2024)

Seasonal changes in hepatic lipid metabolism and apoptosis in Chinese soft-shelled turtle (Pelodiscus sinensis) - Xiaoqi Ai; Rui Lin; Zeeshan Ali; Qingjun Zhu; Li Ding; Haitao Shi; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Interactive Effects of Selenium and Arsenic on their Accumulation, Translocation, Arsenic and Selenium Species, and Subcellular Distribution in Brassica Vegetables - Yuyan Qin; Yunru Wang; Pengtao Shi; Feng Wu; Yunjie Zhong; Hong Li; Bin Shan (Journal of Soil Science and Plant Nutrition, 2024)

Identification of lignans as ATP citrate lyase (ACLY) inhibitors from the roots of Pouzolzia zeylanica - Jin-Long Li; Jia-Yi Jiang; Shan-Shan Gu; Lei Zhang; Yan Sun; Xue-Han Wang; Dan-Yu Li; Zhe-Yu Chen; Sheng-Shi Jiang; Wei-Zhong Zhu; Hao-Wen Jiang; Hong-Jie Zhang (Natural Product Research, 2024)

Exposure to microplastics renders immunity of the thick-shell mussel more vulnerable to diarrhetic shellfish toxin-producing harmful algae - Kuan-Kuan Yuan; Ying-Ying Yu; Yan-Hang Mo; Yu-Jie Liu; Wei-Xia Zhang; Jin-Jin Lv; Wei Shi; Guang-Xu Liu; Hong-Ye Li; Wei-Dong Yang (Science of The Total Environment, 2024)

Regional variations in management and outcomes of patients with acute coronary syndrome in China: Evidence from the National Chest Pain Center Program - Shuduo Zhou; Yan Zhang; Xuejie Dong; Junxiong Ma; Na Li; Hong Shi; Sidney C. Smith; Yinzi Jin; Ming Xu; Dingcheng Xiang; Zhi-Jie Zheng; Yong Huo (Science Bulletin, 2024)

A review of the ethnopharmacology, phytochemistry, pharmacology, pharmacokinetics and toxicology of Abri Herba (Ji-Gu-Cao) - Cheng-Jun Liu; Hong-Xin Li; Zi-Hao Chen; Jin-Jin Li; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Preparation of novel gallic acid-based dummy-template molecularly imprinted polymer adsorbents for rapid adsorption of dibutyl phthalate from water - Shunying Li; Yuanhao Zhou; Qiangqiang Xu; Haoxiang Chen; Shengpeng Shi; Ruobing Jia; Yingying Zhang; Hong Ye (Environmental Pollution, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

Molecular detection and genetic characteristics of porcine circovirus 3 and porcine circovirus 4 in central China - Lin-Qing Wang; Jia-Xin Li; Xi-Meng Chen; Xin-Yue Cao; Hong-Lei Zhang; Lan-Lan Zheng; Shi-Jie Ma (Archives of Virology, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Curvularin derivatives from the marine mangrove derived fungus Penicillium sumatrense MA-325 - Yi-Ran Wang; Yu-Liang Dong; Xiao-Ming Li; Xiao-Shan Shi; Hong-Lei Li; Ling-Hong Meng; Rui Xu; Bin-Gui Wang (Phytochemistry, 2024)

Protective effects and mechanism of chemical- and plant-based selenocystine against cadmium-induced liver damage - Lin Zhang; Wen-Yao Shi; Jia-Ying Xu; Yan Liu; Shi-Jia Wang; Jia-Yang Zheng; Yun-Hong Li; Lin-Xi Yuan; Li-Qiang Qin (Journal of Hazardous Materials, 2024)

Transcriptome analysis reveals the inhibitory mechanism of phloretin on virulence expression of Staphylococcus aureus and its application in cooked chicken - Hong Li; Changzhu Li; Ce Shi; Manal Y. Sameeh; Fahad Al-Asmari; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Phosphoproteomics analysis reveals the anti-bacterial and anti-virulence mechanism of eugenol against Staphylococcus aureus and its application in meat products - Hong Li; Changzhu Li; Ce Shi; Metab Alharbi; Haiying Cui; Lin Lin (International Journal of Food Microbiology, 2024)

Self-floating, monolithic, and aligned phenolic carbon aerogels from coal tar for solar-driven evaporation - Hong-Lei Yan; Jin-Yuan Cheng; Zhan-Ku Li; Jing-Chong Yan; Wei-Dong Zhang; Zhi-Ping Lei; Shi-Biao Ren; Zhi-Cai Wang; Heng-Fu Shui (Fuel, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Comparative toxic effect of ammonia exposure on Mauremys sinensis and invasive species Trachemys scripta elegans - Li Ding; Zubin Huang; Lingyue Liang; Haitao Shi; Zhenhua Fang; Meiling Hong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Highly efficient and stable solution-processed deep-blue OLEDs with LT95 over 50 h at 1000 nit - Hongyang Li; Hao Yan; Xiaopeng Zhang; Kefei Shi; Changchun Kuang; Xiwei Zheng; Yaowu He; Lingqiang Meng; Hong Xu; Zhimin Meng; Chaoyi Yan; Guodan Wei; et al. (Chemical Engineering Journal, 2024)

Meta-analysis of the SARS-CoV-2 positivity rate in municipal wastewater - Keyi Cheng; Ye Lv; Chaokang Li; Shi Cheng; Shanshan Xu; Xin Gao; Hong Xu (Environmental Geochemistry and Health, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

RETRACTED: Effect of the defoliant tribufos on the reproductive ability of Japanese quail (Coturnix japonica) - Xin-Li Yan; Xue Luo; Man Xu; Ying Shi; Yi-Jin Kang; Hong-Wei Wang (Chemosphere, 2024)

Widespread inversions shape the genetic and phenotypic diversity in rice - Wenchuang He; Huiying He; Qiaoling Yuan; Hai Zhang; Xiaoxia Li; Tianyi Wang; Yingxue Yang; Longbo Yang; Yuting Yang; Xiangpei Liu; Hua Wei; Hong Zhang; et al. (Science Bulletin, 2024)

Postharvest application of methyl jasmonate alleviates lignin accumulation in stone cells of pear fruit during low-temperature storage - Panting Hong; Jingyi Zhang; Dongfang Shi; Can Yang; Ming Zeng; Xue Li; Kun Zhou; Wanpeng Xi (Postharvest Biology and Technology, 2024)

Halogenated aliphatic and phenolic disinfection byproducts in chlorinated and chloraminated dairy wastewater: Occurrence and ecological risk evaluation - You-Wei Jiang; Gui-Jing Wang; Shuang Zang; Yue Qiao; Hong-Fei Tao; Qiao Li; Han Zhang; Xian-Shi Wang; Jun Ma (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Thermal performance and ventilation analysis of a zigzag Trombe wall: Full numerical and experimental investigations - Hong-Liang Zhang; Bin Li; Dun-Ke Shi; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2024)

A high-resolution map of soil organic carbon in cropland of Southern China - Bifeng Hu; Modian Xie; Yue Zhou; Songchao Chen; Yin Zhou; Hanjie Ni; Jie Peng; Wenjun Ji; Yongsheng Hong; Hongyi Li; Zhou Shi (CATENA, 2024)

Interaction of 17α-ethinylestradiol and methyltestosterone in western mosquitofish (Gambusia affinis) across two generations - Guo-Yong Huang; Gui-Zhen Fang; Wen-Jun Shi; Xiao-Pei Li; Chen-Si Wang; Hong-Xing Chen; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2024)

Effects of butyl paraben on behavior and molecular mechanism of Chinese striped-necked turtle (Mauremys sinensis) - Xia Wu; Ijaz Khan; Xiaoqi Ai; Jiliang Zhang; Haitao Shi; Ding Li; Meiling Hong (Aquatic Toxicology, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

2D/2D Bi2MoO6/CoAl LDH S-scheme heterojunction for enhanced removal of tetracycline: Performance, toxicity, and mechanism - Huiyin Ye; Yidan Luo; Shuohan Yu; Guangying Shi; Aofeng Zheng; Yong Huang; Mingshan Xue; Zuozhu Yin; Zhen Hong; Xibao Li; Xianchuan Xie; Bin Gao (Chemosphere, 2024)

Correlation analysis between the in vivo bioavailability and in vitro bioaccessibility of nitro PAHs in soil: Application of simplified FOREhST in vitro methods based on the Chinese pharmacopoeia - Xian-xian Chen; Chao Li; Krishna Kumar Selvaraj; Qing-song Ji; Zhi-hong Fang; Shao-gui Yang; Shi-yin Li; Li-min Zhang; Huan He (Science of The Total Environment, 2024)

A novel antimony metallochaperone AntC in Comamonas testosteroni JL40 and its application in antimony immobilization - Lijin An; Mingzhu Xu; Mengjuan Hong; Lipeng Zhao; Ao Wei; Xiong Luo; Kaixiang Shi; Shixue Zheng; Mingshun Li (Science of The Total Environment, 2024)

Structurally diverse rearranged sesquiterpenoids, including a pair of rare tautomers, from the aerial parts of Daphne penicillata - Peng Zhao; Ben-Song Xin; Li Ye; Zhen-Tao Ma; Guo-Dong Yao; Rui Shi; Xia-Hong He; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Introduction of soybean into maize field reduces N2O emission intensity via optimizing nitrogen source utilization - Wei Zhang; Jun-Sheng Lu; Ju Bai; Aziz Khan; Shu-Tong Liu; Ling Zhao; Wei Wang; Shuang-Guo Zhu; Xiao-Gang Li; Xiao-Hong Tian; Shi-Qing Li; You-Cai Xiong (Journal of Cleaner Production, 2024)

Investigation of cross-scale characterization of porous structure and fluid index in bituminous coal via microwave-LN2 freeze-thaw cycles - Xi Wu; He Li; Jiexin Lu; Yi Lu; Yidu Hong; Chunshan Zheng; Meng Liu; Baiquan Lin; Shiliang Shi; Zheng Wang (Fuel, 2024)

Community-level bioaugmentation results in enzymatic activity- and aroma-enhanced Daqu through altering microbial community structure and metabolic function - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (Food Bioscience, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Dual nonionic photoacids synergistically enhanced photosensitivity for chemical amplified resists - Ling-Yan Peng; Shi-Li Xiang; Jun-Dan Huang; Ying-Yi Ren; Pan Hong; Chong Li; Jun Liu; Ming-Qiang Zhu (Chemical Engineering Journal, 2024)

Potential of globally distributed topsoil mid-infrared spectral library for organic carbon estimation - Yongsheng Hong; Jonathan Sanderman; Tomislav Hengl; Songchao Chen; Nan Wang; Jie Xue; Zhiqing Zhuo; Jie Peng; Shuo Li; Yiyun Chen; Yaolin Liu; Abdul Mounem Mouazen; et al. (CATENA, 2024)

Modeling drug-induced mitochondrial toxicity with human primary cardiomyocytes - Xiaoli Tang; Hong Liu; Rongjia Rao; Yafei Huang; Mengqi Dong; Miaomiao Xu; Shanshan Feng; Xun Shi; Li Wang; Zengwu Wang; Bingying Zhou (Science China Life Sciences, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

Development of a full-scale flume test system for depositional behavior study of segregating tailings - Quanming Li; Zhijie Duan; Hai Shi; Yuzhen Yu; Hong Zhang; Botao Fu (Bulletin of Engineering Geology and the Environment, 2024)

Insight into the flame-retardant mechanism of different organic-modified layered double hydroxide for epoxy resin - Xiao-Hui Shi; Xue-Lin Li; Hong Shi; Qing-Yun Liu; Wei-Min Xie; Shi-Jie Wu; Nan Zhao; De-Yi Wang (Applied Clay Science, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Suggested method of utilizing soil arching for optimizing the design of strutted excavations - Ben-Guo He; Bo Lin; Hong-Pu Li; Shi-Qi Zhu (Tunnelling and Underground Space Technology, 2024)

Aridity drives the variability of desert soil microbiomes across north-western China - Lei Dong; Mei-Xiang Li; Shuai Li; Ling-Xiang Yue; Mukhtiar Ali; Jia-Rui Han; Wen-Hui Lian; Chao-Jian Hu; Zhi-Liang Lin; Guo-Yuan Shi; Pan-Deng Wang; Shao-Ming Gao; et al. (Science of The Total Environment, 2024)

Characteristic chromanone acids from Calophyllum membranaceum: Determination of C-3 configuration and anti-inflammatory activity - Wei Shen; Lun Li; Qing-He Liu; Jia-Min Cui; Wei Shi; Xin-Hong Shi; Xiao-Qi Zhang; Wen-Cai Ye; Xiao-Long Hu; Hao Wang (Phytochemistry, 2024)

A model of hybrid speciation process drawn from three new poplar species originating from distant hybridization between sections - Yu-Jie Shi; Jin-Liang Huang; Jia-Xuan Mi; Jing Li; Fan-Yu Meng; Yu Zhong; Fang He; Fei-Fei Tian; Fan Zhang; Liang-Hua Chen; Han-Bo Yang; Hong-Lin Hu; et al. (Molecular Phylogenetics and Evolution, 2024)

Kinetic and mechanism of the reaction between Cl and several mono-methyl branched alkanes - Yan Chen; Weigang Wang; Junling Li; Li Zhou; Bo Shi; Cici Fan; Ke Wang; Hao Zhang; Hong Li; Maofa Ge (Journal of Environmental Sciences, 2024)

Average molecular structure model of shale kerogen: Experimental characterization, structural reconstruction, and pyrolysis analysis - Kanyuan Shi; Junqing Chen; Xiongqi Pang; Fujie Jiang; Shasha Hui; Sijia Zhang; Hong Pang; Yuying Wang; Di Chen; Xiaobin Yang; Bingyao Li; Tingyu Pu (Fuel, 2024)

Aerosol optical and radiative properties and their environmental effects in China: A review - Huizheng Che; Xiangao Xia; Hujia Zhao; Lei Li; Ke Gui; Yu Zheng; Jingjing Song; Bing Qi; Jun Zhu; Yucong Miao; Yaqiang Wang; Zhili Wang; et al. (Earth-Science Reviews, 2024)

Conformational isomerization imparts low concentration dependence to multiple resonance thermally activated delayed fluorescence (MR-TADF) emitters - Hao Wu; Yi-Zhong Shi; Mo-Yuan Li; Xiao-Chun Fan; Feng Huang; Kai Wang; Jia Yu; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Chromosome-scale assembly and gene editing of Solanum americanum genome reveals the basis for thermotolerance and fruit anthocyanin composition - Shuojun Yu; Yue Wang; Tingting Li; Huazhong Shi; Dali Kong; Jia Pang; Zhiqiang Wang; Huiying Meng; Yang Gao; Xu Wang; Yechun Hong; Jian-Kang Zhu; et al. (Theoretical and Applied Genetics, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Preliminary Trial of Male to Female Sex Reversal by 17β-Estradiol in Combination with Trilostane in Spotted Scat (Scatophagus argus) - Zheng-Ting Jiang; Gang Shi; Dong-Neng Jiang; Yu Li; Yuan-Qing Huang; Hong-Juan Shi; Guang-Li Li (Fishes, 2023)
The spotted scat (Scatophagus argus) is an important ornamental species with sexually biased ornamental values that favor males. Therefore, it makes sense to breed mono-male fingerlings as ornamental fish. The spotted scat has an XX/XY sex determination system; therefore, the first step in producing genetically all-male offspring should be the induction of a fertile sex-reversed XY pseudo-female, which would then be mated with a normal XY male to produce a YY super-male. However, the XY pseudo-female produced by estradiol (E2) treatment failed due to ovarian malformations. Here, male to female sex reversal was induced in spotted scat through a combination of E2 and an androgen inhibitor (trilostane, TR). Spotted scat fingerlings of approximately 2.8–3.5 cm were fed a diet containing both E2 (300 µg/g) and TR (300 µg/g). The fish were treated for 90 days and then fed a normal diet until they reached one year of age, when they were sampled. Twenty-eight treated XY individuals were identified using sex-linked markers. According to their gonadal histological characteristics, these treated XY fish could be divided into three groups: males with testes (n = 21), intersex individuals with ovaries–testes (n = 3), and fully sex-reversed individuals with ovaries (n = 4). All treated XX fish (n = 8) developed into normal females. There were no obvious abnormalities in the ovaries of the XY sex-reversed fish compared to the treated XX fish. Serum 11-ketotestosterone (11-KT) levels were significantly lower in XY-reversed females and treated XX females than in XY males. Compared with XY male fish, the expression of female (42sp50, foxl2, figla, zar1, and zp2) and male (dmrt1, gsdf, amh and cyp11b2) biased genes was up- and down-regulated, respectively, in the gonads of XY-completely sex-reversed fish. Immunohistochemical results indicate that 42Sp50 was expressed in oocytes of XY-partially and completely sex-reversed fish, while strong Gsdf signals were mainly detectable in testicular somatic cells of XY-partially sex-reversed fish and XY male fish. XY females were successfully produced by the combined treatment of E2 and TR in the spotted scat. Their fertility will be tested in the future.

Comparative miRNA-seq analysis revealed molecular mechanisms of red color formation in the early developmental stages of Plectropomus leopardus - Xi Liu; Mouyan Jiang; Simin Wen; Kaixiang Zhang; Yucong Hong; Kaihui Sun; Xianwu Deng; Yang Huang; Gang Shi; Changxu Tian; Huapu Chen; Guangli Li; et al. (Frontiers in Marine Science, 2023)
MicroRNAs (miRNAs) are endogenous small non-coding RNAs that play important roles in several biological processes, including the regulation of body color. Leopard coral grouper ( Plectropomus leopardus ) is a valuable marine aquaculture fish; however, at present, there are no published reports on its early body color development. The skin color of P. leopardus undergoes a transition from transparent to red from 26 days post-hatching (dph) to 30 dph. In this study, we performed miRNA sequencing on 26 dph (Transparent, PT) and 30 dph (Red, PR) skin samples of P. leopardus to explore the molecular mechanism underlying red color formation. A total of 44.31 M and 37.55 M clean tags were obtained from PT and PR group, respectively. Among these tags, 981 miRNAs were identified, including 493 known and 488 novel miRNAs. A total of 106 differentially expressed miRNAs (DEMs) were identified in PT vs. PR, with 43 up-regulated and 63 down-regulated miRNAs in the PR group, compared to the PT group (|fold change| > 2 and p-value < 0.05). A miRNA-mRNA network based on 18 candidate miRNAs and 53 target genes related to pigmentation, and KEGG enrichment analysis of the target genes of all DEMs, revealed that miRNAs involved in the formation of red skin color were mainly related to: 1) the inhibition of melanin synthesis (miR-141-z, miR-206-z, miR-206-y, miR-27-z, miR-137-y, miR-204-x, miR-204-y, miR-211-x, miR-211-z); 2) chromatophore development (miR-206-z, miR-206-y, miR-499-y, miR-1-z, miR-2188-x, miR-423-x); and 3) carotenoid metabolism (miR-204-x, miR-204-y, miR-499-y). This study demonstrates the potential role of miRNAs in red color formation and lays the foundation for the molecular mechanism of body color polymorphism in P. leopardus .

Exploring the intentional unsafe behavior of workers in prefabricated construction based on structural equation modeling - Fuyi Yao; Chaofan Shi; Xiaowen Wang; Yingbo Ji; Yan Liu; Hong Xian Li (Environmental Science and Pollution Research, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Nutrient condition modulates the antibiotic tolerance of Pseudomonas aeruginosa - Huizhong Liu; Yingsi Wang; Zhiqing Zhang; Hong Qi; Yu Zhang; Wenru Li; Qingshan Shi; Xiaobao Xie (Science of The Total Environment, 2023)

Seroprevalence and potential risk factors of brucellosis in sheep from America, Africa and Asia regions: A systematic review and meta-analysis - Lian-Min Li; Qi Wang; Jun-Feng Shi; Ting Li; Bo Zhao; Qing-Xia Ma; Hong-Ying Liu; Nuo Su; Ruo-Peng Cai; Fan-Li Zeng; Qing-Long Gong; Kun Shi; et al. (Research in Veterinary Science, 2023)

Application of hydroxyethylidene diphosphonic acid as a depressant for efficient pyrite separation from serpentine: a performance and mechanistic study - Binbin Li; Dezhi Liu; Qing Shi; Guofan Zhang; Hong Zheng (Minerals Engineering, 2023)

Phase reconstruction of Co3O4 with enriched oxygen vacancies induced by cold plasma for boosting methanol-to-formate electro-oxidation - Jingsen Zhang; Yue Hua; Hong Li; Xiuling Zhang; Chuan Shi; Yuxiang Li; Lanbo Di; Zongyuan Wang (Chemical Engineering Journal, 2023)

Supramolecularly engineered S-scheme SubPc-Br/MoS2 photocatalyst nanosheets for enhanced photocatalytic degradation of antibiotics - Bing Wang; XuXia Zhang; RuiQing Zhang; Zhuo Li; Bin Tian; HaiXia Ma; Zheng Zheng; Bo Zhou; MengTing Ji; ChuanHui Shi; Hong Hao (Chemical Engineering Journal, 2023)

Engineering of formate dehydrogenase for improving conversion potential of carbon dioxide to formate - Hong-Ling Shi; Shu-Wei Yuan; Xiao-Qi Xi; Yu-Li Xie; Chao Yue; Ying-Jun Zhang; Lun-Guang Yao; Chuang Xue; Cun-Duo Tang (World Journal of Microbiology and Biotechnology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Triptolide induces PANoptosis in macrophages and causes organ injury in mice - Hong-Rui Zhang; Ya-Ping Li; Zi-Jian Shi; Qi-Qi Liang; Si-Yuan Chen; Yi-Ping You; Tao Yuan; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Apoptosis, 2023)

Machine learning framework for intelligent aeration control in wastewater treatment plants: Automatic feature engineering based on variation sliding layer - Yu-Qi Wang; Hong-Cheng Wang; Yun-Peng Song; Shi-Qing Zhou; Qiu-Ning Li; Bin Liang; Wen-Zong Liu; Yi-Wei Zhao; Ai-Jie Wang (Water Research, 2023)

Photochemistry in the urban agglomeration along the coastline of southeastern China: Pollution mechanism and control implication - Gaojie Chen; Qiao Shi; Lingling Xu; Shaocai Yu; Ziyi Lin; Xiaoting Ji; Xiaolong Fan; Youwei Hong; Mengren Li; Fuwang Zhang; Jinfang Chen; Jinsheng Chen (Science of The Total Environment, 2023)

Activation of estrogen-related receptor: An alternative mechanism of hexafluoropropylene oxide homologs estrogenic effects - Lu Chen; Xicha Lin; Sha Shi; Minjie Li; Monika Mortimer; Wendi Fang; Fangfang Li; Liang-Hong Guo (Science of The Total Environment, 2023)

Rapid identification of hazardous heavy metal-containing waste by combining EDXRF with machine learning: Taking zinc smelting waste as an example - Jing Teng; Yao Shi; Zuo-Hua Liu; Hui-Quan Li; Ming-Xing He; Zhi-Hong Li; Chen-Mu Zhang (Resources, Conservation and Recycling, 2023)

Defensive furofuran lignans localized to the oil cells of Neocinnamomum delavayi and their metabolism by a specialist insect - Min-Jie Yang; Shi-Hong Luo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

Characterizing nighttime vertical profiles of atmospheric particulate matter and ozone in a megacity of south China using unmanned aerial vehicle measurements - Zhanyong Wang; Ruhui Cao; Bai Li; Ming Cai; Zhong-Ren Peng; Guohua Zhang; Qingchang Lu; Hong-di He; Jinpu Zhang; Kai Shi; Yonghong Liu; Hui Zhang; et al. (Environmental Research, 2023)

A solution for calculating the leakage rate through GMB/CCL composite liners with long defects - Yu-Chao Li; Shi-Yuan Yao; Cheng Chen; Yun-Min Chen; Guan-Nian Chen; Ri-Hong Zhang (Computers and Geotechnics, 2023)

Photocatalytic reactive distillation - A novel process intensification approach for purification of electronic-grade silicon tetrachloride - Xiong Zhao; Zhengkun Hou; Shuhu Guo; Renze Shi; Ye Wan; Jianhua Liu; Zhenjun Yuan; Hong Li; Dazhou Yan; Xin Gao (Chemical Engineering Journal, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Fundicoccus culcitae sp. nov., a novel potential bacteriocin producing bacterium isolated from a spoiled eye mask - Gang Zhou; Lei Gao; Bao-Zhu Fang; Ying-Si Wang; Hong-Bing Tao; Xia Wen; Qian Wang; Xiao-Mo Huang; Qing-Shan Shi; Wen-Jun Li; Xiao-Bao Xie (Antonie van Leeuwenhoek, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

PoClu, a teleost Clusterin, acts as a negative regulator in complement activation and antibacterial immunity - Guan-yu Chen; Ji-xing Feng; Wen-kai Shi; Hong-ye Wang; Jian Zhang; Xue-peng Li (Aquaculture, 2023)

Clerodane diterpenoids from the Uygur medicine Salvia deserta with immunosuppressive activity - Xue Ren; Xin Yuan; Shan-Shan Jiao; Xiao-Ping He; Hong Hu; Juan-Juan Kang; Shi-Hong Luo; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

New nornemoralisin and nemoralisin diterpenoids from Aphanamixis polystachya - Yan-Wu Chen; Shi-Li Wu; Fa-Wu Dong; Hua-Yi Jiang; Hong-Ping He (Phytochemistry Letters, 2023)

Gas-pressurized torrefaction of lignocellulosic solid wastes: Low-temperature deoxygenation and chemical structure evolution mechanisms - Liu Shi; Zhenzhong Hu; Xian Li; Shuo Li; Linlin Yi; Xiaohua Wang; Hongyun Hu; Guangqian Luo; Hong Yao (Bioresource Technology, 2023)

Urolithin C reveals anti-NAFLD potential via AMPK-ferroptosis axis and modulating gut microbiota - Jingyuan Xu; Hongyang Tian; Yajun Ji; Lei Dong; Yandong Liu; Yatao Wang; Xuefen Gao; Haitao Shi; Hong Li; Longbao Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Revealing the solid-solution interface interference behaviors between Cu2+ and As(III) via partial peak area analysis of simulations and experiments - Bo Liang; Xiang-Yu Xiao; Zong-Yin Song; Yong-Yu Li; Xin Cai; Rui-Ze Xia; Shi-Hua Chen; Meng Yang; Pei-Hua Li; Chu-Hong Lin; Xing-Jiu Huang (Analytica Chimica Acta, 2023)

A generalized land surface reflectance reconstruction method for aerosol retrieval: Application to the Particulate Observing Scanning Polarimeter (POSP) onboard GaoFen-5 (02) satellite - Zheng Shi; Yisong Xie; Zhengqiang Li; Ying Zhang; Cheng Chen; Linlu Mei; Hua Xu; Haofei Wang; Yang Zheng; Zhenhai Liu; Jin Hong; Mengyao Zhu; et al. (Remote Sensing of Environment, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Risk assessment of unmanned underwater platforms in the South China Sea marine environment based on two-dimensional density-weighted operator and cloud barycentric Bayesian combination - Zilong Guo; Mei Hong; Jian Shi; Yongchui Zhang; Longxia Qian; Hanlin Li (Ocean Engineering, 2023)

Impact of paclobutrazol on storage root number and yield of sweet potato (Ipomoea batatas L.) - Cheng-cheng Si; Yu-jie Li; Hong-Juan Liu; Hai-yan Zhang; Ya-yi Meng; Ning Wang; Chun-yu Shi (Field Crops Research, 2023)

Self-assembled synthesis of Pd/SPEn from polyelectrolyte membranes for efficient direct synthesis of H2O2 via inhibiting the dissociation of O − O bond - Entong Ye; Zheng Chen; Yongyong Shi; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Quansheng Wu; Qian Lin; Hongyan Pan; Keliang Wang (Chemical Engineering Journal, 2023)

An intron-located single nucleotide variation of TaGS5-3D is related to wheat grain size through accumulating intron retention transcripts - Yaoyuan Zhang; Hanxiao Miao; Yi Xiao; Chao Wang; Junjie Zhang; Xiaoxi Shi; Songfeng Xie; Changyou Wang; Tingdong Li; Pingchuan Deng; Chunhuan Chen; Hong Zhang; et al. (Theoretical and Applied Genetics, 2023)

The induction of ferroptosis by KLF11/NCOA4 axis: the inhibitory role in clear cell renal cell carcinoma - Zi-Qi Zhou; Xi Lv; Shi-Bo Liu; Hong-Chen Qu; Qing-Peng Xie; Long-Feng Sun; Gang Li (Human Cell, 2023)

Heterologous expression, fermentation strategies and molecular modification of collagen for versatile applications - Zhi-Xiang Xiang; Jin-Song Gong; Heng Li; Wei-Ting Shi; Min Jiang; Zheng-Hong Xu; Jin-Song Shi (Critical Reviews in Food Science and Nutrition, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Reduced dietary Ca, Cu, Zn, Mn, and Mg bioavailability but increased Fe bioavailability with polyethylene microplastic ingestion in a mouse model: Changes in intestinal permeability and gut metabolites - Shan Chen; Shi-Wei Li; Xue-Yuan Gu; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Science of The Total Environment, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Martynoside rescues 5-fluorouracil-impaired ribosome biogenesis by stabilizing RPL27A - Mengying Hong; Yushen Du; Dongdong Chen; Yuan Shi; Menglong Hu; Kejun Tang; Zhuping Hong; Xiangzhi Meng; Wan Xu; Gaoqi Wu; Yuanyuan Yao; Liubo Chen; et al. (Science Bulletin, 2023)

A complete assembly of the rice Nipponbare reference genome - Lianguang Shang; Wenchuang He; Tianyi Wang; Yingxue Yang; Qiang Xu; Xianjia Zhao; Longbo Yang; Hong Zhang; Xiaoxia Li; Yang Lv; Wu Chen; Shuo Cao; et al. (Molecular Plant, 2023)

Nanographite-assisted matrix solid phase dispersion microextraction of active and toxic compounds from complex food matrices using cyclodextrin aqueous solution as elution solvent - Si-Chen Zhu; Ying Shi; Huang-Fei Jin; Jun Cao; Li-Hong Ye (Food Chemistry, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

A study on the analysis of dynamical transmission behavior and mining key monitoring stations in PM and O3 networks in the Beijing-Tianjin-Hebei region of China - Xiaofei Shi; Bo Li; Donglei Fu; Jiao Bai; Stephen Dauda Yabo; Kun Wang; Xiaoxiao Gao; Jie Ding; Hong Qi (Environmental Research, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Health Risk Assessment of Organophosphate Flame Retardants in Soil Across China Based on Monte Carlo Simulation - Mei-Hong Chen; Shi-Ming Jia; Pu-Fei Yang; Fu-Jie Zhu; Wan-Li Ma (Archives of Environmental Contamination and Toxicology, 2023)

Loss of swallow tail sign on susceptibility-weighted imaging in neurosyphilis mimicking Alzheimer’s disease: a case report - Xiao-Li Cui; Shen Liu; Yi-Ming Zhang; Hong-Dong Zhao; Jian-Quan Shi (Acta Neurologica Belgica, 2023)

High adsorption performance for trace lead (II) cation from sewage by Fe/Cu metal organic nanosheets modified with terephthalic acid - Xiaofeng Shi; Lingshu Gao; Eman Alzahrani; Junmao Hong; Abdullah K. Alanazi; Hala M. Abo-Dief; Junhua Li; Ben Bin Xu; Hassan Algadi; Zeinhom M. El-Bahy; Zhanhu Guo (Chemosphere, 2023)

Delineation and optimization of cotton farmland management zone based on time series of soil-crop properties at landscape scale in south Xinjiang, China - Nan Wang; Dongyun Xu; Jie Xue; Xianglin Zhang; Yongsheng Hong; Jie Peng; Hongyi Li; Abdul Mounem Mouazen; Yong He; Zhou Shi (Soil and Tillage Research, 2023)

Santalane-type sesquiterpenoids and isobenzofuranones from cultures of Paraconiothyrium sporulosum YK-03 - Li-Hua Zhang; Wen-Ke Gao; Shi-Wei Li; Xiao-Yan Song; Hong-Hua Wu; Hai-Feng Wang; Gang Chen; Shao-Xia Wang; Yue-Hu Pei (Phytochemistry, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Characterizing thermo-hydraulic behaviors of seasonally frozen loess via a combined opto-electronic sensing system: Field monitoring and assessment - Hong-Hu Zhu; Bing Wu; Ding-Feng Cao; Biao Li; Zhi Wen; Xi-Feng Liu; Bin Shi (Journal of Hydrology, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Growth of spiral ganglion neurons induced by graphene oxide/oxidized bacterial cellulose composite hydrogel - Lin Shi; Guodong Hong; Chuntao Chen; Xueqian Li; Heng Zhang; Renjie Chai; Dongping Sun (Carbohydrate Polymers, 2023)

Evaluation of the treatment effect of rear slope cutting on hydrodynamic pressure landslides: A case study - Li Wang; Jun-jie Huang; Yong Chen; Shi-mei Wang; Zhi-hong Fan; Fei Guo; Xiao-wei Li (Journal of Mountain Science, 2023)

Effects of endogenous capsaicin stress and fermentation time on the microbial succession and flavor compounds of chili paste (a Chinese fermented chili pepper) - Qiao Shi; Huihua Tang; Yuan Mei; Junfei Chen; Xinrui Wang; Biqin Liu; Yingli Cai; Nan Zhao; Menglu Yang; Hong Li (Food Research International, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Identification and validation of new MADS-box homologous genes in 3010 rice pan-genome - Weihua Li; Duoxiang Wang; Xiaokun Hong; Jin Shi; Jun Hong; Su Su; Cristopher Reyes Loaiciga; Jing Li; Wanqi Liang; Jianxin Shi; Dabing Zhang (Plant Cell Reports, 2023)

NLRP7 participates in the human subcortical maternal complex and its variants cause female infertility characterized by early embryo arrest - Jian Han; Nana Zhang; Qiqi Cao; Xiaodan Shi; Congjing Wang; Ximan Rui; Jie Ding; Chun Zhao; Junqiang Zhang; Xiufeng Ling; Hong Li; Yichun Guan; et al. (Journal of Molecular Medicine, 2023)

Vancomycin Pretreatment on MPTP-Induced Parkinson’s Disease Mice Exerts Neuroprotection by Suppressing Inflammation Both in Brain and Gut - Chun Cui; Hui Hong; Yun Shi; Yu Zhou; Chen-Meng Qiao; Wei-Jiang Zhao; Li-Ping Zhao; Jian Wu; Wei Quan; Gu-Yu Niu; Yi-Bo Wu; Chao-Sheng Li; et al. (Journal of Neuroimmune Pharmacology, 2023)

Sediment sources and their impacts on a check dam-controlled watershed, Loess Plateau, China - Lu-lu Bai; Peng Shi; Wen Wang; Zhan-bin Li; Kun-xia Yu; Peng Li; Ling-zhou Cui; Rong-jian Shen; Mu-hong Guan; Xin-chun Du; Xun-le Zhang; Wen-fu Chen (Journal of Mountain Science, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Simultaneous detection and phylogenetic analysis of porcine epidemic diarrhea virus and porcine circovirus 4 in Henan province, China - Hong-Xuan Li; Xi-Meng Chen; You-Yi Zhao; Hong-Lei Zhang; Lan-Lan Zheng; Lin-Qing Wang; Shi-jie Ma; Hong-Ying Chen (Archives of Virology, 2023)

The whole-cell proteome shows the characteristics of macrolides-resistant Bordetella pertussis in China linked to the biofilm formation - Zhe Lv; Sha Yin; Kaichong Jiang; Wei Wang; Yang Luan; Shuang Wu; Jianfei Shi; Zhe Li; Xiao Ma; Zengguo Wang; Hong Yan (Archives of Microbiology, 2023)
The macrolides-resistant Bordetella pertussis (MR- Bp ) isolates in China evolved from the ptxP1/fhaB3 allele and rapidly became predominant, suggestive of an adaptive transmission ability. This was different from the global prevalent ptxP3 strains, in which MR- Bp was rarely reported. The study aimed to determine the underlying mechanism responsible for fitness and resistance in these two strains. We identify proteomic differences between ptxP1/fhaB3 and ptxP3/fhaB1 strains using tandem mass tag (TMT)-based proteomics. We then performed in-depth bioinformatic analysis to determine differentially expressed genes (DEGs), followed by gene ontology (GO), and protein–protein interaction (PPI) network analysis. Further parallel reaction monitoring (PRM) analysis confirmed the expression of four target proteins. Finally, the crystal violet method was used to determine biofilm-forming ability. The results showed that the main significantly different proteins between the two represent isolates were related to biofilm formation. Furthermore, we have confirmed that ptxP1/fhaB3 showed hyperbiofilm formation in comparison with ptxP3/fhaB1 . It is suggested that the resistance and adaptability of ptxP1/fhaB3 strains may be related to the formation of biofilm through proteomics. In a word, we determined the significantly different proteins between the ptxP1/fhaB3 and ptxP3/fhaB1 strains through whole-cell proteome, which were related to biofilm formation.

Isolation and characterization of three pairs of verrucosidin epimers from the marine sediment-derived fungus Penicillium cyclopium and configuration revision of penicyrone A and related analogues - Yan-He Li; Attila Mándi; Hong-Lei Li; Xiao-Ming Li; Xin Li; Ling-Hong Meng; Sui-Qun Yang; Xiao-Shan Shi; Tibor Kurtán; Bin-Gui Wang (Marine Life Science & Technology, 2023)
Verrucosidins, a methylated α-pyrone class of polyketides rarely reported upon, have been implicated in one or more neurological diseases. Despite the significance of verrucosidins as neurotoxins, the absolute configurations of most of the derivatives have not been accurately characterized yet. In this study, three pairs of C-9 epimeric verrucosidin derivatives, including the known compounds penicyrones A and B ( 1a/1b ) and 9- O -methylpenicyrones A and B ( 2a/2b ), the new compounds 9- O- ethylpenicyrones A and B ( 3a/3b ), together with the related known derivative verrucosidin ( 4 ), were isolated and identified from the culture extract of Penicillium cyclopium SD-413, which was obtained from the marine sediment collected from the East China sea. Their structures were established based on an in-depth analysis of nuclear magnetic resonances (NMR) and mass spectroscopic data. Determination of the absolute configurations of these compounds was accomplished by Mosher’s method and time-dependent density functional theory (TDDFT) calculations of electronic circular dichroism (ECD) and optical rotation (OR). The configurational assignment of penicyrone A demonstrated that the previously reported C-6 absolute configuration of verrucosidin derivatives needs to be revised from (6 S ) to (6 R ). The 9 R /9 S epimers of compounds 1–3 were found to exhibit growth inhibition against some pathogenic bacteria, indicating that they have potential as lead compounds for the creation of antimicrobial agents.

Relative importance of ENSO and IOD on interannual variability of Indonesian Throughflow transport - Aojie Li; Yongchui Zhang; Mei Hong; Jian Shi; Jing Wang (Frontiers in Marine Science, 2023)
Introduction The Indonesian Throughflow (ITF) connects the Pacific Ocean and the Indian Ocean. It plays an important role in the global ocean circulation system. The interannual variability of ITF transport is largely modulated by climate modes, such as Central-Pacific (CP) and Eastern-Pacific (EP) El Niño and Indian Ocean Dipole (IOD). However, the relative importance of these climate modes importing on the ITF is not well clarified. Methods Dominant roles of the climate modes on ITF in specific periods are quantified by combining a machine learning algorithm of the random forest (RF) model with a variety of reanalysis datasets. Results The results reveal that during the period from 1993 to 2019, the average ITF transport derived from high-resolution reanalysis datasets is -14.97 Sv with an intensification trend of -0.06 Sv year -1 , which mainly occurred in the upper layer. Four periods, which are 1993–2000, 2002–2008, 2009–2012 and 2013–2019, are identified as Niño 3.4, Dipole Mode Index (DMI), no significant dominant index, and DMI dominated, respectively. Discussion The corresponding sea surface height differences between the Northwest Tropical Pacific Ocean (NWP) and Southeast Indian Ocean (SEI) in these three periods when exist dominant index are -0.50 cm, 0.99 cm and -3.22 cm, respectively, which are responsible for the dominance of the climate modes. The study provides a new insight to quantify the response of ITF transport to climate drivers.

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Dietary aromatase inhibitor treatment converts XY gsdf homozygous mutants to sub-fertile male in Nile tilapia (Oreochromis niloticus) - Sen Fan; Hong-Juan Shi; You-Xing Peng; Yuan-Qing Huang; Mou-Yan Jiang; Guang-Li Li; De-Shou Wang; Dong-Neng Jiang (Aquaculture, 2023)

Detecting pipeline leakage using active distributed temperature Sensing: Theoretical modeling and experimental verification - Hao-Jie Li; Hong-Hu Zhu; Dao-Yuan Tan; Bin Shi; Jian-Hua Yin (Tunnelling and Underground Space Technology, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

The importance of moisture in regulating soil organic carbon content based on a comparison of “enzymic latch” and “iron gate” in Zoige Plateau peatland - Ruixuan Li; Hanqing Luo; Jianlan Yu; Ling Luo; Yan He; Shihuai Deng; Ouping Deng; Dezhi Shi; Jinsong He; Hong Xiao; Lilin Wang; Ting Lan (CATENA, 2023)

APETALA2 is involved in ABA signaling during seed germination - Huiying Meng; Yunjuan Chen; Tingting Li; Huazhong Shi; Shuojun Yu; Yang Gao; Zhiqiang Wang; Xu Wang; Jian-Kang Zhu; Yechun Hong; Zhen Wang (Plant Molecular Biology, 2023)

Mitoquinone protects against acetaminophen-induced liver injury in an FSP1-dependent and GPX4-independent manner - Xue He; Shi-Min Liang; Hong-Qian Wang; Li Tao; Fei-Fei Sun; Yan Wang; Cheng Zhang; Yi-Chao Huang; De-Xiang Xu; Xi Chen (Toxicology and Applied Pharmacology, 2023)

Genomic insights into the genetic basis of cotton breeding in China - Yiqian Li; Zhanfeng Si; Guoping Wang; Zhuolin Shi; Jinwen Chen; Guoan Qi; Shangkun Jin; Zegang Han; Wenhao Gao; Yue Tian; Yun Mao; Lei Fang; et al. (Molecular Plant, 2023)

Seasonal effects on pilot-scale high-concentration activated sludge systems in cold regions - Xueying Shi; Wenai Liu; Zebing Nie; Qingzhe Li; Xin Liang; Wanli Zhao; Hong Qu; Dejun Bian (Journal of Water Process Engineering, 2023)

Efficient degradation of tetracycline by a novel nanoconfinement structure Cu2O/Cu@MXene composite - Qianqian Zhou; Peidong Hong; Xu Shi; Yulian Li; Ke Yao; Wanqi Zhang; Chengming Wang; Junyong He; Kaisheng Zhang; Lingtao Kong (Journal of Hazardous Materials, 2023)

Bacteria and filamentous fungi running a relay race in Daqu fermentation enable macromolecular degradation and flavor substance formation - Wen-Hu Liu; Li-Juan Chai; Hong-Mei Wang; Zhen-Ming Lu; Xiao-Juan Zhang; Chen Xiao; Song-Tao Wang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2023)

Understanding the inter-city causality and regional transport of atmospheric PM2.5 pollution in winter in the Harbin-Changchun megalopolis in China: A perspective from local and regional - Bo Li; Xiaofei Shi; Jinpan Jiang; Lu Lu; Li-xin Ma; Wei Zhang; Kun Wang; Hong Qi (Environmental Research, 2023)

MXene-containing anisotropic hydrogels strain sensors with enhanced sensing performance for human motion monitoring and wireless transmission - Bingyan Guo; Shaoshuai He; Mengmeng Yao; Zhouying Tan; Xi Li; Min Liu; Chaojie Yu; Lei Liang; Zhongming Zhao; Zhicheng Guo; Mingyue Shi; Yuping Wei; et al. (Chemical Engineering Journal, 2023)

High-titer production of myo-inositol by a co-immobilized four-enzyme cocktail in biomimetic mineralized microcapsules - Pingping Han; Chun You; Yunjie Li; Ting Shi; Hong Wu; Yi-Heng P. Job Zhang (Chemical Engineering Journal, 2023)

Deciphering the fate of osmotic stress priming on enhanced microorganism acclimation for purified terephthalic acid wastewater treatment with high salinity and organic load - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Bioresource Technology, 2023)

Variations of chemical composition of NR-PM1 under the influence of sea land breeze in a coastal city of Southeast China - Yuping Chen; Chen Yang; Lingling Xu; Xiaolong Fan; Jiayan Shi; Ronghua Zheng; Youwei Hong; Mengren Li; Taotao Liu; Gaojie Chen; Liqian Yin; Jinsheng Chen (Atmospheric Research, 2023)

Drivers of 2015–2021 trends in cold winter surface PM2.5 in the Harbin-Changchun megalopolis in China: Meteorology vs. anthropogenic emission - Bo Li; Lu Lu; Xiaofei Shi; Lixin Ma; Jin-Pan Jiang; Stephen Dauda Yabo; Kun Wang; Hong Qi (Atmospheric Research, 2023)

LncRNA GNAS-AS1 knockdown inhibits keloid cells growth by mediating the miR-188-5p/RUNX2 axis - Yun Liu; Lei Li; Jia-Yao Wang; Fei Gao; Xia Lin; Shi-Shuai Lin; Zhi-Yang Qiu; Zun-Hong Liang (Molecular and Cellular Biochemistry, 2023)

Environmental Isotopes and Cl/Br Ratios Evidences for Delineating Arsenic Mobilization in Aquifer System of the Jianghan Plain, Central China - Yu Zhang; Qian Yu; Chongwen Shi; Ping Li; Hong Niu (Journal of Earth Science, 2023)

Synergistic interactions of fine particles and radiative effects in modulating urban heat islands during winter haze event in a cold megacity of Northeast China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Lixin Ma; Xiaofei Shi; Lu Lu; Xie Shengjin; Fan Meng; Jinpan Jiang; Wei Zhang; Hong Qi (Environmental Science and Pollution Research, 2023)

Ecotoxicity stress and bioaccumulation in Eisenia fetida earthworms exposed to vanadium pentoxide in soil - Shi-qing Zhao; Hong Ni; Ji Li; Shun-hao Ai; Xiao-nan Wang; Xiang-yun Gao; Qian-yun Xu; Zheng-tao Liu (Environmental Science and Pollution Research, 2023)

Influence mechanism of organic matter and low-molecular-weight organic acids on the interaction between minerals and PAHs - Longmiao Yuan; Yingqin Wu; Qiaohui Fan; Ping Li; Jianjun Liang; Yan hong Liu; Rong Ma; Ruijie Li; LeiPing Shi (Science of The Total Environment, 2023)

New insight into enhanced transport of multi-component porous covalent-organic polymers with alkyl chains as injection agents for levofloxacin removal in saturated sand columns - Aiyuan Jia; Yongsheng Zhao; Zhi Liu; Fangyuan Zhang; Can Shi; Zhisheng Liu; Mei Hong; Yangxue Li (Science of The Total Environment, 2023)

Evaluation the food safety of cultured fat via detection of residues of adipogenic differentiation cocktail in cultured fat with high performance liquid chromatography and enzyme-linked immunosorbent assay - Wen-Juan Song; Pei-Pei Liu; Chun-Bao Li; Hui- Xia Li; Shi- Jie Ding; Guang-Hong Zhou (Food Research International, 2023)

Concomitant oxidation of fatty acids other than DHA and EPA plays a role in the characteristic off-odor of fish oil - Yun-Qi Wen; Chang-Hu Xue; Hong-Wei Zhang; Li-Li Xu; Xiao-Han Wang; Shi-Jie Bi; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Interaction and phase behavior of whey protein and propylene glycol alginate complex condensates - Ge Shi; Ce Shi; Yongkang Luo; Hui Hong; Jiaran Zhang; Yan Li; Yuqing Tan (Food Chemistry, 2023)

The compositional characteristics, influencing factors, effects on wine quality and relevant analytical methods of wine polysaccharides: A review - Hong-Yue Zhai; Si-Yu Li; Xu Zhao; Yi-Bin Lan; Xin-Ke Zhang; Ying Shi; Chang-Qing Duan (Food Chemistry, 2023)

Why did air quality experience little improvement during the COVID-19 lockdown in megacities, northeast China? - Donglei Fu; Xiaofei Shi; Jinxiang Zuo; Stephen Dauda Yabo; Jixiang Li; Bo Li; Haizhi Li; Lu Lu; Bo Tang; Hong Qi; Jianmin Ma (Environmental Research, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Enhancing intercity transportation will improve the equitable distribution of high-quality health care in China - Han Zhang; Bing-Bing Zhou; Shuwen Liu; Guohua Hu; Xing Meng; Xiaojuan Liu; Hong Shi; Yukun Gao; Haiyan Hou; Xia Li (Applied Geography, 2023)

High-resolution distribution and emission of dimethyl sulfide and its relationship with pCO2 in the Northwest Pacific Ocean - Shi-Bo Yan; Xiao-Jun Li; Feng Xu; Hong-Hai Zhang; Jian Wang; Yueqi Zhang; Gui-Peng Yang; Guang-Chao Zhuang; Zhaohui Chen (Frontiers in Marine Science, 2023)
Ocean-derived dimethyl sulfide (DMS) is widely concerning because of its hypothesized influence on global climate change. This study aims to explore the distribution characteristics and influencing factors of DMS and partial pressure of carbon dioxide ( p CO 2 ) in the Northwest Pacific Ocean, as well as the potential relationship between DMS and p CO 2 . A high-resolution, underway, shipboard measurement device was used to determine the DMS and p CO 2 of the surface seawater and atmosphere in the Northwest Pacific and its marginal seas during November 2019. The result show that atmospheric and surface seawater DMS concentrations ranged from 3 to 125 pptv and 0.63 to 2.28 nmol L -1 , respectively, with mean values of 46 ± 19 pptv and 1.08 ± 0.34 nmol L -1 . The average sea surface p CO 2 was 371 ± 16 μatm (range from 332 to 401 μatm). The trends in the surface seawater DMS in different current systems were primarily associated with phytoplankton abundance and composition. Biological activity and physical processes such as cooling jointly influenced the sea surface p CO 2 . A cold eddy along the transect in the Northwest Pacific Ocean increased DMS at the sea surface by 10% and CO 2 uptake by 3%. We found a significant negative correlation between DMS and p CO 2 in the Northwest Pacific Ocean at the 0.1° resolution [DMS] seawater = -0.0161[ p CO 2 ] seawater + 7.046 (R 2 = 0.569, P < 0.01). The DMS and p CO 2 sea-air fluxes were estimated to range from 0.04 to 25.3 μmol m -2 ·d -1 and from -27.0 to 4.22 mmol m -2 ·d -1 throughout the survey area. The Northwest Pacific Ocean, especially the Oyashio Current, is an important sink of CO 2 and a source of DMS.

The study on the main mode of the death of red blood cells in grass carp (Ctenopharyngodon idella) - Hong Chen; Minshan Yao; Ying Tang; Lixiang Wei; Junyan Lin; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

Study on the regulatory mechanism of erythropoietin in erythropoiesis in grass carp (Ctenopharyngodon idella) - Junyan Lin; Lixiang Wei; Minshan Yao; Hong Chen; Ying Tang; Fei Shi; Fanbin Zhan; Yanan Li; Jun Li; Li Lin; Zhendong Qin (Aquaculture, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Labdane diterpenoids from the heartwood of Leucosceptrum canum that impact on root growth and seed germination of Arabidopsis thaliana - Yan Liu; Yan-Ying Zhou; Shi-Hong Luo; Kai Guo; Man-Wen Zhang; Shu-Xi Jing; Chun-Huan Li; Juan Hua; Sheng-Hong Li (Phytochemistry, 2023)

Comparative chemical and non-contact bioleaching of ion-adsorption type rare earth ore using ammonium sulfate and metabolites of Aspergillus niger and Yarrowia lipolytica to rationalise the role of organic acids for sustainable processing - Li Shen; Hao Zhou; Qiyuan Shi; Xiaoyu Meng; Yu Zhao; Guanzhou Qiu; Xigang Zhang; Hong Yu; Xiao He; Huajin He; Hongbo Zhao (Hydrometallurgy, 2023)

Efficient liquefaction of Kraft lignin over N-doped carbon supported size-controlled MoC nanoparticles in supercritical ethanol - Chang Li; Hong Li; Yishuang Wang; Zhiyuan Tang; Jingjing Shi; Mingqiang Chen (Fuel, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

Predicting ozone formation in petrochemical industrialized Lanzhou city by interpretable ensemble machine learning - Li Wang; Yuan Zhao; Jinsen Shi; Jianmin Ma; Xiaoyue Liu; Dongliang Han; Hong Gao; Tao Huang (Environmental Pollution, 2023)

UV pretreatment reduced biofouling of ultrafiltration and controlled opportunistic pathogens in secondary water supply systems - Haibo Wang; Haotian Hu; Susu Chen; Cory Schwarz; Hong Yin; Chisheng Hu; Guiwei Li; Baoyou Shi; Jingang Huang (Desalination, 2023)

A robust protein-peptide co-assembling nanoformulation (PePCAN) platform with significant cell-entry characteristics for targeted cancer therapy - Xiaoyuan Zhao; Xiang Li; Bo Li; Yao Sun; Yejiao Shi; Huaxing Shen; Fan Wang; Jingjing Li; Farukh Sharopov; Zainiddin Mukhiddinov; Chao Ma; Kai Liu; et al. (Chemical Engineering Journal, 2023)

Acinetobacter baumannii reinforces the pathogenesis by promoting IL-17 production in a mouse pneumonia model - Yangyang Zhou; Chuanying Xiang; Ning Wang; Xiaomin Zhang; Yu Xie; Hong Yang; Gang Guo; Kaiyun Liu; Yan Li; Yun Shi (Medical Microbiology and Immunology, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Variation of lead bioaccessibility in soil reference materials: Intra- and inter-laboratory assessments - Xiaoyue Huang; Minghui Chang; Lei Han; Jie Li; Shi-Wei Li; Hong-Bo Li (Chemosphere, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

Temperature-regulated and starvation-induced refractory para-toluic acid anaerobic biotransformation - Xiao-chen Ma; Ke Wang; Xin-lei Gao; Xiang-kun Li; Gai-ge Liu; Hong-ying Chen; Chen-yu Piao; Shi-jie You (Chemosphere, 2023)

Insight on the heterogeneously activated H2O2 with goethite under visible light for cefradine degradation: pH dependence and photoassisted effect - Yan Shi; Shaoming Hong; Ruiping Li; Biying Luo; Huaiyong Zhu; Yingping Huang (Chemosphere, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Multi-index assessment of heavy metal contamination in surface sediments of the Pearl River estuary intertidal zone - Rui-Ze Liang; Yang-Guang Gu; Hai-Song Li; Yan-Jie Han; Jie Niu; Hong Su; Richard W. Jordan; Xiang-Tian Man; Shi-Jun Jiang (Marine Pollution Bulletin, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L - Shi-Wei Li; Bian-Xia Xue; Tian-Tian Yang; Ran Li; Mingjie Zhang; Miao Wang; Li-Hua Zhang; Peng Zhang; Yi Zhang; Tao Wang; Shao-Xia Wang; Hong-Hua Wu (Phytochemistry, 2023)

Iridoids and sesquiterpenoids from Valeriana officinalis and their bioactivities - Dao-Qun Shi; Jia-Jin Liu; Yu-Mei Feng; Yan Zhou; Cai-Cen Liao; Dan Liu; Rong-Tao Li; Hong-Mei Li (Phytochemistry, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Oxidation affects dye binding of myofibrillar proteins via alteration in net charges mediated by a reduction in isoelectric point - Qingqing Yu; Tong Shi; Zhiyu Xiong; Li Yuan; Hui Hong; Ruichang Gao; Yulong Bao (Food Research International, 2023)

A chemometric study on the identification of 5-methylfurfural and 2-acetylfuran as particular volatile compounds of oxidized fish oil based on SHS-GC-IMS - Yun-Qi Wen; Hong-Wei Zhang; Chang-Hu Xue; Xiao-Han Wang; Shi-Jie Bi; Li-Li Xu; Qian-Qian Xue; Yong Xue; Zhao-Jie Li; Joaquín Velasco; Xiao-Ming Jiang (Food Chemistry, 2023)

Gut microbiota and metabolic profile as affected by Maillard reaction products derived from bighead carp meat hydrolysates with galactose and galacto-oligosaccharides during in vitro pig fecal fermentation - Yifan Liang; Huijuan Zhang; Li Tian; Ce Shi; Yanyan Zheng; Jinfeng Wang; Yuqing Tan; Yongkang Luo; Hui Hong (Food Chemistry, 2023)

Numerical studies of the tilting of mesoscale eddies: The effects of rotation and stratification - Hong Li; Fanghua Xu; Guihua Wang; Ruizi Shi (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

From the perspective of high-throughput recognition: Sulfur quantum dots-based multi-channel sensing platform for metal ions detection - Zhe Sun; Huan Huan Xing; Min Qing; Yan Shi; Yu Ling; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Graphene induced structure and doping level tuning of evaporated CsPbBr3 on different substrates - Zhaorui Wen; Yunlei Zhong; Bingchen He; Gang Wang; Shengwen Li; Zhen Mu; Jielei Li; Junpeng Xie; Yi Zheng; Guichuan Xing; Guo Hong; Shi Chen (Chemical Engineering Journal, 2023)

Spraying EPDM@NPs as an efficient strategy for polyethylene-based high-voltage insulation - Fan-Bo Meng; Xiangrong Chen; Yiwen Shi; Zelin Hong; Hanshan Zhu; Awais Muhammad; Hao Li; Ashish Paramane (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Resistance of QYm.nau-2D to wheat yellow mosaic virus was derived from an alien introgression into common wheat - Yiming Chen; Jialun Ji; Dehui Kong; Xiong Tang; Mingxing Wen; Guoqing Wang; Keli Dai; Peiyao Shi; Xu Zhang; Huajian Zhang; Chengzhi Jiao; Zongkuan Wang; et al. (Theoretical and Applied Genetics, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Protein Arginine Methyltransferase 5 Is Necessary for Embryonic Development in Medaka Oryzias latipes - Xiaoting Liang; Shi Duan; Qing Yang; Xiaoqin Ma; Zhenyu Li; Qiting Yao; Kongyue Wu; Pei Chang; Gongqing Feng; Wentao Hong; Mengxi Cao; Qingchun Zhou; et al. (Fishes, 2022)
Protein arginine methyltransferase 5 (Prmt5), conserved from yeast to humans, catalyzes arginine’s dimethylation in proteins. Prmt5 is necessary for embryonic development in mice because it maintains embryonic stem cells. However, the embryos of zebrafish (Danio rerio) remain viable with a deficiency in germ cells and sexual development after the knockout of prmt5. Therefore, it was considered whether prmt5 is dispensable during embryogenesis in fish. Medaka (Oryzias latipes), another model fish organism, was used in this experiment. The medaka prmt5 was mutated with Transcription Activator-Like Effector Nucleases (TALEN) causing the premature stopping of transcription. None of the homozygous prmt5 mutant fish were viable, only the heterozygous offspring survived. Quantitative reverse transcription-polymerase chain reaction (qPCR) results showed a significant decrease in octamer-binding transcription factor 4 (oct4), homeobox transcription factor nanog (nanog), vasa, B-cell CLL/lymphoma 2 (bcl2), and the ratio of bcl2 to bax (bcl2 associated x), and a significant increase in caspase3 and caspase8 in the embryos of the heterozygous prmt5 mutant compared with that of the wild type. The results showed that the mutation of prmt5 caused down-regulation of the genes functioning in stemness and up-regulation of the genes in the cascade of cell death. These results suggested that prmt5 is necessary for embryogenesis via maintaining stemness and repressing apoptosis in medaka.

Magnetic Plug Sensor with Bridge Nonlinear Correction Circuit for Oil Condition Monitoring of Marine Machinery - Yuwei Zhang; Jiaju Hong; Haotian Shi; Yucai Xie; Hongpeng Zhang; Shuyao Zhang; Wei Li; Haiquan Chen (Journal of Marine Science and Engineering, 2022)
Diesel engines in marine power systems often work in extreme environments. Oil monitoring technology can guarantee the operational safety of diesel engines. In this paper, a magnetic plug sensor for oil debris monitoring is proposed to improve sensitivity and accuracy. Through finite element analysis, absolute deviation is reduced by optimizing the sensor structure. A bridge nonlinear correction circuit is designed to make sensitivity consistent over the entire scale range, which can facilitate calibration and data processing. In order to reduce noise and amplify the signal effectively, a signal post-processing circuit is adopted as well, which consists of a first stage filter circuit, a second stage filter, an active filter module, and an instrumentation amplifier. Therefore, this magnetic plug sensor exhibits better sensitivity and accuracy. Furthermore, a void test and a dynamic test are carried out to investigate its performance. There is a linear relationship between the voltage and the particle mass for the sensor with a bridge nonlinear correction circuit. The results illustrate a minimum of 0.033 mg iron debris with a 1.647 signal-to-noise ratio. Additionally, it can capture and detect 47 μm particles with a debris capture rate of over 90%, which allows it to excel in early fault diagnosis as well.

Effect and Mechanism of Cotrimoxazole Against Talaromyces marneffei in vitro - Jie Chen; Rongfeng Chen; Wudi Wei; Fengxiang Qin; Xiu Chen; Jinhao He; Hong Zhang; Gang Wang; Minjuan Shi; Tongxue Qin; Yinlu Liao; Yuting Wu; et al. (Mycopathologia, 2022)

Effect of gravel content on the detachment of colluvial deposits in Benggang - Li-ting Zhang; Fang Shuai; Li-bo Chen; Yan-he Huang; Jin-shi Lin; Yue Zhang; Hong-li Ge; Fang-shi Jiang (Journal of Mountain Science, 2022)

Model tests on horizontal load-bearing and deformation resistance capacities of pile-bucket foundation in soft seabed soil - Ben He; Zhi-ying Yuan; Zhen-qiang Jiang; Ding-yu Ni; Li Shi; Zong-hao Yuan; Hong-lei Sun (Marine Georesources & Geotechnology, 2022)

Comparative Methylome Analysis Reveals Epigenetic Signatures Associated with Growth and Shell Color in the Pacific Oyster, Crassostrea gigas - Chao Tan; Chenyu Shi; Yin Li; Wen Teng; Yongjing Li; Huiru Fu; Liting Ren; Hong Yu; Qi Li; Shikai Liu (Marine Biotechnology, 2022)

Differences in small-world networks between methamphetamine and heroin use disorder patients and their relationship with psychiatric symptoms - Yan Liu; Qiang Li; Tianyi Zhang; Lei Wang; Yarong Wang; Jiajie Chen; Jia Zhu; Hong Shi; Wei Wang; Wei Li (Brain Imaging and Behavior, 2022)

A novel irinotecan derivative ZBH-1207 with different anti-tumor mechanism from CPT-11 against colon cancer cells - Dawei Zhao; Di Wu; Gengyue Zhang; Yongqi Li; Weiguo Shi; Bohua Zhong; Hong Yu (Molecular Biology Reports, 2022)

Molecular detection of spotted fever group rickettsiae in hedgehogs (Erinaceus amurensis) and hedgehog-attached ticks in Xuyi County, Southeast China - Changqiang Zhu; Lele Ai; Yong Qi; Yunsheng Liu; Hong Li; Fuqiang Ye; Qiuwei Wang; Yizhe Luo; Weilong Tan; Chunmeng Shi (Experimental and Applied Acarology, 2022)
Tick-borne diseases like Rickettsia , Anaplasma and Ehrlichia are widespread infectious zoonoses that threaten the health of both humans and animals worldwide. Ticks and their hosts, such as hedgehogs, can play a crucial role in transmitting tick-borne diseases and the cycle of Rickettsia . To investigate the presence and identity of Rickettsia in hedgehogs and hedgehog-attached ticks in Xuyi County, Southeast China, 114 ticks were collected from 45 hedgehogs captured totally. Via morphological and molecular methods, all these ticks were identified as two species: Haemaphysalis flava (110/114, 96.5%) and Haemaphysalis longicornis (4/114, 3.5%). Rickettsia spp. were genotypically characterized by PCR targeting rrs , gltA , ompA , ompB , and sca4 gene fragments. The prevalence of spotted fever group rickettsiae (SFGR) infection found in hedgehogs and ticks was 17.8% (8/45) and 78.1% (89/114), respectively. Phylogenetic analyses demonstrated that those Rickettsia spp. belong to two species: Rickettsia heilongjiangensis ( R. heilongjiangensis XY-1) and a potential new species, Candidatus Rickettsia xuyiensis XY-2. The present study gave the first evidence of R. heilongjiangensis and Candidatus R. xuyiensis in ticks and hedgehogs of Southeast China. Our findings suggest that hedgehogs might be involved in the natural transmission cycle of Rickettsia species.

Phthalate exposure enhances incidence of urinary incontinence: US NHANES, 2003–2004 and 2005–2006 - Xianyanling Yi; Kun Jin; Shi Qiu; Xingyu Xiong; Tianyi Zhang; Ge Peng; Dazhou Liao; Xiaonan Zheng; Hang Xu; Hong Li; Lu Yang; Qiang Wei; et al. (Environmental Science and Pollution Research, 2022)

Ovary transcriptomic analysis reveals regulation effects of dietary fish oil on hormone, lipid, and glucose metabolism in female adult spotted scat (Scatophagus argus) - Tuo Wang; Zhi-Long Liu; Guang-Li Li; Umar Farouk Mustapha; Charles Brighton Ndandala; Hong-Juan Shi; Chun-Hua Zhu; Hua-Pu Chen; Yang Huang; Dong-Neng Jiang (Frontiers in Marine Science, 2022)
In the aquaculture industry, fish oil is widely used as a nutritional supplement to promote the gonadal maturation of broodstocks, while the mechanism of fish oil on ovary development remain unclear. Herein, female adult spotted scat ( Scatophagus argus ) with most ovaries at phase II were fed with diets containing 8% soybean oil (SO) or 8% fish oil (FO) for 60 days. The final average fish body weight was similar between FO and SO groups. The average gonadosomatic index (GSI) of FO group was higher (non-significant) than that of SO group. Finally, the phase IV ovary of the FO and SO groups were 7 and 5 out of 10, respectively. The serum estradiol (E2) level of the FO group was significantly higher than that of the SO group. The proportions of n-3 long-chain polyunsaturated fatty acids (LC-PUFA, such as docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA)) in the ovaries were much higher in the FO group than in the SO group. These results suggest that the maturity level of the FO group is relatively higher than that of the SO group. Transcriptome sequencing was used to detect the ovary gene expression. Comparatively, the ovary transcriptome analysis showed 68 up-regulated and 193 down-regulated genes in the FO group. The expression levels of Jund and Jun necessary for the ovary maturation were up-regulated in the FO group, while Pparγ and Cxcl12 , which could inhibit the ovary development, were down-regulated in the FO group. Cyp3a27 coding the enzyme for degrading the estrogen was significantly down-regulated in the FO group and coincided with the increase of its serum E2. Kif5b which could regulate the glucose metabolism was up-regulated in the FO group. Serum insulin level was also increased in the FO group. Additionally, Aldh3a2 and Plin2 related to lipid metabolism were significantly down-regulated in the FO group. Briefly, dietary fish oil can influence the expression of genes related to steroid hormone, glucose and lipid metabolism. This study will clarify the mechanism of dietary fish oil in promoting ovary development in teleost fish.

Genetic basis underlying tiller angle in rice (Oryza sativa L.) by genome-wide association study - Shaoxing Bai; Jun Hong; Su Su; Zhikang Li; Wensheng Wang; Jianxin Shi; Wanqi Liang; Dabing Zhang (Plant Cell Reports, 2022)

Evansella halocellulosilytica sp. nov., an alkali-halotolerant and cellulose-dissolving bacterium isolated from bauxite residue - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Extremophiles, 2022)

Experimental study on the effects of particle grading on lime-treated slurry with vacuum preloading - Hong-lei Sun; Zhen-qi Weng; Xue-yu Geng; Meng-fen Shen; Xiao-dong Pan; Li Shi; Yuan-qiang Cai (Marine Georesources & Geotechnology, 2022)

Characterization, heterologous expression and engineering of trehalase for biotechnological applications - Han Gao; Jin-Song Gong; Chang Su; Heng Li; Zheng-Hong Xu; Jin-Song Shi (Systems Microbiology and Biomanufacturing, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

A Hypoxia-Sensitive Drug Delivery System Constructed by Nitroimidazole and its Application in the Treatment of Hepatocellular Carcinoma - Tingting Meng; Yinghong Li; Ying Tian; Mingxing Ma; Kequan Shi; Xuwei Shang; Hong Yuan; Fuqiang Hu (AAPS PharmSciTech, 2022)

Ligustilide ameliorates cognitive impairment via AMPK/SIRT1 pathway in vascular dementia rat - Dong Peng; Han-Zi Qiao; Hong-Yu Tan; Yi-Xue Wang; Dan Luo; Li-Jun Qiao; Ye-Feng Cai; Shi-Jie Zhang; Qi Wang; Li Guan (Metabolic Brain Disease, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Impact of land cover transformation on urban heat islands in Harbin, China - Stephen Dauda Yabo; Donglei Fu; Bo Li; Xiaofei Shi; Samit Thapa; Xie Shengjin; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2022)

An integrated belowground trait‐based understanding of nitrogen‐driven plant diversity loss - Qiuying Tian; Peng Lu; Xiufeng Zhai; Ruifang Zhang; Yao Zheng; Hong Wang; Bao Nie; Wenming Bai; Shuli Niu; Peili Shi; Yuanhe Yang; Kaihui Li; et al. (Global Change Biology, 2022)
Belowground plant traits play important roles in plant diversity loss driven by atmospheric nitrogen (N) deposition. However, the way N enrichment shapes plant microhabitats by patterning belowground traits and finally determines aboveground responses is poorly understood. Here, we investigated the rhizosheath trait of 74 plant species in seven N‐addition simulation experiments across multiple grassland ecosystems in China. We found that rhizosheath formation differed among plant functional groups and contributed to changes in plant community composition induced by N enrichment. Compared with forb species, grass and sedge species exhibited distinct rhizosheaths; moreover, grasses and sedges expanded their rhizosheaths with increasing N‐addition rate which allowed them to colonize belowground habitats. Grasses also shaped a different microenvironment around their roots compared with forbs by affecting the physicochemical, biological, and stress‐avoiding properties of their rhizosphere soil. Rhizosheaths act as a “biofilm‐like shield” by the accumulation of protective compounds, carboxylic anions and polysaccharides, determined by both plants and microorganisms. This enhanced the tolerance of grasses and sedges to stresses induced by N enrichment. Conversely, forbs lacked the protective rhizosheaths which renders their roots sensitive to stresses induced by N enrichment, thus contributing to their disappearance under N‐enriched conditions. This study uncovers the processes by which belowground facilitation and trait matching affect aboveground responses under conditions of N enrichment, which advances our mechanistic understanding of the contribution of competitive exclusion and environmental tolerance to plant diversity loss caused by N deposition.

Erratum to: MYH7B variants cause hypertrophic cardiomyopathy by activating the CaMK-signaling pathway - Peng Chen; Zongzhe Li; Jiali Nie; Hong Wang; Bo Yu; Zheng Wen; Yang Sun; Xiaolu Shi; Li Jin; Dao-Wen Wang (Science China Life Sciences, 2022)

Metagenomic analysis reveals wide distribution of phototrophic bacteria in hydrothermal vents on the ultraslow-spreading Southwest Indian Ridge - Hong Chen; Deng Hui Li; Ai Jun Jiang; Xue Gong Li; Shi Jun Wu; Jian Wei Chen; Meng Jie Qu; Xiao Qing Qi; Jie Dai; Rui Zhao; Wei-Jia Zhang; Shan Shan Liu; et al. (Marine Life Science & Technology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Neobacillus rhizophilus sp. nov. and Neobacillus citreus sp. nov., isolated from the citrus rhizosphere soil - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Huai Shi; Jian-Mei Che; Bo Liu; Wen-Jun Li (Archives of Microbiology, 2022)

Quantitative detection of parasitic ciliate Cryptocaryon irritans in seawater with an optimized sample processing method - Jia‐Jia Tang; Zhi‐Hong Zhong; Zhi‐Cheng Li; Qing‐Kai Guo; Shi‐Yu Li; Yi‐Xuan Guo; Biao Jiang; An‐Xing Li (Journal of Fish Diseases, 2022)
The protozoan Cryptocaryon irritans is one of the most important ectoparasites of marine fish, causing ‘white spot disease’ and mass mortality in aquaculture. To accurately predict disease outbreaks and develop prevention strategies, improved detection methods are required that are sensitive, convenient and rapid. In this study, a pair of specific primers based on the C . irritans 18S rRNA gene was developed and used in a real‐time PCR (qPCR) assay. This assay was able to detect five theronts in 1 L of natural seawater. Furthermore, a linear model was established to analyse the log of Ct value and parasite abundance in seawater (y = –2.9623x + 24.2930), and the coefficient of determination (R 2 ) value was 0.979. A lysis buffer was optimized for theront DNA extraction and used for storage sample. This method was superior to the commercial water DNA kit, and there was no significant degradation of DNA at room temperature for 24–96 hr. A dilution method was developed to manage qPCR inhibitors and used to investigate natural seawater samples in a net cage farm with diseased fish, and the findings were consistent with the actual situation. This study provides a valuable tool for assisting in the early monitoring and control of cryptocaryoniasis in aquaculture.

Geochronology and geochemistry of Late Triassic intrusions in the Liaodong Peninsula, eastern North China Craton: implications for post-collisional lithospheric thinning - Chen Wang; Zheng-Hong Liu; Gang Li; Xiao-Jie Dong; Shi-Chao Li; Qing-Ying Zhao (International Geology Review, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Unique bacterial communities associated with components of an artificial aquarium ecosystem and their possible contributions to nutrient cycling in this microecosystem - Jun Shi Zhou; Jian Fei Cheng; Xue Dong Li; Yan Hong Li (World Journal of Microbiology and Biotechnology, 2022)

Distinct co-occurrence patterns and driving forces of abundant and rare bacterial communities in the multispecies solid-state fermentation process of cereal vinegar - Ming-Ye Peng; Zhen-Ming Lu; Xiao-Juan Zhang; Ting Huang; Yong-Jian Deng; Li-Juan Chai; Jin-Song Shi; Zheng-Hong Xu (Systems Microbiology and Biomanufacturing, 2022)

Sodium tanshinone IIA sulfonate improves cognitive impairment via regulating Aβ transportation in AD transgenic mouse model - Hui-Han Ma; Can Wan; Lu-Di Zhang; Rong-Rong Zhang; Dong Peng; Li-Jun Qiao; Shi-Jie Zhang; Ye-Feng Cai; Hong-Qiang Huang (Metabolic Brain Disease, 2022)

A genetic-based population PK/PD modeling of methadone in Chinese opiate dependence patients - Dong Guo; Zhirong Tan; Xiaoya Lou; Shan Shi; Yan Shu; Honghao Zhou; Li Yu; Hong Yang (European Journal of Clinical Pharmacology, 2022)

Correction to: Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo‑Hong Liu; Manik Prabhu Narsing Rao; Qian‑Qian Chen; Jian‑Mei Che; Huai Shi; Bo Liu; Wen‑Jun Li (Current Microbiology, 2022)

Efficient production of GlcNAc in an aqueous-organic system with a Chitinolyticbacter meiyuanensis SYBC-H1 mutant - Zhi-kui Hao; Jian-song Li; Dan-hua Wang; Fei He; Jing-shi Xue; Liang-hong Yin; Hua-bao Zheng (Biotechnology Letters, 2022)

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Impacts of late-spring North Eurasian soil moisture variation on summer rainfall anomalies in Northern East Asia - Yinghan Sang; Hong-Li Ren; Yi Deng; Xiaofeng Xu; Xueli Shi; Shuo Zhao (Climate Dynamics, 2022)

Fine mapping of the tiller inhibition gene TIN4 contributing to ideal plant architecture in common wheat - Zhiqiang Wang; Fangkun Wu; Xudong Chen; Wanlin Zhou; Haoran Shi; Yu Lin; Shuai Hou; Shifan Yu; Hong Zhou; Caixia Li; Yaxi Liu (Theoretical and Applied Genetics, 2022)

Lederbergia citri sp. nov., and Lederbergia citrisecundus sp. nov., isolated from citrus rhizosphere - Guo-Hong Liu; Manik Prabhu Narsing Rao; Qian-Qian Chen; Jian-Mei Che; Huai Shi; Bo Liu; Wen-Jun Li (Current Microbiology, 2022)

Delayed body development with reduced triglycerides levels in leptin transgenic pigs - Yubo Qing; Muhammad Ameen Jamal; Dejia Shi; Sumei Zhao; Kaixiang Xu; Deling Jiao; Heng Zhao; Honghui Li; Baoyu Jia; Haizhen Wang; Hong-Ye Zhao; Hong-Jiang Wei (Transgenic Research, 2022)

Responses and feedback of litter properties and soil mesofauna to herbaceous plants expansion into the alpine tundra on Changbai Mountain, China - Ying-jie Zhang; Ying-hua Jin; Jia-wei Xu; Hong-shi He; Yan Tao; Zhi-peng Yang; Jing Zhao; Yin-xia Diao; Chen-hui Sun; Mai-He Li (Journal of Mountain Science, 2022)

Cloning and expression analysis of the HSL gene in Whitmania pigra (Annelida: Hirudinea) - Li-Yuan Guo; Qiao-Sheng Guo; Hong-Zhuan Shi; Feng Yang; Yi-Xiu Miao (Invertebrate Reproduction & Development, 2022)

Sigma-1 Receptor Activation Suppresses Microglia M1 Polarization via Regulating Endoplasmic Reticulum–Mitochondria Contact and Mitochondrial Functions in Stress-Induced Hypertension Rats - Kokwin Ooi; Li Hu; Yi Feng; Chenzhi Han; Xiaorong Ren; Xinyi Qian; Haofeng Huang; Sijia Chen; Qi Shi; Hong Lin; Jijiang Wang; Danian Zhu; et al. (Molecular Neurobiology, 2021)

Overexpression of an aquaporin protein from Aspergillus glaucus confers salt tolerance in transgenic soybean - Feiwu Li; Hejia Ni; Wei Yan; Yanbo Xie; Xiaodan Liu; Xichang Tan; Ling Zhang; Shi-Hong Zhang (Transgenic Research, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Stress response mechanisms and description of three novel species Shewanella avicenniae sp. nov., Shewanella sedimentimangrovi sp. nov. and Shewanella yunxiaonensis sp. nov., isolated from mangrove ecosystem - Guo-Hong Liu; Qi Zhang; Manik Prabhu Narsing Rao; Shang Yang; Rong Tang; Huai Shi; Jie-Ping Wang; Guan-Min Huang; Bo Liu; Shun-Gui Zhou; Wen-Jun Li (Antonie van Leeuwenhoek, 2021)

NB-LRR genes: characteristics in three Solanum species and transcriptional response to Ralstonia solanacearum in tomato - Jian Lei Shi; Wen Shan Zai; Zhi Li Xiong; Hong Jian Wan; Wei Ren Wu (Planta, 2021)

Time-resolved Fluorescence Immunoassay (TRFIA) for the Simultaneous Detection of MMP-9 and Lp-PLA2 in Serum - Hong-yan Ma; Qian Mao; Yan-bin Zhu; Chun-li Cong; Shi-yu Zheng; Qi Zhang; Cui-cui Chen; Lai-qing Li (Journal of Fluorescence, 2021)

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

Do foreign direct investment and environmental regulation improve green technology innovation? An empirical analysis based on panel data from the Chinese manufacturing industry - Shi-Chun Xu; Yun-Fan Li; Jing-Nan Zhang; Yan Wang; Xiao-Xue Ma; Hong-Yu Liu; Hai-Ning Wang; Yuan Tao (Environmental Science and Pollution Research, 2021)

Methane Concentration in the Heartwood of Living Trees and Estimated Methane Emission on Stems in Upland Forests - Zhi-Ping Wang; Huan-Long Li; Hong-Hui Wu; Shi-Jie Han; Jian-Hui Huang; Xi-Mei Zhang; Xing-Guo Han (Ecosystems, 2021)

Characterization of a transcription factor SlNAC7 gene from Suaeda liaotungensis and its role in stress tolerance - Hong-Fei Wang; Hong-Yan Shan; He Shi; Dan-Dan Wu; Tong-Tong Li; Qiu-Li Li (Journal of Plant Research, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

Fine mapping of hybrid necrosis gene Ne1 in common wheat (Triticum aestivum L.) - Yaoqi Si; Shusong Zheng; Jianqing Niu; Shuiquan Tian; Xiaoli Shi; Yilin He; Yiwen Li; Hong-Qing Ling (Theoretical and Applied Genetics, 2021)

Alpha-Lipoic Acid Attenuates Cadmium- and Lead-Induced Neurotoxicity by Inhibiting Both Endoplasmic-Reticulum Stress and Activation of Fas/FasL and Mitochondrial Apoptotic Pathways in Rat Cerebral Cortex - Yan Yuan; Shi Wen Zhao; Shuang Quan Wen; Qiao Ping Zhu; Li Wang; Hui Zou; Jian Hong Gu; Xue Zhong Liu; Jian Chun Bian; Zong Ping Liu (Neurotoxicity Research, 2021)

Impact of climate change on snowmelt runoff in a Himalayan basin, Nepal - Samit Thapa; Haizhi Li; Bo Li; Donglei Fu; Xiaofei Shi; Stephen Yabo; Lu Lu; Hong Qi; Wei Zhang (Environmental Monitoring and Assessment, 2021)

Individual variation in metabolic rate, locomotion capacity and hypoxia tolerance and their relationships in juveniles of three freshwater fish species - Xu Pang; De-Yong Pu; Dan-Yang Xia; Xiao-Hong Liu; Shi-Hua Ding; Yun Li; Shi-Jian Fu (Journal of Comparative Physiology B, 2021)

Ziziphus jujuba Mill., a plant used as medicinal food: a review of its phytochemistry, pharmacology, quality control and future research - Shi-Jun Liu; Yan-Ping Lv; Zhi-Shu Tang; Yu Zhang; Hong-Bo Xu; Dong-Bo Zhang; Chun-Li Cui; Hong-Bo Liu; Huan-Huan Sun; Zhong-Xing Song; Si-Min Wei (Phytochemistry Reviews, 2021)

Genetic Architecture of Childhood Kidney and Urological Diseases in China - Ye Fang; Hua Shi; Tianchao Xiang; Jiaojiao Liu; Jialu Liu; Xiaoshan Tang; Xiaoyan Fang; Jing Chen; Yihui Zhai; Qian Shen; Guomin Li; Li Sun; et al. (Phenomics, 2021)
Kidney disease is manifested in a wide variety of phenotypes, many of which have an important hereditary component. To delineate the genotypic and phenotypic spectrum of pediatric nephropathy, a multicenter registration system is being implemented based on the Chinese Children Genetic Kidney Disease Database (CCGKDD). In this study, all the patients with kidney and urological diseases were recruited from 2014 to 2020. Genetic analysis was conducted using exome sequencing for families with multiple affected individuals with nephropathy or clinical suspicion of a genetic kidney disease owing to early-onset or extrarenal features. The genetic diagnosis was confirmed in 883 of 2256 (39.1%) patients from 23 provinces in China. Phenotypic profiles showed that the primary diagnosis included steroid-resistant nephrotic syndrome (SRNS, 23.5%), glomerulonephritis (GN, 32.2%), congenital anomalies of the kidney and urinary tract (CAKUT, 21.2%), cystic renal disease (3.9%), renal calcinosis/stone (3.6%), tubulopathy (9.7%), and chronic kidney disease of unknown etiology (CKDu, 5.8%). The pathogenic variants of 105 monogenetic disorders were identified. Ten distinct genomic disorders were identified as pathogenic copy number variants (CNVs) in 11 patients. The diagnostic yield differed by subgroups, and was highest in those with cystic renal disease (66.3%), followed by tubulopathy (58.4%), GN (57.7%), CKDu (43.5%), SRNS (29.2%), renal calcinosis /stone (29.3%) and CAKUT (8.6%). Reverse phenotyping permitted correct identification in 40 cases with clinical reassessment and unexpected genetic conditions. We present the results of the largest cohort of children with kidney disease in China where diagnostic exome sequencing was performed. Our data demonstrate the utility of family-based exome sequencing, and indicate that the combined analysis of genotype and phenotype based on the national patient registry is pivotal to the genetic diagnosis of kidney disease.

Deformation and fracture at floor area and the correlation with main roof breakage in deep longwall mining - Chunyuan Li; Jianping Zuo; Yue Shi; Chunchen Wei; Yuqing Duan; Yong Zhang; Hong Yu (Natural Hazards, 2021)

DNA Methyltransferase 1 Is Dysregulated in Parkinson’s Disease via Mediation of miR-17 - Hong-Qiu Zhang; Jian-Yong Wang; Zhao-Feng Li; Lei Cui; Shi-Shi Huang; Lan-Bing Zhu; Yue Sun; Rui Yang; Hui-Hui Fan; Xiong Zhang; Jian-Hong Zhu (Molecular Neurobiology, 2021)

Effects of multi-phase inoculation on the fungal community related with the improvement of medicinal herbal residues composting - Xiao-Lin Lu; Hao Wu; Shi-Li Song; Hong-Yan Bai; Meng-Jun Tang; Fang-Ji Xu; Yan Ma; Chuan-Chao Dai; Yong Jia (Environmental Science and Pollution Research, 2021)

Physical test of fracture development in the overburden strata above the goaf and diffusion process of permeable grout slurry - Hong Shi; Yongbo Zhang; Li Tang (Bulletin of Engineering Geology and the Environment, 2021)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

The nonreciprocal heterostyly and heterotypic self-incompatibility of Ceratostigma willmottianum - Suping Gao; Wenji Li; Meiting Hong; Ting Lei; Ping Shen; Jiani Li; Mingyan Jiang; Yifan Duan; Lisha Shi (Journal of Plant Research, 2021)

Influence of major water conservation projects on river channels and shorelines in the middle and lower reaches of the Yangtze River - Yue-hua Jiang; He-qin Cheng; Quan-ping Zhou; Yun Li; Guo-qiang Yang; Yang Jin; Shi-jia Mei; Xuan Gu; Hong Zhang (Arabian Journal of Geosciences, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Examining construction waste management policies in mainland China for potential performance improvements - Hao Lv; Yashuai Li; Hong-Bin Yan; Di Wu; Guanqun Shi; Qian Xu (Clean Technologies and Environmental Policy, 2021)

Evaluating the effect of midpalatal corticotomy-assisted rapid maxillary expansion on the upper airway in young adults using computational fluid dynamics - Juan Li; Lingfang Shi; Xiayao Zhang; Luxi Weng; Hong Chen; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2021)

Improvement of Soil Moisture Simulation in Eurasia by the Beijing Climate Center Climate System Model from CMIP5 to CMIP6 - Yinghan Sang; Hong-Li Ren; Xueli Shi; Xiaofeng Xu; Haishan Chen (Advances in Atmospheric Sciences, 2021)

Correction to: The effects of soil shrinkage during centrifuge tests on SWCC and soil microstructure measurements - Lincui Li; Xi-An Li; Li Wang; Bo Hong; Jianfeng Shi; Jianqiang Sun (Bulletin of Engineering Geology and the Environment, 2021)

Field tests of micro screw anchor piles under different loading conditions at three soil sites - Shi-Jin Feng; Wen-Ding Fu; Hong-Xin Chen; Hong-Xing Li; Yan-Li Xie; Shao-Feng Lv; Jin Li (Bulletin of Engineering Geology and the Environment, 2021)

Using sowing date management to promote micronutrient quality and alleviate cadmium accumulation in rice grains - Lin-lin Shi; Ming-xing Shen; Hong-jun Wu; Chang-ying Lu; Li-juan Mei; Xin-lian Zhu; Hai-hou Wang; Yun-Sheng Song (Cereal Research Communications, 2020)

Larger regional volume of the thalamus in diarrhea-predominant irritable bowel syndrome: a cross-sectional study - Cui Ping Mao; Fen Rong Chen; Hong Hong Sun; Mei Juan Shi; Hua Juan Yang; Xiao Hui Li; Dun Ding (Brain Imaging and Behavior, 2020)

Three-dimensional numerical modeling of water distribution tunnels in karst area - Xiao-dong Pan; Yu-chao Fang; Yong Lai; Hong-lei Sun; Yuan-qiang Cai; Li Shi; Xue-yu Geng (Arabian Journal of Geosciences, 2020)

Dietary lipid concentrations influence growth, body composition, morphology of the liver and mid-intestine, and antioxidant status of marbled eel (Anguilla marmorata) - Shi-Jun Chen; Peng Liu; You-Ming Jia; Hong-Ping Liao; Shao-Xuan Zhu; Li-Liu Zhou; Xue-Ming Dan; Li Liu; Jia-Hao Li; Su-Bi Zheng; Jun-Jiang Yang; Lian Gan (Aquaculture International, 2020)

Influence of complex topography on magnetotelluric-observed data using three-dimensional numerical simulation: A case from Guangxi area, China - Xiong Bin; Luo Tian-Ya; Chen Long-Wei; Dai Shi-Kun; Xu Zhi-Feng; Li Chang-Wei; Ding Yan-Li; Wang Hong-Hua; Li Jing-He (Applied Geophysics, 2020)

The effect of cell size on cellular Zn and Cd and Zn‐Cd‐CO 2 colimitation of growth rate in marine diatoms - Weiying Li; William G. Sunda; Wenfang Lin; Haizheng Hong; Dalin Shi (Limnology and Oceanography, 2020)
Cadmium (Cd) can serve as nutrient in marine diatoms by partially replacing zinc (Zn) in Zn‐limited cells. A major basis for this is the replacement of Cd for Zn in a Cd‐containing carbonic anhydrase (CDCA) needed for cellular acquisition of CO 2 . As a result of these interactions, cells can become colimited by Zn, Cd, and CO 2 . Large cell size should restrict the cellular uptake of Zn, Cd, and CO 2 due to decreasing surface to volume ratios and limitation of diffusive flux of these nutrients to the cell surface. Large cells are thus more likely to become Zn‐Cd‐CO 2 colimited than smaller ones. These predictions were confirmed in experiments with three marine diatoms: Thalassiosira pseudonana , Thalassiosira weissflogii , and Ditylum brightwellii , ranging in cell volume from 50 to 6000 fL. Cellular Zn : C ratios decreased by 10‐fold between the largest and smallest species, and consequently, the largest diatom was more readily growth‐limited than smaller ones by low external concentrations of bioavailable dissolved inorganic Zn (Zn′). Decreasing cellular Zn : C ratios were accompanied by large increases in cellular Cd uptake rates and Cd : C ratios. However, at the lowest Zn′ concentrations, Cd uptake plateaued, with the larger cells having lower cellular concentrations of both Zn and Cd. Cellular replacement of Zn by Cd was accompanied by increases in cellular CDCA expression. The largest diatom had higher combined carbonic anhydrase activities for a given Zn‐, Cd‐limited growth rate, supporting the hypothesis that these cells could be colimited by Zn, Cd, and CO 2 at low external CO 2 concentrations.

Genetic diversity comparisons of wild populations of Nelumbo nucifera (Nelumbonaceae) in Russia and China using microsatellite markers - Zhi-Zhong Li; Md. Rabiul Islam; Shi-Xu Huang; Dan Yang; Yeshitila Mekbib; Popova Svetlana; Hong-Bing Sun; Jin-Ming Chen; Xing-Yu Yang (Plant Systematics and Evolution, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

MYH7B variants cause hypertrophic cardiomyopathy by activating the CaMK-signaling pathway - Peng Chen; Zongzhe Li; Jiali Nie; Hong Wang; Bo Yu; Zheng Wen; Yang Sun; Xiaolu Shi; Li Jin; Dao-Wen Wang (Science China Life Sciences, 2020)

Macrophage–NLRP3 Inflammasome Activation Exacerbates Cardiac Dysfunction after Ischemic Stroke in a Mouse Model of Diabetes - Hong-Bin Lin; Guan-Shan Wei; Feng-Xian Li; Wen-Jing Guo; Pu Hong; Ya-Qian Weng; Qian-Qian Zhang; Shi-Yuan Xu; Wen-Bin Liang; Zhi-Jian You; Hong-Fei Zhang (Neuroscience Bulletin, 2020)

The effects of soil shrinkage during centrifuge tests on SWCC and soil microstructure measurements - Lincui Li; Xi-An Li; Li Wang; Bo Hong; Jianfeng Shi; Jianqiang Sun (Bulletin of Engineering Geology and the Environment, 2020)

Effective identification of CRISPR/Cas9-induced and naturally occurred mutations in rice using a multiplex ligation-dependent probe amplification-based method - Sukumar Biswas; Rong Li; Jun Hong; Xiangxiang Zhao; Zheng Yuan; Dabing Zhang; Jianxin Shi (Theoretical and Applied Genetics, 2020)

Ghrelin Reduces A-Type Potassium Currents in Dopaminergic Nigral Neurons via the PLC/PKCδ Pathway - Bao Xue; Chen Li; Xiaoli Chang; Hong Jiang; Limin Shi; Junxia Xie (Neuroscience Bulletin, 2020)

Effects of crop straw biochars on aluminum species in soil solution as related with the growth and yield of canola (Brassica napus L.) in an acidic Ultisol under field condition - Wen-rui Zhao; Jiu-yu Li; Kai-ying Deng; Ren-yong Shi; Jun Jiang; Zhi-neng Hong; Wei Qian; Xian He; Ren-kou Xu (Environmental Science and Pollution Research, 2020)

Assessing drug cue-induced brain response in heroin dependents treated by methadone maintenance and protracted abstinence measures - Xuan Wei; Wei Li; Jiajie Chen; Yongbin Li; Jia Zhu; Hong Shi; Jierong Liu; Jiuhua Xue; Wei Liu; Fan Wang; Yan Liu; Shan Dang; et al. (Brain Imaging and Behavior, 2020)

Arsenic, lead, and cadmium bioaccessibility in contaminated soils: Measurements and validations - Hong-Bo Li; Meng-Ya Li; Di Zhao; Jie Li; Shi-Wei Li; Ping Xiang; Albert L. Juhasz; Lena Q. Ma (Critical Reviews in Environmental Science and Technology, 2020)

Correlation Between CCG Polymorphisms and CAG Repeats During Germline Transmission in Chinese Patients with Huntington’s Disease - Hong-Rong Cheng; Xiao-Yan Li; Hui-Li Yu; Miao Xu; Yan-Bin Zhang; Shi-Rui Gan; Hong-Lei Li; Zhi-Ying Wu (Neuroscience Bulletin, 2020)

Preparation of aluminum sludge composite gel spheres and adsorption of U(IV) from aqueous solution - Jin-hui Yang; Zeng-jiang Lei; Yang-hong Dai; Yi Luo; Shui-bo Xie; Jing-song Wang; Shu-kui Zhou; Bai Wei; Cong Li; Shi-qing Hu (Environmental Science and Pollution Research, 2020)

Trend analysis of climatic variables and their relation to snow cover and water availability in the Central Himalayas: a case study of Langtang Basin, Nepal - Samit Thapa; Bo Li; Donglei Fu; Xiaofei Shi; Bo Tang; Hong Qi; Kun Wang (Theoretical and Applied Climatology, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Synchrotron Radiation-Based Three-Dimensional Visualization of Angioarchitectural Remodeling in Hippocampus of Epileptic Rats - Pan Gu; Zi-Hao Xu; Yu-Ze Cao; Sheng-Hui Liao; Qian-Fang Deng; Xian-Zhen Yin; Zhuo-Lu Wang; Zhuo-Hui Chen; Xin-Hang Hu; Hui Wang; Li-Zhi Li; Shi-Xin Liu; et al. (Neuroscience Bulletin, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

Statistical optimization of a cellulase from Aspergillus glaucus CCHA for hydrolyzing corn and rice straw by RSM to enhance yield of reducing sugar - Lina Chen; Yi Wei; Mao Shi; Zhengqun Li; Shi-Hong Zhang (Biotechnology Letters, 2020)

Wave and current-induced dynamic response in a multilayered poroelastic seabed - Hui-Feng Qi; Zhang-Long Chen; Yi-Cheng Li; Shi-Jin Feng; Hong-Xin Chen (Bulletin of Engineering Geology and the Environment, 2020)

Study of Recellularized Human Acellular Arterial Matrix Repairs Porcine Biliary Segmental Defects - Wei Liu; Sheng-Ning Zhang; Zong-Qiang Hu; Shi-Ming Feng; Zhen-Hui Li; Shu-Feng Xiao; Hong-Shu Wang; Li Li (Tissue Engineering and Regenerative Medicine, 2019)

Comparative transcriptome analysis of male and female gonads reveals sex-biased genes in spotted scat (Scatophagus argus) - Fei-Xiang He; Dong-Neng Jiang; Yuan-Qing Huang; Umar Farouk Mustapha; Wei Yang; Xue-Fan Cui; Chang-Xu Tian; Hua-Pu Chen; Hong-Juan Shi; Si-Ping Deng; Guang-Li Li; Chun-Hua Zhu (Fish Physiology and Biochemistry, 2019)

Environmental and economic impact assessment of the alumina–carbon refractory production in China - Yuzhou Tang; Yifei Shi; Yue Li; Xueliang Yuan; Ruimin Mu; Qingsong Wang; Qiao Ma; Jinglan Hong; Shensong Cao; Jian Zuo; Jon Kellett (Clean Technologies and Environmental Policy, 2019)

Glacier change in the Tanggula Mountains, Tibetan Plateau, in 1969–2015 - Hong-yu Duan; Xiao-jun Yao; Shi-yin Liu; Yong-peng Gao; Miao-miao Qi; Juan Liu; Da-hong Zhang; Xiao-feng Li (Journal of Mountain Science, 2019)

QTL mapping and genetic effect of chromosome segment substitution lines with excellent fiber quality from Gossypium hirsutum × Gossypium barbadense - Shao-qi Li; Ai-ying Liu; Ling-lei Kong; Ju-wu Gong; Jun-wen Li; Wan-kui Gong; Quan-wei Lu; Peng-tao Li; Qun Ge; Hai-hong Shang; Xiang-hui Xiao; Rui-xian Liu; et al. (Molecular Genetics and Genomics, 2019)

Carbon Monoxide Attenuates High Salt-Induced Hypertension While Reducing Pro-inflammatory Cytokines and Oxidative Stress in the Paraventricular Nucleus - Dong-Dong Zhang; Yan-Feng Liang; Jie Qi; Kai B. Kang; Xiao-Jing Yu; Hong-Li Gao; Kai-Li Liu; Yan-Mei Chen; Xiao-Lian Shi; Guo-Rui Xin; Li-Yan Fu; Yu-Ming Kang; et al. (Cardiovascular Toxicology, 2019)

Extraction of electron density profiles with geostationary satellite-based GPS side lobe occultation signals - Wenwen Li; Min Li; Qile Zhao; Chuang Shi; Meng Wang; Min Fan; Hong Wang; Kecai Jiang (GPS Solutions, 2019)

Are mountaintops climate refugia for plants under global warming? A lesson from high-mountain oaks in tropical rainforest - Hong-Hu Meng; Shi-Shun Zhou; Xiao-Long Jiang; Paul F. Gugger; Lang Li; Yun-Hong Tan; Jie Li (Alpine Botany, 2019)

FTY720 Inhibits MPP+-Induced Microglial Activation by Affecting NLRP3 Inflammasome Activation - Shu Yao; Longjun Li; Xin Sun; Jun Hua; Keqi Zhang; Li Hao; Lixin Liu; Dongyan Shi; Hong Zhou (Journal of Neuroimmune Pharmacology, 2019)

Life cycle assessment of autoclaved aerated fly ash and concrete block production: a case study in China - Yifei Shi; Yue Li; Yuzhou Tang; Xueliang Yuan; Qingsong Wang; Jinglan Hong; Jian Zuo (Environmental Science and Pollution Research, 2019)

The complete chloroplast genome of Taiwania cryptomerioides (Cupressales: Cupressaceae), an endangered relict conifer species endemic to East Asia - Ling-Li Wang; Yong-Liang Shi; Qi-Lin Zhang; Yan-Ru Guo; Hong-Mei Teng (Conservation Genetics Resources, 2019)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Differences in clinical and laboratory features between patients with non-tuberculous Mycobacterium and Mycobacterium tuberculosis complex - Xinling Pan; Songjun Ji; Yunzhen Shi; Guogang Li; Li Hong; Yangxiao Zhou (Infectious Diseases, 2019)

F‐box proteins MoFwd1, MoCdc4 and MoFbx15 regulate development and pathogenicity in the rice blast fungus Magnaporthe oryzae - Huan‐Bin Shi; Nan Chen; Xue‐Ming Zhu; Shuang Liang; Lin Li; Jiao‐Yu Wang; Jian‐Ping Lu; Fu‐Cheng Lin; Xiao‐Hong Liu (Environmental Microbiology, 2019)
Summary The Skp1‐Cul1‐F‐box‐protein (SCF) ubiquitin ligases are important parts of the ubiquitin system controlling many cellular biological processes in eukaryotes. However, the roles of SCF ubiquitin ligases remain unclear in phytopathogenic Magnaporthe oryzae . Here, we cloned 24 F‐box proteins and confirmed that 17 proteins could interact with MoSkp1, showing their potential to participate in SCF complexes. To determine their functions, null mutants of 21 F‐box‐containing genes were created. Among them, the F‐box proteins MoFwd1, MoCdc4 and MoFbx15 were found to be required for growth, development and full virulence. Fluorescent‐microscopy observations demonstrated that both MoFbx15 and MoCdc4 were localized to the nucleus, compared with MoFwd1, which was distributed in the cytosol. MoCdc4 and MoFwd1 bound to MoSkp1 via the F‐box domain, the deletion of which abrogated their function. Race tube and qRT‐PCR assays confirmed that MoFwd1 was involved in circadian rhythm by regulating transcription and protein stability of the core circadian clock regulator MoFRQ . Moreover, MoFWD1 also orchestrates conidial germination by influencing conidial amino acids pools and oxidative stress release. Overall, our results indicate that SCF ubiquitin ligases play indispensable roles in development and pathogenicity in M. oryzae .

Wavelet-Nonlinear Cointegration Prediction of Irrigation Water in the Irrigation District - Jinping Zhang; Hongbin Li; Xixi Shi; Yang Hong (Water Resources Management, 2019)

Effect of Fluoride on Small Intestine Morphology and Serum Cytokine Contents in Rats - Hong-wei Wang; Jing Liu; Wen-peng Zhao; Zi-hao Zhang; Si-qi Li; Si-han Li; Shi-quan Zhu; Bian-hua Zhou (Biological Trace Element Research, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Adsorption of sulfate from acid mine drainage in Northwestern China using Malan loess - Qiang Zheng; Yongbo Zhang; Yanrong Li; Zhixiang Zhang; Aijing Wu; Hong Shi (Arabian Journal of Geosciences, 2019)

Copy number variation of bovine SHH gene is associated with body conformation traits in Chinese beef cattle - Mei Liu; Bo Li; Tao Shi; Yongzhen Huang; George E. Liu; Xianyong Lan; Chuzhao Lei; Hong Chen (Journal of Applied Genetics, 2019)

Numerical model of aerobic bioreactor landfill considering aerobic-anaerobic condition and bio-stable zone development - Shi-Jin Feng; An-Zheng Li; Qi-Teng Zheng; Ben-Yi Cao; Hong-Xin Chen (Environmental Science and Pollution Research, 2019)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

Effects of acclimation temperature on the thermal tolerance, hypoxia tolerance and swimming performance of two endangered fish species in China - Long-Yan Zhou; Shi-Jian Fu; Cheng Fu; Hong Ling; Xiu-Ming Li (Journal of Comparative Physiology B, 2019)

Expression of the intrarenal angiotensin receptor and the role of renin-angiotensin system inhibitors in IgA nephropathy - Zheng Zhang; Shi-min Jiang; Ye-ping Ma; Pei-lin Dai; Yi-ning Wang; Gu-ming Zou; Hong-mei Gao; Yue Yang; Wen-ge Li (Molecular and Cellular Biochemistry, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Conflict between biodiversity conservation and economic growth: insight into rare plants in tropical China - Hong-Hu Meng; Shi-Shun Zhou; Lang Li; Yun-Hong Tan; Jian-Wu Li; Jie Li (Biodiversity and Conservation, 2019)

Late Paleocene–early Eocene granitoids in the Jiamusi Massif, NE China: Zircon U–Pb ages, geochemistry, and tectonic implications - Peng-Chuan Li; Zheng-Hong Liu; Shi-Chao Li; Qing-Ying Zhao; Qiang Shi; Chang-Hai Li; Xu-Hai Yang (International Geology Review, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Low root/shoot (R/S) biomass ratio can be an indicator of low cadmium accumulation in the shoot of Chinese flowering cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) cultivars - Zhi-Min Xu; Xiu-Qin Mei; Ling Tan; Qu-Sheng Li; Li-Li Wang; Bao-Yan He; Shi-Hong Guo; Chu Zhou; Han-Jie Ye (Environmental Science and Pollution Research, 2018)

Positive PCNA and Ki-67 Expression in the Testis Correlates with Spermatogenesis Dysfunction in Fluoride-Treated Rats - Wen-peng Zhao; Hong-wei Wang; Jing Liu; Pan-pan Tan; Xiang-long Luo; Shi-quan Zhu; Xue-li Chen; Bian-hua Zhou (Biological Trace Element Research, 2018)

Lack of Association Between DNMT3B Polymorphisms and Sporadic Parkinson’s Disease in a Han Chinese Population - Hong Pan; Jun-Yi Shen; Juan-Juan Du; Shi-Shuang Cui; Jin Liu; Yi-Qi Lin; Yi-Xi He; Yang Fu; Chao Gao; Gen Li; Sheng-Di Chen; Jian-Fang Ma (Neuroscience Bulletin, 2018)

The relationship between putamen-SMA functional connectivity and sensorimotor abnormality in ESRD patients - Dun Ding; Peng Li; Xue-ying Ma; Wang-huan Dun; Shi-feng Yang; Shao-hui Ma; Hong-juan Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Development of a TaqMan probe-based quantitative reverse transcription PCR assay for detection of Getah virus RNA - Ning Shi; Hao Liu; Li-xia Li; Bo Hu; Lei Zhang; Chuan-fang Zhao; Xiao-yu Deng; Xin-tong Li; Xiang-hong Xue; Xue Bai; Hai-ling Zhang; Rong-guang Lu; et al. (Archives of Virology, 2018)

New angular oxazole-fused coumarin derivatives: synthesis and biological activities - Yan Wei; Shi-qiang Li; Shuang-hong Hao (Natural Product Research, 2018)

Cytochrome P450 2AA molecular clone, expression pattern, and different regulation by fish oil and lard oil in diets of grass carp (Ctenopharyngodon idella) - Xiao-chen Shi; Jian Sun; Ai Jin; Hong Ji; Hai-bo Yu; Yang Li; Xue-xian Li; Pin Liu; Chao Li; Ji-qin Huang (Fish Physiology and Biochemistry, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

Depolymerized konjac glucomannan: preparation and application in health care - Min Jiang; Heng Li; Jin-song Shi; Zheng-hong Xu (Journal of Zhejiang University-SCIENCE B, 2018)

The unique GH5 cellulase member in the extreme halotolerant fungus Aspergillus glaucus CCHA is an endoglucanase with multiple tolerance to salt, alkali and heat: prospects for straw degradation applications - Zhengqun Li; Xue Pei; Ziyu Zhang; Yi Wei; Yanyue Song; Lina Chen; Shouan Liu; Shi-Hong Zhang (Extremophiles, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Purα Repaired Expanded Hexanucleotide GGGGCC Repeat Noncoding RNA-Caused Neuronal Toxicity in Neuro-2a Cells - Jianying Shen; Yu Zhang; Shi Zhao; Hong Mao; Zhongjing Wang; Honglian Li; Zihui Xu (Neurotoxicity Research, 2018)

Identification, characterization and expression analysis of genes involved in steroidal saponin biosynthesis in Dracaena cambodiana - Jia-Hong Zhu; Hui-Liang Li; Dong Guo; Ying Wang; Hao-Fu Dai; Wen-Li Mei; Shi-Qing Peng (Journal of Plant Research, 2018)

In Situ Observation of Rock Spalling in the Deep Tunnels of the China Jinping Underground Laboratory (2400 m Depth) - Xia-Ting Feng; Hong Xu; Shi-Li Qiu; Shao-Jun Li; Cheng-Xiang Yang; Hao-Sen Guo; Yuan Cheng; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Signaling molecule methylglyoxal-induced thermotolerance is partly mediated by hydrogen sulfide in maize (Zea mays L.) seedlings - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang (Acta Physiologiae Plantarum, 2018)

Predictive modeling of microbial single cells: A review - Tian Ding; Xin-Yu Liao; Qing-Li Dong; Xiao-Ting Xuan; Shi-Guo Chen; Xing-Qian Ye; Dong-Hong Liu (Critical Reviews in Food Science and Nutrition, 2018)

DR1 activation reduces the proliferation of vascular smooth muscle cells by JNK/c-Jun dependent increasing of Prx3 - Junting Chen; Sa Shi; Xiaona Cai; Hongzhu Li; Lina Wang; Hong Li; Changqing Xu (Molecular and Cellular Biochemistry, 2018)

Comparative WGBS identifies genes that influence non-ripe phenotype in tomato epimutant Colourless non-ripening - Weiwei Chen; Zhiming Yu; Junhua Kong; Hui Wang; Yichen Li; Mei Zhao; Xiaohong Wang; Qianqian Zheng; Nongnong Shi; Pengcheng Zhang; Silin Zhong; Paul Hunter; et al. (Science China Life Sciences, 2018)

Short hairpin RNA interference targeting interleukin 1 receptor type I in the paraventricular nucleus attenuates hypertension in rats - Peng Lu; Shu-jun Jiang; Hong Pan; Ai-li Xu; Gui-hua Wang; Chun-lei Ma; Zhen Shi (Pflügers Archiv - European Journal of Physiology, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

CFD modeling of hydro-biochemical behavior of MSW subjected to leachate recirculation - Shi-Jin Feng; Ben-Yi Cao; An-Zheng Li; Hong-Xin Chen; Qi-Teng Zheng (Environmental Science and Pollution Research, 2018)

Inducible ATF3–NFAT axis aggravates podocyte injury - Hong Zhang; Shun Liang; Yue Du; Ruizhao Li; Chaosheng He; Wenjian Wang; Shuangxin Liu; Zhiming Ye; Xinling Liang; Wei Shi; Bin Zhang (Journal of Molecular Medicine, 2018)

Regulatory role of miR-18a to CCN2 by TGF-β1 signaling pathway in pulmonary injury induced by nano-SiO2 - Hong Yang; Wenchao Li; Yingjian Zhang; Mingyue Li; Ying Gao; Canshan Lao; Bing Shi (Environmental Science and Pollution Research, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Pathogen genomic surveillance elucidates the origins, transmission and evolution of emerging viral agents in China - Weifeng Shi; Juan Li; Hong Zhou; George F. Gao (Science China Life Sciences, 2017)

Nanoparticle-encapsulated emodin decreases diabetic neuropathic pain probably via a mechanism involving P2X3 receptor in the dorsal root ganglia - Lin Li; Xuan Sheng; Shanhong Zhao; Lifang Zou; Xinyao Han; Yingxin Gong; Huilong Yuan; Liran Shi; Lili Guo; Tianyu Jia; Shuangmei Liu; Bing Wu; et al. (Purinergic Signalling, 2017)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Effects of virus infection on plant growth, root development and phytohormone levels in in vitro-cultured pear plants - Jie Chen; Hui-Hui Tang; Liu Li; Shi-Jiao Qin; Guo-Ping Wang; Ni Hong (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Identification and expression analysis of genes involved in histone acetylation in Hevea brasiliensis - Hui-Liang Li; Dong Guo; Jia-Hong Zhu; Ying Wang; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

MtDNA genomes reveal a relaxation of selective constraints in low-BMI individuals in a Uyghur population - Hong-Xiang Zheng; Lei Li; Xiao-Yan Jiang; Shi Yan; Zhendong Qin; Xiaofeng Wang; Li Jin (Human Genetics, 2017)

Genome-wide identification, characterization, and expression analysis of SnRK2 family in Hevea brasiliensis - Dong Guo; Hui-Liang Li; Jia-Hong Zhu; Ying Wang; Feng An; Gui-Shui Xie; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Expression-based genotyping of the rice blast resistance genes in the elite maintainer line Yixiang1B - Li Wang; Xiao-Hong Hu; Gang Lin; De-Ming Zhao; Jun Shi; Zhi-Xue Zhao; Rui Zeng; Heng-Jing Li; De-Qiang Li; Jing Fan; Yan Li; Fu Huang; et al. (European Journal of Plant Pathology, 2017)

Phytochemicals and biological activities of Artemisia sieversiana - Shi-Jun Liu; Zhi-Xin Liao; Zhi-Shu Tang; Chun-Li Cui; Hong-Bo Liu; Yan-Ni Liang; Yu Zhang; Huan-Xian Shi; Yao-Run Liu (Phytochemistry Reviews, 2017)

The Role of Photoreceptors in Response to Cucumber Mosaic Virus in Arabidopsis thaliana - Xue Zhou; Tong Zhu; Li-Sha Zhu; Shi-Shuai Luo; Xing-Guang Deng; Hong-hui Lin; De-Hui Xi (Journal of Plant Growth Regulation, 2017)

Ne2 encodes protein(s) and the altered RuBisCO could be the proteomics leader of hybrid necrosis in wheat (Triticum aestivum L.) - Si Rui Pan; Xing Lai Pan; Qian Ying Pan; Yin Hong Shi; Li Zhang; Yun Fan; Yan Rui Xue (Journal of Genetics, 2017)

Colon-Targeted Delivery of IgY Against Clostridium difficile Toxin A and B by Encapsulation in Chitosan-Ca Pectinate Microbeads - Pingping Xing; Yanan Shi; Chuangchuang Dong; Hong Liu; Yan Cheng; Junbo Sun; Dalei Li; Min Li; Kaoxiang Sun; Dongxiao Feng (AAPS PharmSciTech, 2017)

Temporal and spatial distributions of PBDEs in atmosphere at Shanghai rural regions, China - Yun-Juan Zhu; Dan Sun; Nuo-Er Yang; Yong-Sheng Ding; Wei-Bing Feng; Wen-Jun Hong; Shi-Mao Zhu; Yi-Fan Li (Environmental Science and Pollution Research, 2017)

Identification of protein tyrosine phosphatase SHP-2 as a new target of perfluoroalkyl acids in HepG2 cells - Yu Yang; Qi-Yan Lv; Liang-Hong Guo; Bin Wan; Xiao-Min Ren; Ya-Li Shi; Ya-Qi Cai (Archives of Toxicology, 2017)

Delicaflavone induces autophagic cell death in lung cancer via Akt/mTOR/p70S6K signaling pathway - Yuxia Sui; Hong Yao; Shaoguang Li; Long Jin; Peiying Shi; Zhijun Li; Gang Wang; Shilan Lin; Youjia Wu; Yuxiang Li; Liying Huang; Qicai Liu; et al. (Journal of Molecular Medicine, 2017)

Outbreak of severe pseudorabies virus infection in pig-offal-fed farmed mink in Liaoning Province, China - Hao Liu; Xin-Tong Li; Bo Hu; Xiao-Yu Deng; Lei Zhang; Shi-Zhen Lian; Hai-Ling Zhang; Shuang Lv; Xiang-Hong Xue; Rong-Guang Lu; Ning Shi; Ming-Hao Yan; et al. (Archives of Virology, 2017)

Pilot Demonstration of Ceramic Membrane Ultrafiltration of Sugarcane Juice for Raw Sugar Production - Wen Li; Guo-Qing Ling; Chang-Rong Shi; Kai Li; Hai-Qin Lu; Fang-Xue Hang; Yu Zhang; Cai-Feng Xie; Deng-Jun Lu; Hong Li (Sugar Tech, 2017)

In vitro reprogramming of rat bmMSCs into pancreatic endocrine-like cells - Hong-Tu Li; Fang-Xu Jiang; Ping Shi; Tao Zhang; Xiao-Yu Liu; Xue-Wen Lin; Zhong-Yan San; Xi-Ning Pang (In Vitro Cellular & Developmental Biology - Animal, 2017)

Moisture increase in response to high-altitude warming evidenced by tree-rings on the southeastern Tibetan Plateau - Jinbao Li; Jiangfeng Shi; David D. Zhang; Bao Yang; Keyan Fang; Pak Hong Yue (Climate Dynamics, 2017)

Characterization of the whole chloroplast genome of Caragana microphylla Lam (Fabaceae) - Bing-bing Liu; Na Duan; Hong-li Zhang; Shuang Liu; Jian-wei Shi; Bao-feng Chai (Conservation Genetics Resources, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Netrin-1 Contributes to Myelinated Afferent Fiber Sprouting and Neuropathic Pain - Cai-Hua Wu; Xiao-Cui Yuan; Fang Gao; Hong-Ping Li; Jie Cao; Yan-Shen Liu; Wei Yu; Bo Tian; Xian-Fang Meng; Jing Shi; Hui-Lin Pan; Man Li (Molecular Neurobiology, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Design, synthesis, and evaluation of the anticonvulsant and antidepressant activities of pyrido[2,3-d]pyrimidine derivatives - Hong-Jian Zhang; Shi-Ben Wang; Xiang Wen; Jin-Zi Li; Zhe-Shan Quan (Medicinal Chemistry Research, 2016)

The Kuqa late Cenozoic fold–thrust belt on the southern flank of the Tian Shan Mountains - Yue-Jun Li; Lei Wen; Hong-An Zhang; Tai-Zhu Huang; Hui-Li Li; Yuan-Yuan Shi; Qing-Long Meng; Geng-Xin Peng; Shao-Ying Huang; Qiang Zhang (International Journal of Earth Sciences, 2016)

Identification of loci contributing to maize drought tolerance in a genome-wide association study - Nan Wang; Zhen-ping Wang; Xiao-ling Liang; Jian-feng Weng; Xiang-ling Lv; De-gui Zhang; Jie Yang; Hong-jun Yong; Ming-shun Li; Feng-hai Li; Li-yan Jiang; Shi-huang Zhang; et al. (Euphytica, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Alterations and correlations of the gut microbiome, metabolism and immunity in patients with primary biliary cirrhosis - Long‐Xian Lv; Dai‐Qiong Fang; Ding Shi; De‐Ying Chen; Ren Yan; Yi‐Xin Zhu; Yan‐Fei Chen; Li Shao; Fei‐Fei Guo; Wen‐Rui Wu; Ang Li; Hai‐Yan Shi; et al. (Environmental Microbiology, 2016)
Summary We selected 42 early‐stage primary biliary cirrhosis (PBC) patients and 30 healthy controls (HC). Metagenomic sequencing of the 16S rRNA gene was used to characterize the fecal microbiome. UPLC‐MS/MS assaying of small molecules was used to characterize the metabolomes of the serum, urine and feces. Liquid chip assaying of serum cytokines was used to characterize the immune profiles. The gut of PBC patients were depleted of some potentially beneficial bacteria, such as Acidobacteria, Lachnobacterium sp., Bacteroides eggerthii and Ruminococcus bromii , but were enriched in some bacterial taxa containing opportunistic pathogens, such as γ‐Proteobacteria, Enterobacteriaceae, Neisseriaceae, Spirochaetaceae , Veillonella , Streptococcus , Klebsiella , Actinobacillus pleuropneumoniae , Anaeroglobus geminatus , Enterobacter asburiae , Haemophilus parainfluenzae , Megasphaera micronuciformis and Paraprevotella clara . Several altered gut bacterial taxa exhibited potential interactions with PBC through their associations with altered metabolism, immunity and liver function indicators, such as those of Klebsiella with IL‐2A and Neisseriaceae with urinary indoleacrylate. Many gut bacteria, such as some members of Bacteroides, were altered in their associations with the immunity and metabolism of PBC patients, although their relative abundances were unchanged. Consequently, the gut microbiome is altered and may be critical for the onset or development of PBC by interacting with metabolism and immunity.

Semi-supervised least squares support vector machine algorithm: application to offshore oil reservoir - Wei-Ping Luo; Hong-Qi Li; Ning Shi (Applied Geophysics, 2016)

Facile microwave-assisted synthesis of benzimidazole scaffolds via Ugi-type three-component condensation (3CC) reactions - Gui-Ting Song; Zhi-Gang Xu; Dian-Yong Tang; Shi-Qiang Li; Zhi-Gang Xie; Hong-Liang Zhong; Zhi-Wei Yang; Jin Zhu; Jin Zhang; Zhong-Zhu Chen (Molecular Diversity, 2016)

Genetic variation in APE1 gene promoter is associated with noise-induced hearing loss in a Chinese population - Huanxi Shen; Jianrui Dou; Lei Han; Ying Bai; Qian Li; Zhiqiang Hong; Jian Shi; Hengdong Zhang; Feng Zhang; Cheng Du; Zhimin Tong; Baoli Zhu (International Archives of Occupational and Environmental Health, 2016)

One-step reverse transcription loop-mediated isothermal amplification assay for rapid detection of melon yellow spot virus - Rong Zeng; Li-hui Xu; Shi-gang Gao; Xiu-hong Ni; Chun-lei Chen; Jian-cai Chen; Fu-ming Dai (European Journal of Plant Pathology, 2016)

Human cytomegalovirus UL49 encodes an early, virion-associated protein essential for virus growth in human foreskin fibroblasts - Feng Zhu; Jian Yuan; Hong-Jian Li; Zhi-Feng Zeng; Zhi-Wen Luo; Shi-Qian Li; Chi-Qiang He; Xue-Fang Jia; Xin Zhang; Hui Zuo; Yi-Min Liu; Martin Chang; et al. (Archives of Virology, 2016)

Tracking bamboo dynamics in Zhejiang, China, using time-series of Landsat data from 1990 to 2014 - Mengna Li; Congcong Li; Hong Jiang; Chengyuan Fang; Jun Yang; Zhiliang Zhu; Lei Shi; Shirong Liu; Peng Gong (International Journal of Remote Sensing, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Use of flue gas desulfurization gypsum for leaching Cd and Pb in reclaimed tidal flat soil - Ping Yang; Xian Li; Ze-Jun Tong; Qu-Sheng Li; Bao-Yan He; Li-Li Wang; Shi-Hong Guo; Zhi-Min Xu (Environmental Science and Pollution Research, 2016)

Structural characterization and biological activities of two α-glucans from Radix Paeoniae Alba - Wuxia Zhang; Peng Li; Dan Song; Hong Niu; Songshan Shi; Shunchun Wang; Jinyou Duan (Glycoconjugate Journal, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Migration and transformation rule of heavy metals in sludge during hydrolysis for protein extraction - Yulong Li; Fei Xue; Jiebing Li; Shi hong Xu; Dengxin Li (Environmental Science and Pollution Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Synthesis of some new thiazolo[3,2-a]pyrimidine derivatives and screening of their in vitro antibacterial and antitubercular activities - Dong Cai; Zhi-Hua Zhang; Yu Chen; Xin-Jia Yan; Shi-Ti Zhang; Liang-Jing Zou; Li-Hong Meng; Fang Li; Bing-Jie Fu (Medicinal Chemistry Research, 2016)

Effects of freshwater leaching on potential bioavailability of heavy metals in tidal flat soils - Hui Li; Jun Lu; Qu-Sheng Li; Bao-Yan He; Xiu-Qin Mei; Dan-Ping Yu; Zhi-Min Xu; Shi-Hong Guo; Hui-Jun Chen (Environmental Geochemistry and Health, 2016)

An Empirical Method to Investigate the Spatial and Temporal Distribution of Annual Average Groundwater Recharge Intensity-a Case Study in Grand River, Michigan, USA - Zhang Jing; Lan-yue Zhang; Qin Xie; Yao Li; Shi-huai Deng; Fei Shen; Yuan-wei Li; Hong Xiao; Gang Yang; Chun Song (Water Resources Management, 2016)

Evidence for anaerobic ammonium oxidation process in freshwater sediments of aquaculture ponds - Li-dong Shen; Hong-sheng Wu; Zhi-qiu Gao; Yun-jie Ruan; Xiang-hua Xu; Ji Li; Shi-jie Ma; Pei-hui Zheng (Environmental Science and Pollution Research, 2016)

A novel Halomonas ventosae-specific virulent halovirus isolated from the Qiaohou salt mine in Yunnan, Southwest China - Chao-Qun Fu; Qin Zhao; Zhi-Ying Li; Yong-Xia Wang; Shi-Ying Zhang; Yong-Hong Lai; Wei Xiao; Xiao-Long Cui (Extremophiles, 2016)

Genipin-crosslinked, immunogen-reduced decellularized porcine liver scaffold for bioengineered hepatic tissue - Xiujuan Wu; Yujia Wang; Qiong Wu; Yi Li; Li Li; Jing Tang; Yujun Shi; Hong Bu; Ji Bao; Mingjun Xie (Tissue Engineering and Regenerative Medicine, 2015)

An ecological information analysis-based approach for assessing the sustainability of water use systems: a case study of the Huaihe River Basin, China - Reti Hai; Hong Shi; Bo Zhang; Yanan Zhai; Yuan Li; Weilong Wang (Clean Technologies and Environmental Policy, 2015)

Three new phenanthrenone constituents from Trigonostemon lii - Shi-Fei Li; Hong-Ping He; Xiao-Jiang Hao (Natural Product Research, 2015)

Autophagy regulates hyperoxia-induced intracellular accumulation of surfactant protein C in alveolar type II cells - Liang Zhang; Shuang Zhao; Li-Jie Yuan; Hong-Min Wu; Hong Jiang; Shi-Meng Zhao; Gang Luo; Xin-Dong Xue (Molecular and Cellular Biochemistry, 2015)

Endogenous hydrogen sulfide regulated by calcium is involved in thermotolerance in tobacco Nicotiana tabacum L. suspension cell cultures - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Ling Wen; Bing-Yu Zhu; Xiong Min (Acta Physiologiae Plantarum, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Molecular characterization of HbCZF1, a Hevea brasiliensis CCCH-type zinc finger protein that regulates hmg1 - Dong Guo; Hong-Yan Yi; Hui-Liang Li; Chen Liu; Zi-Ping Yang; Shi-Qing Peng (Plant Cell Reports, 2015)

Enzymatic hydrolysis of 7-xylosyltaxanes by an extracellular xylosidase from Cellulosimicrobium cellulans - Tong-Yi Dou; Hong-Wei Luan; Xing-Bao Liu; Shi-Yang Li; Xun-Fu Du; Ling Yang (Biotechnology Letters, 2015)

Interactive effects of light, nitrogen source, and carbon dioxide on energy metabolism in the diatom Thalassiosira pseudonana - Dalin Shi; Weiying Li; Brian M. Hopkinson; Haizheng Hong; Dongmei Li; Shuh‐Ji Kao; Wenfang Lin (Limnology and Oceanography, 2015)
Due to the ongoing effects of climate change, phytoplankton are likely to experience enhanced irradiance, more reduced nitrogen, and increased water acidity in the future ocean. Here, we used Thalassiosira pseudonana as a model organism to examine how phytoplankton adjust energy production and expenditure to cope with these multiple, interrelated environmental factors. Following acclimation to a matrix of irradiance, nitrogen source, and CO 2 levels, the diatom's energy production and expenditures were quantified and incorporated into an energetic budget to predict how photosynthesis was affected by growth conditions. Increased light intensity and a shift from to led to increased energy generation, through higher rates of light capture at high light and greater investment in photosynthetic proteins when grown on . Secondary energetic expenditures were adjusted modestly at different culture conditions, except that utilization was systematically reduced by increasing p CO 2 . The subsequent changes in element stoichiometry, biochemical composition, and release of dissolved organic compounds may have important implications for marine biogeochemical cycles. The predicted effects of changing environmental conditions on photosynthesis, made using an energetic budget, were in good agreement with observations at low light, when energy is clearly limiting, but the energetic budget over‐predicts the response to at high light, which might be due to relief of energetic limitations and/or increased percentage of inactive photosystem II at high light. Taken together, our study demonstrates that energetic budgets offered significant insight into the response of phytoplankton energy metabolism to the changing environment and did a reasonable job predicting them.

Protective effects of vascular endothelial growth factor in cultured brain endothelial cells against hypoglycemia - Fei Zhao; Jiangshan Deng; Xiaoyan Yu; Dawei Li; Hong Shi; Yuwu Zhao (Metabolic Brain Disease, 2015)

Involvement of sulfhydryl compounds and antioxidant enzymes in H2S-induced heat tolerance in tobacco (Nicotiana tabacum L.) suspension-cultured cells - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Tao Chen (In Vitro Cellular & Developmental Biology - Plant, 2015)

Numerical simulation on slope stability analysis considering anisotropic properties of layered fractured rocks: a case study - Tian-hong Yang; Wen-hao Shi; Pei-tao Wang; Hong-lei Liu; Qing-lei Yu; Yang Li (Arabian Journal of Geosciences, 2015)

Chemical constituents from Piper wallichii - Yan-Ni Shi; Lian Yang; Jin-Hua Zhao; Yi-Ming Shi; Yan Qu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Xing-Cong Li; Min Xu; Ying-Jun Zhang (Natural Product Research, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Water relations and gas exchange of fan bryophytes and their adaptations to microhabitats in an Asian subtropical montane cloud forest - Liang Song; Yong-Jiang Zhang; Xi Chen; Su Li; Hua-Zheng Lu; Chuan-Sheng Wu; Zheng-Hong Tan; Wen-Yao Liu; Xian-Meng Shi (Journal of Plant Research, 2015)

Characterization of polymorphic microsatellite markers and genetic diversity in the Hong Kong oyster Crassostrea hongkongensis using paired-end Illumina shotgun sequencing - Xuelin Zhao; Huitong Shi; Hong Yu; Qi Li (Genes & Genomics, 2015)

Endophytic microbes Bacillus sp. LZR216-regulated root development is dependent on polar auxin transport in Arabidopsis seedlings - Jianfeng Wang; Yongqiang Zhang; Ying Li; Xiaomin Wang; Wenbin Nan; Yanfeng Hu; Hong Zhang; Chengzhou Zhao; Feng Wang; Ping Li; Hongyong Shi; Yurong Bi (Plant Cell Reports, 2015)

Distribution of Yeast Isolates from Invasive Infections and Their In Vitro Susceptibility to Antifungal Agents: Evidence from 299 Cases in a 3-Year (2010 to 2012) Surveillance Study - Wei Li; Yu-an Hu; Fang-qiu Li; Li-ning Shi; Hai-feng Shao; Mei Huang; Ying Wang; Dan-dan Han; Hong Liao; Chun-fang Ma; Guo-yong Zhang (Mycopathologia, 2015)

Effects of heat stress on serum insulin, adipokines, AMP-activated protein kinase, and heat shock signal molecules in dairy cows - Li Min; Jian-bo Cheng; Bao-lu Shi; Hong-jian Yang; Nan Zheng; Jia-qi Wang (Journal of Zhejiang University-SCIENCE B, 2015)

Expression of Cyclooxygenase-2 in Squamous Cell Carcinoma and Keratoacanthoma and its Clinical Significance - Hai-Kang Hua; Cheng Jin; Li-Jia Yang; Shi-Qin Tao; Xiao-Hong Zhu (Cell Biochemistry and Biophysics, 2015)

Arthroscopic Characteristics of Normal and Discoid Meniscus Injury, and Efficiency of Recovery in Each Type of Meniscus Injury - Xiao Ouyang; Bo Wei; Shi Dong Hong; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Establishment and maintenance of a standardized glioma tissue bank: Huashan experience - Abudumijiti Aibaidula; Jun-feng Lu; Jin-song Wu; He-jian Zou; Hong Chen; Yu-qian Wang; Zhi-yong Qin; Yu Yao; Ye Gong; Xiao-ming Che; Ping Zhong; Shi-qi Li; et al. (Cell and Tissue Banking, 2015)

A small-world-based population encoding model of the primary visual cortex - Li Shi; Xiaoke Niu; Hong Wan; Zhigang Shang; Zhizhong Wang (Biological Cybernetics, 2015)

Data mining and well logging interpretation: application to a conglomerate reservoir - Ning Shi; Hong-Qi Li; Wei-Ping Luo (Applied Geophysics, 2015)

Determination of tumorigenic Agrobacterium density in soil by real-time PCR assay and its effect on crown gall disease severity - Qian Li; Rong-Jun Guo; Shi-Dong Li; Shi-Fang Li; Hong-Qing Wang (European Journal of Plant Pathology, 2015)

Endogenous nitric oxide in Pseudomonas fluorescens ZY2 as mediator against the combined exposure to zinc and cefradine - Yan-Bin Xu; Yan Zhou; Jing-Jing Ruan; Shi-Hui Xu; Ji-Dong Gu; Shao-Song Huang; Li Zheng; Bao-Hong Yuan; Li-Hua Wen (Ecotoxicology, 2015)

Effect of the small-world structure on encoding performance in the primary visual cortex: an electrophysiological and modeling analysis - Li Shi; Xiaoke Niu; Hong Wan (Journal of Comparative Physiology A, 2015)

Three-dimensional spheroid culture of human umbilical cord mesenchymal stem cells promotes cell yield and stemness maintenance - Yi Li; Gang Guo; Li Li; Fei Chen; Ji Bao; Yu-jun Shi; Hong Bu (Cell and Tissue Research, 2015)

An ATP-dependent protease homolog ensures basic standards of survival and pathogenicity for Magnaporthe oryzae - Jian Li; Xilong Liang; Yi Wei; Jinliang Liu; Fucheng Lin; Shi-Hong Zhang (European Journal of Plant Pathology, 2015)

Phylogenetic and recombination analysis of rice black-streaked dwarf virus segment 9 in China - Yu Zhou; Jian-Feng Weng; Yan-Ping Chen; Chang-Lin Liu; Xiao-Hua Han; Zhuan-Fang Hao; Ming-Shun Li; Hong-Jun Yong; De-Gui Zhang; Shi-Huang Zhang; Xin-Hai Li (Archives of Virology, 2015)

A new daphnane diterpenoid from Excoecaria venenata with inhibitory effect on human leukaemia HL-60 cells - De-Sheng Ning; Li-Yan Peng; Shi-Hong Lv; Dian-Peng Li; Zheng-Hong Pan (Natural Product Research, 2015)

Enhanced Phytoextraction of Heavy Metals from Contaminated Soil by Plant Co-cropping Associated with PGPR - Zhi-feng Liu; Hong-guang Ge; Chen Li; Zuo-ping Zhao; Feng-min Song; Shi-bin Hu (Water, Air, & Soil Pollution, 2015)

Effects of HAb18G/CD147 Knockout on Hepatocellular Carcinoma Cells In Vitro Using a Novel Zinc-Finger Nuclease-Targeted Gene Knockout Approach - Hong-Wei Li; Xiang-Min Yang; Juan Tang; Shi-Jie Wang; Zhi-Nan Chen; Jian-Li Jiang (Cell Biochemistry and Biophysics, 2015)

Comparison of chemical, electrical, and combined activation methods for in vitro matured porcine oocytes - Shuai Liu; Kuiqing Cui; Hong Li Li; Jun Ming Sun; Xing Rong Lu; Kai Yuan Shen; Qing You Liu; De Shun Shi (In Vitro Cellular & Developmental Biology - Animal, 2015)

Primary succession of soil enzyme activity and heterotrophic microbial communities along the chronosequence of Tianshan Mountains No. 1 Glacier, China - Jun Zeng; Xiao-xia Wang; Kai Lou; Moniruzzaman Khan Eusufzai; Tao Zhang; Qing Lin; Ying-wu Shi; Hong-mei Yang; Zhong-qing Li (Antonie van Leeuwenhoek, 2015)

Characterization of four hemocyanin isoforms in Litopenaeus vannamei - Jingxiang Xu; Lingwei Ruan; Zhen Li; Xiaoman Yu; Sedong Li; Hong Shi; Xun Xu (Acta Oceanologica Sinica, 2015)

Effects of rapamycin against paraquat-induced pulmonary fibrosis in mice - Xue Shao; Meng Li; Chong Luo; Ying-ying Wang; Ying-ying Lu; Shi Feng; Heng Li; Xia-bing Lang; Yu-cheng Wang; Chuan Lin; Xiu-jin Shen; Qin Zhou; et al. (Journal of Zhejiang University-SCIENCE B, 2015)

Influence of PTGS1, PTGFR, and MRP4 genetic variants on intraocular pressure response to latanoprost in Chinese primary open-angle glaucoma patients - Li-chen Gao; Di Wang; Fang-qun Liu; Zheng-yu Huang; Hong-guang Huang; Gui-hua Wang; Xi Chen; Qun-zhi Shi; Li Hong; Li-ping Wu; Jie Tang (European Journal of Clinical Pharmacology, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Experimental Study of the Effect on Bone Metabolism and Bone Histomorphometry of Osteoporosis Rats with Birdpecking and Revolving Moxibustion on Twelve Back-Shu Points - Hong-Shi Zhang; Tie Li; Xing-Shan Liu; Fu-Chun Wang; Xin Yao; Li Yan; Wu-Jin Liang (Cell Biochemistry and Biophysics, 2015)

Unsupervised change detection based on robust chi-squared transform for bitemporal remotely sensed images - Aiye Shi; Du Q. Huynh; Feng Chen Huang; Shao Hong Shen; Wen Ping Lu; Zhen Li Ma (International Journal of Remote Sensing, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Using hourly measurements to explore the role of secondary inorganic aerosol in PM2.5 during haze and fog in Hangzhou, China - Roeland Cornelis Jansen; Yang Shi; Jianmin Chen; YunJie Hu; Chang Xu; Shengmao Hong; Jiao Li; Min Zhang (Advances in Atmospheric Sciences, 2014)

Multiple correlations of mRNA expression and protein abundance in human cytokine profile - Hong-wu Du; Guang-yu Chen; Chun-he Yang; Chuan-bao Li; Yi-ping Xun; Jia Liu; Peng Chen; Li-li Shi (Molecular Biology Reports, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Expression of bioactive porcine interferon-alpha in Lactobacillus casei - Shi-jie Ma; Kun Li; Xin-Sheng Li; Xiao-Qing Guo; Peng-Fei Fu; Ming-Fan Yang; Hong-Ying Chen (World Journal of Microbiology and Biotechnology, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Soil Heavy Metal Contamination and Risk Assessment Around the Fenhe Reservoir, China - Hong Zhang; Guanglei Liu; Wei Shi; Jinchang Li (Bulletin of Environmental Contamination and Toxicology, 2014)

A Novel Risk Haplotype of ALOX5AP Gene is Associated with Ischemic Stroke in Chinese Han Population - Dongzhi Yang; Ying He; Manyu Li; Congcong Shi; Guoying Song; Qing Wang; Yujia Fan; Qingchuan Feng; Hong Zheng (Journal of Molecular Neuroscience, 2014)

Icariin-Mediated Inhibition of NF-κB Activity Enhances the In Vitro and In Vivo Antitumour Effect of 5-Fluorouracil in Colorectal Cancer - De-Bing Shi; Xin-Xiang Li; Hong-Tu Zheng; Da-Wei Li; Guo-Xiang Cai; Jun-Jie Peng; Wei-Lie Gu; Zu-Qing Guan; Ye Xu; San-Jun Cai (Cell Biochemistry and Biophysics, 2014)

Urinary Perchlorate Exposure and Risk in Women of Reproductive Age in a Fireworks Production Area of China - Qin Li; Yun-jiang Yu; Fei-fei Wang; Shi-wu Chen; Yan Yin; Hai-peng Lin; Fei Che; Peng Sun; Juan Qin; Jie Liu; Hong-mei Wang (Archives of Environmental Contamination and Toxicology, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Biological control of Ralstonia wilt, Phytophthora blight, Meloidogyne root-knot on bell pepper by the combination of Bacillus subtilis AR12, Bacillus subtilis SM21 and Chryseobacterium sp. R89 - Hong-Xia Liu; Shi-Mo Li; Yu-Ming Luo; Lai-Xin Luo; Jian-Qiang Li; Jian-Hua Guo (European Journal of Plant Pathology, 2014)

Mega-shoaling in carbonate platform of the Middle Triassic Leikoupo Formation, Sichuan Basin, southwest China - XiuCheng Tan; Ling Li; Hong Liu; Jian Cao; XiaoQing Wu; SuYan Zhou; XueWen Shi (Science China Earth Sciences, 2014)

Nesfatin-1 Decreases Excitability of Dopaminergic Neurons in the Substantia Nigra - Chen Li; Fang Zhang; Limin Shi; Haoyun Zhang; Zibin Tian; Junxia Xie; Hong Jiang (Journal of Molecular Neuroscience, 2014)

Artificial antigen synthesis and the development of polyclonal antibody-based immunoassay for citreoviridin determination - Zhen Hong Zhuang; Shan Jin Que; Yue Ming Gao; Jun Yuan; Zhou Ye; Min Du; Guang Mei Lin; Li Cai Liu; Shi Hua Wang (World Journal of Microbiology and Biotechnology, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Sirt1 Promotes Axonogenesis by Deacetylation of Akt and Inactivation of GSK3 - Xiao-hong Li; Chong Chen; Yue Tu; Hong-tao Sun; Ming-liang Zhao; Shi-xiang Cheng; Yang Qu; Sai Zhang (Molecular Neurobiology, 2013)

Construction and Characterization of a CTLA-4-Targeted scFv–Melittin Fusion Protein as a Potential Immunosuppressive Agent for Organ Transplant - Hailong Jin; Congran Li; Ding Li; Ming Cai; Zhouli Li; Shuang Wang; Xin Hong; Bingyi Shi (Cell Biochemistry and Biophysics, 2013)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Definition of Management Zones for Enhancing Cultivated Land Conservation Using Combined Spatial Data - Yan Li; Zhou Shi; Hao-Xiang Wu; Feng Li; Hong-Yi Li (Environmental Management, 2013)

6-Hydroxydopamine promotes iron traffic in primary cultured astrocytes - Hao-Yun Zhang; Nai-Dong Wang; Ning Song; Hua-Min Xu; Li-Min Shi; Hong Jiang; Jun-Xia Xie (BioMetals, 2013)

Role of Endoplasmic Reticulum Stress in Aberrant Activation of Fluoride-Treated Osteoblasts - Yu-lai Zhou; Hong-yan Shi; Xi-ning Li; Peng Lv; Guang-sheng Li; Qin-yi Liu; Hui Xu (Biological Trace Element Research, 2013)

Genomic sequence analysis of a new reassortant infectious bursal disease virus from commercial broiler flocks in central China - Pei Cui; Shi-Jie Ma; Yu-Geng Zhang; Xin-Sheng Li; Xiao-Yun Gao; Bao-An Cui; Hong-Ying Chen (Archives of Virology, 2013)

Association of PON1 genotype and haplotype with susceptibility to coronary artery disease and clinical outcomes in dual antiplatelet-treated Han Chinese patients - Yan-Hong Kang; Hai-Yan Lao; Hong Wu; Wei-Hua Lai; Xin-Xin Li; Xi-Yong Yu; Ji-Yan Chen; Shi-Long Zhong (European Journal of Clinical Pharmacology, 2013)

Effects of Norepinephrine on Immune Functions of Cultured Splenic Lymphocytes Exposed to Aluminum Trichloride - Ji-Hong Zhang; Chong-Wei Hu; Yan-Zhu Zhu; Shi-Min Liu; Chong-Sheng Bai; Yan-Fei Han; Shi-Liang Xia; Yan-Fei Li (Biological Trace Element Research, 2013)

Hydrological characteristics of vegetated river flows: a laboratory flume study - John Z. Shi; Yan-Hong Li; Jocelyne M.R. Hughes; Ming Zhao (Hydrological Sciences Journal, 2013)

Re-Examination of the Genotoxic Activity of Water Taken From the Songhua River in P. R. China - Jia Yu; Hong-Wei Dong; Li-Tian Shi; Hui-Ling Jiang; Jian-Wen Yu; Qian-Wen Zhao; Shi-Chun Cai; Dan Han; Xuan-Yue Tang; Jia-Ren Liu (Archives of Environmental Contamination and Toxicology, 2013)

Proteomic and physiological analyses reveal detoxification and antioxidation induced by Cd stress in Kandelia candel roots - Zhao-Xia Weng; Ling-Xia Wang; Fang-lin Tan; Li Huang; Jian-Hong Xing; Shi-Pin Chen; Chi-Lien Cheng; Wei Chen (Trees, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

Effects of zinc-substituted nano-hydroxyapatite coatings on bone integration with implant surfaces - Shi-fang Zhao; Wen-jing Dong; Qiao-hong Jiang; Fu-ming He; Xiao-xiang Wang; Guo-li Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Analysis of genetic diversity of Ruthenia Medic (Medicago ruthenica (L.) Trautv.) in Inner Mongolia using ISSR and SSR markers - Hong-yan Li; Zhi-yong Li; Li-yan Cai; Wen-gui Shi; Fu-gui Mi; Feng-ling Shi (Genetic Resources and Crop Evolution, 2013)

Isolation and characterization of three fungi with the potential of transforming glycyrrhizin - Chao Wang; Xiao-Xiao Guo; Xiao-Yan Wang; Feng Qi; Shi-Jiang Feng; Chun Li; Xiao-Hong Zhou (World Journal of Microbiology and Biotechnology, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

OCPs and PCBs in Marine Edible Fish and Human Health Risk Assessment in the Eastern Guangdong, China - Jingchun Shi; Yuelin Li; Hong Liang; Gene J. Zheng; Yinglin Wu; Wenhua Liu (Archives of Environmental Contamination and Toxicology, 2013)

Isolation and identification of a wheat gene encoding a zinc finger protein (TaZnFP) responsive to abiotic stresses - Dong-Hong Min; Yue Zhao; Dong-Ying Huo; Lian-Cheng Li; Ming Chen; Zhao-Shi Xu; You-Zhi Ma (Acta Physiologiae Plantarum, 2013)

Flow Karyotyping of Wheat Addition Line “T240” with a Haynaldia villosa 6VS Telosome - Dong-wei Guo; Dong-hong Min; Zhao-shi Xu; Ming Chen; Lian-cheng Li; Muhammad Ashraf; Abdul Ghafoor; You-zhi Ma (Plant Molecular Biology Reporter, 2013)

Reduced expression of aquaporin 9 in tubal ectopic pregnancy - Yin Fen Ji; Li You Chen; Kai Hong Xu; Ji Fen Yao; Yi Fu Shi; Xue Jun Shanguan (Journal of Molecular Histology, 2013)

In vitro isolation and cultivation of rabbit tracheal epithelial cells using tissue explant technique - Hong-Can Shi; Dan Lu; Hai-Jia Li; Shi Han; Yan-Jun Zeng (In Vitro Cellular & Developmental Biology - Animal, 2013)

Potential Prevention and Treatment of Maifanite for Alzheimer's Disease Based on Behavior Test, Oxidative Stress Assay, and Trace Element Analysis in Hippocampus of Aβ(25–35)-Induced AD Rats - Ling-Feng Jiang; Hai-Lin Liao; Hong-Miao Huang; Li-Xia Zhou; Ling Li; Shi-Xian Cheng; Cheng-Zhi Du (Biological Trace Element Research, 2013)

Erratum to: Effect of oxygen free radicals and nitric oxide on apoptosis of immune organ induced by selenium deficiency in chickens - Zi-wei Zhang; Jiu-li Zhang; Yu-hong Gao; Qiao-hong Wang; Shu Li; Xiao-long Wang; Shi-wen Xu (BioMetals, 2013)

Effect of oxygen free radicals and nitric oxide on apoptosis of immune organ induced by selenium deficiency in chickens - Zi-wei Zhang; Jiu-li Zhang; Yu-hong Zhang; Qiao-hong Wang; Shu Li; Xiao-long Wang; Shi-wen Xu (BioMetals, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Molecular cloning and sequence analysis of methionine adenosyltransferase from the economic seaweed Undaria pinnatifida - Kun Qiao; Shi Guo Li; Hong Yan Li; Shao Ming Tong; He Sheng Hou (Journal of Applied Phycology, 2013)

Manganese-Induced Effects on Testicular Trace Element Levels and Crucial Hormonal Parameters of Hyline Cocks - Xiao-fei Liu; Li-ming Zhang; Ziwei Zhang; Ning Liu; Shi-wen Xu; Hong-jin Lin (Biological Trace Element Research, 2013)

Plant-Soil Feedbacks and Soil Sickness: From Mechanisms to Application in Agriculture - Li-Feng Huang; Liu-Xia Song; Xiao-Jian Xia; Wei-Hua Mao; Kai Shi; Yan-Hong Zhou; Jing-Quan Yu (Journal of Chemical Ecology, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Low nitrogen-induced expression of cyclophilin in Nicotiana tabacum - Huijuan Yang; Li Xu; Hong Cui; Boxiong Zhong; Guoshun Liu; Hongzhi Shi (Journal of Plant Research, 2013)

Induction Kinetics of a Novel Stress-related LEA Gene in Wheat - Dong-Hong Min; Xiao-Hong Zhang; Zhao-Shi Xu; Yue Zhao; Yang Chen; Lian-Cheng Li; Ming Chen; You-Zhi Ma (Plant Molecular Biology Reporter, 2012)

Effects of Oxidative Stress on Immunosuppression Induced by Selenium Deficiency in Chickens - Zi-wei Zhang; Qiao-hong Wang; Jiu-li Zhang; Shu Li; Xiao-Long Wang; Shi-wen Xu (Biological Trace Element Research, 2012)

Polymorphisms of the interleukin-15 gene and their associations with fatness and muscle fiber traits in chickens - Shi-Jie Lv; Ling Su; Hong Li; Rui-Li Han; Gui-Rong Sun; Xiang-Tao Kang (Journal of Applied Genetics, 2012)

Clinical significance of detection of antibodies to fetal and adult acetylcholine receptors in myasthenia gravis - Qi-Guang Shi; Zhi-Hong Wang; Xiao-Wei Ma; Da-Qi Zhang; Chun-Sheng Yang; Fu-Dong Shi; Li Yang (Neuroscience Bulletin, 2012)

Perifosine as potential anti-cancer agent inhibits proliferation, migration, and tube formation of human umbilical vein endothelial cells - Feng Ze Wang; Hong Rong Fei; Xiao Qian Li; Renjiu Shi; De Cai Wang (Molecular and Cellular Biochemistry, 2012)

Microsatellite markers developed for the multi-ocellated racerunner, Eremias multiocellata (Lacertidae) - Lian Chen; Jia Guo; Zong-Shi Zhou; Hong Li (Conservation Genetics Resources, 2012)

Decadal variations in the season advancement of spring water cycle over Eastern China - RuiXia Zhao; Hong Zhang; GuoXiong Wu; WeiPing Li; AiLi Shi (Science China Earth Sciences, 2012)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Three new secolignan glycosides from Urtica fissa E. Pritz - Bao-min Feng; Hai-hong Qin; Hui-guo Wang; Li-ying Shi; Da-yong Yu; Bao-quan Ji; Qi Zhao; Yong-qi Wang (Journal of Natural Medicines, 2012)

EGFR-mediated G1/S transition contributes to the multidrug resistance in breast cancer cells - Shu-Jun Chen; Jing Luan; Hai-Shi Zhang; Can-Ping Ruan; Xin-Yun Xu; Qing-Quan Li; Nian-Hong Wang (Molecular Biology Reports, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

An Acyl–acyl Carrier Protein Thioesterase Gene Isolated from Wintersweet (Chimonanthus praecox), CpFATB, Enhances Drought Tolerance in Transgenic Tobacco (Nicotiana tobaccum) - Li-Hong Zhang; Baolei Jia; Ren-Ying Zhuo; Jin-Liang Liu; Hong-Yu Pan; Timothy C. Baldwin; Shi-Hong Zhang (Plant Molecular Biology Reporter, 2012)

TNF-α Increases Bone Marrow Mesenchymal Stem Cell Migration to Ischemic Tissues - Qiong Xiao; Shi-kun Wang; Hua Tian; Li Xin; Zhi-geng Zou; Yan-lai Hu; Cui-ming Chang; Xue-ying Wang; Qun-sheng Yin; Xiang-hong Zhang; Li-yan Wang (Cell Biochemistry and Biophysics, 2012)

Influence of acute cadmium exposure on the liver proteome of a teleost fish, ayu (Plecoglossus altivelis) - Xin-Jiang Lu; Jiong Chen; Zuo-An Huang; Li Zhuang; Li-Zhen Peng; Yu-Hong Shi (Molecular Biology Reports, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

XPA A23G polymorphism and lung cancer risk: a meta-analysis - Ji-Hong Zou; Li An; Shi Chen; Li-Qun Ren (Molecular Biology Reports, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

Expression of β1,3-N-acetylglucosaminyltransferases during differentiation of human acute myeloid leukemia cells - Hao Qiu; Shi-Liang Wu; Xiang-Hong Guo; Hong-Jie Shen; Huan-Ping Zhang; Hui Li Chen (Molecular and Cellular Biochemistry, 2011)

Gastric motility functional study based on electrical bioimpedance measurements and simultaneous electrogastrography - Zhang-yong Li; Chao-shi Ren; Shu Zhao; Hong Sha; Juan Deng (Journal of Zhejiang University-SCIENCE B, 2011)

Overexpression of a cytosolic glyceraldehyde-3-phosphate dehydrogenase gene OsGAPC3 confers salt tolerance in rice - Xiu-Hong Zhang; Xiao-Lan Rao; Hai-Tao Shi; Rong-Jun Li; Ying-Tang Lu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Environmental Lead Exposure Among Children in Chengdu, China, 2007–2009 - Hua Shi; Yong-mei Jiang; Jia-yuan Li; Fang Liu; Hong Wang; Fan Yu; Hui Yang (Biological Trace Element Research, 2011)

Halomonas qijiaojingensis sp. nov. and Halomonas flava sp. nov., two moderately halophilic bacteria isolated from a salt lake - Chao Chen; Rong Shi; Bing-Bing Liu; Yun-Jiao Zhang; Hong-Zhuan Sun; Chang-Tian Li; Shu-Kun Tang; Li-Li Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2011)

MED19 promotes proliferation and tumorigenesis of lung cancer - Mei Sun; Rui Jiang; Jin-dong Li; Shu-li Luo; Hong-Wen Gao; Cheng-yan Jin; Dong-lei Shi; Chun-guang Wang; Bin Wang; Xing-yi Zhang (Molecular and Cellular Biochemistry, 2011)

Molecular cloning, characterization and mRNA expression analysis of a novel selenoprotein: avian selenoprotein W from chicken - Jin-Long Li; Hong-Feng Ruan; Hui-Xin Li; Shu Li; Shi-Wen Xu; Zhao-Xin Tang (Molecular Biology Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Polymorphisms of the prion protein gene and their effects on litter size and risk evaluation for scrapie in Chinese Hu sheep - Feng Guan; Lei Pan; Jie Li; Hong Tang; Cheng Zhu; Guoqing Shi (Virus Genes, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Degradation of dye rhodamine B under visible irradiation with Prussian blue as a photo-Fenton reagent - Shou-Qing Liu; Shi Cheng; Li Luo; Hong-Ying Cheng; Song-Jun Wang; Shuai Lou (Environmental Chemistry Letters, 2011)

Leaf anatomical structures of Paphiopedilum and Cypripedium and their adaptive significance - Zhi-Jie Guan; Shi-Bao Zhang; Kai-Yun Guan; Shu-Yun Li; Hong Hu (Journal of Plant Research, 2011)

Expression, purification, and characterization of recombinant human hypoxia inducible factor 1α in E.coli - Rutong Yu; Xueyuan Li; Xiuping Zhou; Qiong Shi; Hong Tang (World Journal of Microbiology and Biotechnology, 2011)

Efficacy and safety of escitalopram versus citalopram in major depressive disorder: a 6-week, multicenter, randomized, double-blind, flexible-dose study - Jian-Jun Ou; Guang-Lei Xun; Ren-Rong Wu; Le-Hua Li; Mao-Sheng Fang; Hong-Geng Zhang; Shi-Ping Xie; Jian-Guo Shi; Bo Du; Xue-Qin Yuan; Jing-Ping Zhao (Psychopharmacology, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Effects of nitrogen form on growth, CO2 assimilation, chlorophyll fluorescence, and photosynthetic electron allocation in cucumber and rice plants - Yan-hong Zhou; Yi-li Zhang; Xue-min Wang; Jin-xia Cui; Xiao-jian Xia; Kai Shi; Jing-quan Yu (Journal of Zhejiang University-SCIENCE B, 2011)

Pseudonocardia sichuanensis sp. nov., a novel endophytic actinomycete isolated from the root of Jatropha curcas L. - Sheng Qin; Ke Xing; Shi-Min Fei; Qiang Lin; Xiu-Min Chen; Cheng-Liang Cao; Yong Sun; Yun Wang; Wen-Jun Li; Ji-Hong Jiang (Antonie van Leeuwenhoek, 2011)

Genetic analysis of starch paste viscosity parameters in glutinous rice (Oryza sativa L.) - Chang-Jie Yan; Zhi-Xi Tian; Yu-Wei Fang; Ya-Chun Yang; Jian Li; Sheng-Yuan Zeng; Shi-Liang Gu; Chen-Wu Xu; Shu-Zhu Tang; Ming-Hong Gu (Theoretical and Applied Genetics, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Clinicopathological features of atypical lipomatous tumors of the laryngopharynx - Huai-yin Shi; Li-xin Wei; Hong-tian Wang; Lu Sun (Journal of Zhejiang University-SCIENCE B, 2010)

Assessing the combination effects of environmental estrogens in fish - Hui Zhang; Fan-Xiang Kong; Yang Yu; Xiao-Li Shi; Min Zhang; Hong-Er Tian (Ecotoxicology, 2010)

Association between NMDA receptor subunit 2b gene polymorphism and Alzheimer’s disease in Chinese Han population in Shanghai - Chao Chen; Xia Li; Tao Wang; Hai-Hong Wang; Yi Fu; Lei Zhang; Shi-Fu Xiao (Neuroscience Bulletin, 2010)

Corpus Callosum: a Favorable Target for rSFV-Mediated Gene Transfer to Rat Brain with Broad and Efficient Expression - Zhao-Jian Li; Peng Sun; Hong-Di Zhang; Shi-Fang Li; Xia Liu; Ren-Zhi Wang (Journal of Molecular Neuroscience, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Potential Carbon Mineralization of Permafrost Peatlands in Great Hing’an Mountains, China - Xianwei Wang; Xiuzhen Li; Yuanman Hu; Jiujun Lü; Ju Sun; Zongmei Li; Hong Shi He (Wetlands, 2010)

Co-culture with cardiomyocytes enhanced the myogenic conversion of mesenchymal stromal cells in a dose-dependent manner - Xiao-qing He; Min-sheng Chen; Shu-Hong Li; Shi-ming Liu; Yun Zhong; Heather Y. McDonald Kinkaid; Wei-Yang Lu; Richard D. Weisel; Ren-Ke Li (Molecular and Cellular Biochemistry, 2010)

Effects of Ginkgo biloba extracts on diazepam metabolism: a pharmacokinetic study in healthy Chinese male subjects - Xiao-Cong Zuo; Bi-Kui Zhang; Su-Jie Jia; Shi-Kun Liu; Ling-Yun Zhou; Jing Li; Jie Zhang; Ling-Ling Dai; Ben-Mei Chen; Guo-Ping Yang; Hong Yuan (European Journal of Clinical Pharmacology, 2010)

Type IV Pili of Acidithiobacillus ferrooxidans Are Necessary for Sliding, Twitching Motility, and Adherence - Yong-Quan Li; Dong-Shi Wan; Shuang-Sheng Huang; Fei-Fan Leng; Lei Yan; Yong-Qing Ni; Hong-Yu Li (Current Microbiology, 2010)

Brassinosteroids promote photosynthesis and growth by enhancing activation of Rubisco and expression of photosynthetic genes in Cucumis sativus - Xiao-Jian Xia; Li-Feng Huang; Yan-Hong Zhou; Wei-Hua Mao; Kai Shi; Jian-Xiang Wu; Tadao Asami; Zhixiang Chen; Jing-Quan Yu (Planta, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Isolation and characterization of 15 microsatellite markers from wild tea plant (Camellia taliensis) using FIASCO method - Jun-Bo Yang; Jing Yang; Hong-Tao Li; Yu Zhao; Shi-Xiong Yang (Conservation Genetics, 2009)

Takayasu’s arteritis associated with Crohn’s disease - You-shi Liu; You-hong Fang; Ling-xiang Ruan; You-ming Li; Lin Li; Ling-ling Jiang (Journal of Zhejiang University-SCIENCE B, 2009)

Competitive replication of different genotypes of infectious bursal disease virus on chicken embryo fibroblasts - Lixue Shi; Haibin Li; Guangpeng Ma; Jiyong Zhou; Lianlian Hong; Xiaojuan Zheng; Yongping Wu; Yongzhi Wang; Yan Yan (Virus Genes, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Osteogenic differentiation of mesenchymal stem cells promoted by overexpression of connective tissue growth factor - Jin-jing Wang; Feng Ye; Li-jia Cheng; Yu-jun Shi; Ji Bao; Huai-qiang Sun; Wei Wang; Peng Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Substitutions of 169Lys and 173Thr in nonstructural protein 1 influence the infectivity and pathogenicity of XJ-160 virus - Wu-yang Zhu; Yi-liang Yang; Shi-hong Fu; Li-hua Wang; You-gang Zai; Qing Tang; Guo-dong Liang (Archives of Virology, 2009)

The effects of soy isoflavone on insulin sensitivity and adipocytokines in insulin resistant rats administered with high-fat diet - Hong-Min Zhang; Shi-Wei Chen; Li-Shi Zhang; Xiao-Fan Feng (Natural Product Research, 2008)

Arabidopsis acyl-CoA-binding proteins ACBP4 and ACBP5 are subcellularly localized to the cytosol and ACBP4 depletion affects membrane lipid composition - Shi Xiao; Hong-Ye Li; Jiao-Ping Zhang; Suk-Wah Chan; Mee-Len Chye (Plant Molecular Biology, 2008)

Cloning and characterization of a novel cysteine protease gene (HbCP1) from Hevea brasiliensis - Shi-Qing Peng; Jia-Hong Zhu; Hui-Liang Li; Wei-Min Tian (Journal of Biosciences, 2008)

Potential inhibitors against Sclerotinia sclerotiorum, produced by the fungus Myrothecium sp. associated with the marine sponge Axinella sp. - Lian Wu Xie; Shu Mei Jiang; Hong Hui Zhu; Wei Sun; Yong Chang Ouyang; Shi Kun Dai; Xiang Li (European Journal of Plant Pathology, 2008)

Development and characterization of microsatellite loci for lotus (Nelumbo nucifera) - Hong-Li Tian; Xiao-Qing Chen; Jian-Xiu Wang; Jian-Hua Xue; Jun Wen; Grant Mitchell; Shi-Liang Zhou (Conservation Genetics, 2008)

Down-regulation of S-adenosyl-l-homocysteine hydrolase reveals a role of cytokinin in promoting transmethylation reactions - Chun-Hong Li; Nan Yu; Shi-Min Jiang; Xiao-Xia Shangguan; Ling-Jian Wang; Xiao-Ya Chen (Planta, 2008)

Mitochondria dysfunction was involved in copper-induced toxicity in MES23.5 cells - Li-Min Shi; Hong Jiang; Jun Wang; Ze-Gang Ma; Jun-Xia Xie (Neuroscience Bulletin, 2008)

Molecular characterization and phylogenetic analysis of membrane protein genes of porcine epidemic diarrhea virus isolates in China - Jian-Fei Chen; Dong-Bo Sun; Cheng-Bao Wang; Hong-Yan Shi; Xiao-Chen Cui; Sheng-Wang Liu; Hua-Ji Qiu; Li Feng (Virus Genes, 2008)

Molecular Variability of Hop stunt viroid: Identification of a Unique Variant with a Tandem 15-nucleotide Repeat from Naturally Infected Plum Tree - Yuan-Ai Yang; Hong-Qing Wang; Zu-Jian Wu; Zhuo-Min Cheng; Shi-Fang Li (Biochemical Genetics, 2008)

Determination of potential management zones from soil electrical conductivity, yield and crop data - Yan Li; Zhou Shi; Ci-fang Wu; Hong-yi Li; Feng Li (Journal of Zhejiang University-SCIENCE B, 2008)

Promotion of the articular cartilage proteoglycan degradation by T-2 toxin and selenium protective effect - Si-yuan Li; Jun-ling Cao; Zhong-li Shi; Jing-hong Chen; Zeng-tie Zhang; Clare E. Hughes; Bruce Caterson (Journal of Zhejiang University-SCIENCE B, 2008)

Molecular cloning and overexpression of a novel UDP-glucosyltransferase elevating salidroside levels in Rhodiola sachalinensis - Lan-Qing Ma; Ben-Ye Liu; Dong-Yao Gao; Xiao-Bin Pang; Shi-You Lü; Han-Song Yu; Hong Wang; Fang Yan; Zhen-Qiu Li; Yan-Fang Li; He-Chun Ye (Plant Cell Reports, 2007)

Rice Allelopathy Induced by Methyl Jasmonate and Methyl Salicylate - Hai Hong Bi; Ren Sen Zeng; Li Ming Su; Min An; Shi Ming Luo (Journal of Chemical Ecology, 2007)

Expressions of polypeptide: N-acetylgalactosaminyltransferase in leukemia cell lines during 1,25-dihydroxyvitamin D3 induced differentiation - Hao Qiu; Xiang-Hong Guo; Jian-Hua Mo; Mei-Fang Jin; Shi-Liang Wu; Hui-Li Chen (Glycoconjugate Journal, 2006)

Functional analysis of the α-neurotoxin, BmαTX14, derived from the Chinese scorpion, Buthus martensii Karsch - Kun Wang; Shi-Jin Yin; Meng Lu; Hong Yi; Chao Dai; Xiu-Jing Xu; Zhi-Jian Cao; Ying-Liang Wu; Wen-Xin Li (Biotechnology Letters, 2006)

Screening and identification of vascular-endothelial-cell-specific binding peptide in gastric cancer - Shuhui Liang; Tao Lin; Jie Ding; Yanglin Pan; Dongmei Dang; Changcun Guo; Min Zhi; Pengtao Zhao; Li Sun; Liu Hong; Yongquan Shi; Liping Yao; et al. (Journal of Molecular Medicine, 2006)

Neural responses in multiple basal ganglia regions following unilateral dopamine depletion in behaving rats performing a treadmill locomotion task - Jing-Yu Chang; Li-Hong Shi; Fei Luo; Donald J. Woodward (Experimental Brain Research, 2006)

The impacts of optical properties on radiative forcing due to dust aerosol - Hong Wang; Guangyu Shi; Shuyan Li; Wei Li; Biao Wang; Yanbin Huang (Advances in Atmospheric Sciences, 2006)

Arabidopsis ACBP3 is an extracellularly targeted acyl-CoA-binding protein - Ka-Chun Leung; Hong-Ye Li; Shi Xiao; Muk-Hei Tse; Mee-Len Chye (Planta, 2006)

The Genetic Diversity and Similarities Among Kengyilia Species Based on Random Amplified Microsatellite Polymorphism (RAMP) - Li Zhang; You-Liang Zheng; Yu-Ming Wei; Shi-Gui Liu; Yong-Hong Zhou (Genetic Resources and Crop Evolution, 2005)

Application of comprehensive geophysical techniques to predict carbonate fractured reservoirs in Qingxi oilfield - Yongmin Shi; liming Sa; Tinanxiang Duan; Xin Tian; Hong Li; Bingting Wang (Applied Geophysics, 2005)

Treatment of spinal cord injury with co-grafts of genetically modified schwann cells and fetal spinal cord cell suspension in the rat - Shi -Qing Feng; Xiao -Hong Kong; Shi -Fu Guo; Pei Wang; Li Li; Jin -Hua Zhong; Xin -Fu Zhou (Neurotoxicity Research, 2005)

Relation between precipitation and sediment transport in the Dasha River Watershed - Jian-chun Zhang; Wei Zhang; Ji-hong Li; Zhi-gang Shi; Shen-yuan Pu (Chinese Geographical Science, 2004)

A polymorphism in the promoter region of catalase is associated with blood pressure levels - Zhengwen Jiang; Joshua M. Akey; Jinxiu Shi; Momiao Xiong; Ying Wang; Yayun Shen; Xiaoyun Xu; Hua Chen; Hong Wu; Junhua Xiao; Daru Lu; Wei Huang; et al. (Human Genetics, 2001)

The Myxococcus xanthus wbgB gene encodes a glycosyltransferase homologue required for lipopolysaccharide O-antigen biosynthesis - Zhaomin Yang; Dongchuan Guo; M. Gabriela Bowden; Hong Sun; Leming Tong; Zhuo Li; Alfred E. Brown; Heidi B. Kaplan; Wenyuan Shi (Archives of Microbiology, 2000)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)

Multiple genotypes of mitochondrial DNA within a horse population from a small region in Yunnan province of China - Wen Wang; Ai-hua Liu; Shi-ying Lin; Hong Lan; Bing Su; De-wen Xie; Li-ming Shi (Biochemical Genetics, 1994)